La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Nouveaux cahiers de recherche, 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Les femmes dans l’industrie musicale canadienne francophone - Bissonnette, Joëlle (Fondation Musicaction, 2022)

Au-delà des "vagues" #moiaussi : Cinq ans de mobilisation féministe en musique au Québec (2017-2022) - Blais-Tremblay, Vanessa; Champagne, Lysandre (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2022)

Jumol-Julia Edéry’s Wedding in Early 20th Century Morocco - Cohen, Judith R. (Canadian Jewish Studies/Études juives canadiennes, 2022)

Alanis Obomsawin: Lifework - Hill, Richard William; Peleg, Hila; Haus der Kulturen der Welt (Prestel Publishing, 2022)
"One of today's most important documentary filmmakers, Alanis Obomsawin has dedicated her life's work to shining a light on the injustices experienced by Canada's Indigenous people. This retrospective monograph features an extensive interview with Obomsawin and includes stills and reflections on her entire career including her most recent series devoted to the rights of Indigenous children. Never shying away from controversy, Obomsawin's films have played a critical role in exposing ongoing systemic bias towards Indigenous populations-from fishing rights and education to health care and treaty violations. Obomsawin is also a graphic artist, and she incorporates her often dream-inspired etchings and prints into many of her films. This volume includes illuminating essays exploring Obomsawin's practice and mission as well as personal commentary from collaborators, archival materials, and photographs from the filmmaker's personal life and professional exploits. As Obomsawin closes in on her ninth decade of life-and fifth decade behind the camera-this beautifully illustrated record of her astounding body of work and tireless efforts on behalf of Indigenous peoples and culture is an inspiring celebration of the power of film to dramatically change the course of history"-- Provided by publisher.

Une médiation de la musique au masculin ? Analyse des dispositifs numériques de médiation de la musique produits par les institutions musicales - Kirchberg, Irina (Digital Studies/Le champ numérique, 2022)
Dans le sillage de l’ouvrage dirigé par Octobre et Patureau (Octobre et Patureau 2018), cet article engage à une réflexion sur le traitement de la question du genre dans les dispositifs numériques de médiation produits par des organismes de diffusion et de production musicale. Les études en sociologie du travail artistique (Coulangeon et Ravet 2003 ; Buscatto 2007 ; Bousquet et al. 2018) ne cessent de montrer que l’ensemble des mondes de la musique, aussi bien classiques que jazz ou pop, est traversé par une double ségrégation genrée horizontale (répartition sexuée selon le type d’emploi) et verticale (moindre accès aux postes à responsabilités). On pourrait imaginer que les producteurs de dispositifs numériques de médiation de la musique, portant des valeurs de vivre-ensemble, d’inclusion sociale et d’agentivité (Perez-Roux et Montandon 2014 ; Carrel 2017), et conscients des effets normatifs et prescriptif des supports éducationnels (Octobre 2014), viennent questionner ces frontières. Le « dénombrement » et l’analyse de « cas » tirés du dépouillement systématique d’une centaine dispositifs numériques consultables en ligne et produits par des organismes de production et de diffusion musicale permettront de montrer que tel n’est pas le cas.

"[N]ou rasanble" : rassemblements hétérolingues et hétérogènes dans les chansons de Muzion - Leclerc, Catherine (Analyses, 2022)
Muzion a été parmi les tout premiers groupes de rap québécois à faire résonner une parole locale distinctive. Il le faisait dans un français mâtiné d’anglais et de créole haïtien, multipliant les registres et faisant des emprunts à encore d’autres langues. Cet article se penche sur les chansons du premier album du groupe, Mentalité moune morne, à partir de son hétérolinguisme et des questions d’appartenance que celui-ci soulève. Il examine la manière dont Muzion entrelace les langues, mais aussi les interpellations, défaisant l’association entre langue et identité. Le groupe s’adresse ainsi à la fois à une communauté immigrante locale (d’abord haïtienne, mais également pluriethnique et racisée) qu’il québécise, et à une communauté québécoise élargie qu’il pluralise. Le rap permet en outre à ses membres de faire entendre leurs voix individuelles distinctes, notamment grâce à des usages différenciés de la palette plurilingue du groupe. Ce faisant, ce sont les notions même d’appartenance et de communauté que Muzion se trouve à refaçonner, à l’encontre de toute forme d’homogénéisation, de figement ou de stéréotype.

Parcours professionnels de musiciennes migrantes : de la théorie à l'expérience. Note de terrain à propos du colloque Femmes musiciennes du monde tenu les 26 et 27 novembre 2021 au Centre des musiciens du monde - Marcoux-Gendron, Caroline; Champagne, Lysandre (La Revue musicale OICRM, 2022)

“Before I made fims, I was singing” - Obomsawin, Alanis; Gagnon, Monika Kin (Alanis Obomsawin: Lifework, 2022)

Les rappeuses québécoises sur le devant de la scène : autorité lyrique de la voix féminine chez Donzelle et MCM - Simard, Mathieu; Kirouac Massicotte, Isabelle (Analyses, 2022)

Stories I Might Regret Telling You: A Memoir - Wainwright, Martha (Hachette Books, 2022)
The singer-songwriter's heartfelt memoir about growing up in a bohemian musical family and her experiences with love, loss, motherhood, divorce, the music industry, and more. Born into music royalty, the daughter of folk legends Kate McGarrigle and Loudon Wainwright III and sister to the highly-acclaimed and genre-defying singer Rufus Wainwright, Martha grew up in a world filled with such incomparable folk legends as Leonard Cohen; Suzzy Roche, Anna McGarrigle, Richard and Linda Thompson, Pete Townshend, Donald Fegan, and Emmylou Harris. It was within this loud, boisterous, carny, musical milieu that Martha came of age, struggling to find her voice until she exploded on the scene with her 2005 debut critically acclaimed album, Martha Wainwright, containing the blistering hit, 'Bloody Mother F*cking Asshole,' which the Sunday Times called one of the best songs of that year. Her successful debut album and the ones that followed such as Come Home to Mama, I Know You're Married But I've Got Feelings Too, and Goodnight City came to define Martha's searing songwriting style and established her as a powerful voice to be reckoned with. In her memoir, Stories I Might Regret Telling You, Martha digs into the deep recesses of herself with the same emotional honesty that has come to define her music. She describes her tumultuous public-facing journey from awkward, earnest, and ultimately rebellious daughter, through her intense competition and ultimate alliance with her brother, Rufus, to the indescribable loss of their mother, Kate, and then, finally, discovering her voice as an artist. With candor and grace, Martha writes of becoming a mother herself and making peace with her past struggles with Kate and her former self, finally understanding and facing the challenge of being a female artist and a mother. Ultimately, Stories I Might Regret Telling You offers readers a thoughtful and deeply personal look into the extraordinary life of one of the most talented singer-songwriters in music today.

L’avenir. Les changements que les personnes répondantes souhaitent voir concernant le harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision - Aftermetoo (2021)
Keywords: Pas de lien web

L’état des choses. Le harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision - Aftermetoo (2021)
Keywords: Pas de lien web

Le suivi. Dénonciation, soutien et qui cause le préjudice? Concernant le harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision. - Aftermetoo (2021)
Keywords: Pas de lien web

Les dommages. Les répercussions sur les personnes survivantes du harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision - Aftermetoo (2021)
Keywords: Pas de lien web

Principaux constats. Résultats de la toute première enquête sur le harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision - Aftermetoo (2021)
Keywords: Pas de lien web

Sur le terrain. La parole aux personnes survivantes. Suggestions écrites concernant le harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision - Aftermetoo (2021)
Keywords: Pas de lien web

Naviguer les attentes genrées de la communauté de danse swing de Montréal - Batty, Megan (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Gender and Extreme Metal: Understanding Gender Relations in the Montreal Extreme Metal Scene With Schippers' Gender Framework - Beauchamp, Caroline (Université Concordia, 2021)
Extreme metal is a masculine space, yet more and more women join in. They face a contradiction: as women, they are expected to adopt feminine behaviours; however, they are part of a subculture that valorizes warrior masculinity. I sought to understand the gender expectations of the Montreal extreme metal scene and interpret the contradictions encountered by women in this scene with the help of Schippers’ (2007) theoretical framework on gender. To do so, I conducted 16 individual interviews with women and men who take part in the scene. This research fills a gap in the literature on gender that derives from Connell and Schippers’ writings and addresses issues that the field of metal studies has brushed over. I found that metal men are the “default” participants in the scene. They are expected to be fine music connoisseurs and even become musicians. In contrast, women’s presence is heterosexualized and attributed to a romantic or sexual interest in metal men. Women are suspected of being “poseuses” or groupies with no real interest in the music until proven otherwise. To become legitimate participants, they have to overcome those expectations and prove that they are worthy of being viewed through the prism of masculinity rather than femininity. They do so by proving their exceptionality through manhood acts and distancing themselves from other women. Despite their gender transgressions, women’s presence does not fundamentally question gender relations but reaffirms the overall primacy of masculinity over femininity.

Myriam Boucher + Followup - Boucher, Myriam (Taking the Temperature: Crisis, Curating, and Musical Diversity, 2021)
The caesura in musical production caused by recent global lockdowns has made contemporary music’s crisis of societal relevancy more apparent than ever. Bringing together interviews with music curators, musicians, activist networks and institutional leaders, this book details existing practices and approaches, showing that change is possible but only if the recent wave of interest in curatorial practices, diversity and divestment from a white, European bourgeois aesthetic are taken seriously by the musical establishment. This expanded second edition of Taking the Temperature adds a new preface, five new interviews, as well as followups with previous interviewees. Radiating out from the Ultima Festival and Oslo, ..

Les îles (2011) d’Isabelle Panneton et l’héritage de Philippe Boesmans : généalogie d’une démarche compositionnelle - Brasset, Marie-Pierre (Circuit : musiques contemporaines, 2021)
Dans les années 1980, après ses études auprès de Gilles Tremblay, Isabelle Panneton fait la rencontre de Philippe Boesmans lors d’un passage du compositeur belge à Montréal. Impressionnée par sa musique, elle se rendra en Belgique pour y suivre des leçons de composition avec lui de 1984 à 1987. Cette période sera déterminante pour la compositrice, ouvrant toute grande la porte à l’émergence de sa personnalité musicale. Ce texte retrace les moments forts du passage d’Isabelle Panneton chez le compositeur belge et met en lumière les liens qui les unissent, en guise de prélude à l’analyse de son trio Les îles pour violon, violoncelle et piano.
Keywords: Belgique; Belgium; Isabelle Panneton; Philippe Boesmans; chamber music; développement motivique; motivic development; musique de chambre

Do We Really Want to Keep the Gate Threshold That High? - Brooks, Grace; Pras, Amandine; Elafros, Athena; Lockett, Monica (Journal of the Audio Engineering Society, 2021)
Drawing upon the survey instruments of Lewis and Neville [1], Nadal [2], and Yang and Carroll [3], we conducted an online survey that captured experiences of discrimination and microaggressions reported by 387 recording engineers, producers, and studio assistants living in 46 different countries. Our statistical analyses reveal highly significant and systemic gender inequalities within the field, e.g., cisgender women experience many more sexually inappropriate comments (p < e-14, large effect size) and unwanted comments about their physical appearance (p < e-12, large effect size) than cisgender men, and they are much more likely to face challenges to their authority (p < e-13, large effect size) and expertise (p < e-10, large effect size). A comparison of our results with a study about women’s experiences of microaggressions within STEM academia [3] indicates that the recording studio workplace scores 33% worse on the silencing and marginalization of women, 33% worse on gender-related workplace microaggressions, and 24% worse on sexual objectification. These findings call for serious reflection on the part of the community to progress from awareness to collective action that will unlock the control room for women and other historically and systemically marginalized groups of studio professionals.

Lise Vachon and “Octobre au mois de mai”: Relistening to the Québécois Revolution - Cancel-Bigay, Mario R. (Sounds that Fall Through the Cracks, and Other Silences and Acts of Love: Decoloniality and Anticolonialism in Puerto Rican Nueva Canción and Chanson Québécoise [thèse de doctorat, Université Columbia], 2021)

Marie-Claire Séguin: Feminism and Settler Colonialism in “Mater Maria” - Cancel-Bigay, Mario R. (Sounds that Fall Through the Cracks, and Other Silences and Acts of Love: Decoloniality and Anticolonialism in Puerto Rican Nueva Canción and Chanson Québécoise [thèse de doctorat, Université Columbia], 2021)

"If you see me walking alone on the road": Sephardic Songs of Exile, Expulsion, Memory – and Return - Cohen, Judith R. (Armenian and Jewish Experience between Expulsion and Destruction, 2021)

David Denada - Farnsworth, Brandon (Taking the Temperature: Crisis, Curating, and Musical Diversity, 2021)

Barbara Scales - Farnsworth, Brandon; Massera, Vanessa (Taking the Temperature: Crisis, Curating, and Musical Diversity, 2021)

Étude patrimoniale sur le katajjaniq - Gadoua, Marie-Pierre (Publications Nunavik, 2021)
Ce livre présente une résumé exhaustif de l’étude effectuée sur le katajjaniq, suite à la désignation de cette pratique à titre de premier élément du patrimoine immatériel québécois.

Interroger l'expérience d'un chœur féministe : le cas du Chœur Maha - Harrison-Boisvert, Catherine (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Black Women Dancers, Jazz Culture, and “Show Biz”: Recentering Afro-Culture and Reclaiming Dancing Black Bodies in Montréal, 1920s–1950s - Jabouin, Emilie (Canadian Journal of History, 2021)
The documentary Show Girls, directed by Meilan Lam, makes an unprecedented contribution to the history of jazz and Black women jazz dancers in Montréal, Quebec, and to the conversation of jazz in Canada. Show Girls offers a glimpse into the lives of three Black women dancers of the 1920s–1950s. This essay asks what the lives of Black women dancers were like and how they navigated their career paths in terms of social and economic opportunities and barriers. I seek to better understand three points: (1) the gap in the study of jazz that generally excludes and/or separates dance and singing from the music; (2) the use of dance as a way to commercialize, sell, and give visual and conceptual meaning to jazz; (3) the importance of the Black body and the role of what I would define as “Afro- culture” in producing the ingenious and creative genre of jazz. My study suggests there is a dominant narrative of jazz, at least in academic literature, that celebrates one dimension of jazz as it was advertised in show business, and that bringing in additional components of jazz provides a counternarrative, but also a restorative, whole and more authentic story of jazz and its origins. More specifically, by re- exploring jazz as a whole culture that relies on music, song, and dance, this essay explores three major ideas. First, Black women dancers played a significant role in the success of jazz shows. Second, they articulated stories of self, freedom, and the identity of the New Negro through jazz culture and dance. Third, Black women’s bodies and art were later crystallized into images that further served to sell jazz as a product of show business.

Dick Montgomery et la personnification féminine afrodescendante en Amérique du Nord, 1935-1960 - Jacques, Raphaël (Histoire Engagée, 2021)

Terri Hron (Canadian New Music Network) - Jakobsson, Anna (Taking the Temperature: Crisis, Curating, and Musical Diversity, 2021)

Black Gold: A Black Feminist Art History of 1920s Montréal - Joachim, Joana (Canadian Journal of History, 2021)
The 1920s have been touted as the golden era of jazz and Black history in Montréal. Similarly, the decade is well known for the Harlem Renaissance, a key moment in African American art history. Yet this period in Black Canadian art histories remains largely unknown. As a first step toward shedding some light on this period in Black Canadian art history, I propose to use what I term a Black feminist art-historical (bfah) praxis to discuss some visual art practices undoubtedly active alongside well-known jazz musicians and cultural producers in 1920s Montréal. This paper presents an overview of critical race art history and feminist art history, as well as Black feminist approaches to visual representation, to outline what might be considered four tenets of bfah praxis. Applying these tenets, I propose that a new art history may emerge from well-known art objects and practices as well as lesser-known ones. I posit that through a deliberately bfah approach, new meanings emerge and the voices of Black women, even when obstructed by mainstream white narratives, may begin to stand out and shed light upon a variety of histories. This praxis aims to underline the subtext lurking at the edges of these images and to make intangible presences visible in the archive and in art history. I propose bfah as a strategy for more nuanced discussion of the work of Black Canadian artists and histories that have by and large been left out of official records.

Nueva vida : Mener la danse avec un trouble de santé mentale - K, Florence (2021)
« Un trouble de santé mentale impose souvent le travail d'une vie, soit un profond apprentissage de soi, de sa maladie et de la maîtrise de celle-ci. Pour arriver un jour à valser avec son état et à mener la danse. » Nueva vida, c'est le récit d'un cheminement vers une nouvelle vie. C'est la preuve que, comme les chats, on peut retomber sur ses pattes neuf fois, sinon plus. Après la parution de Buena vida, alors que tout devrait bien aller, Florence K sent encore le trou noir qui la guette. Puis un psychiatre pose enfin un diagnostic sur le précipice au bord duquel elle marche depuis plusieurs années : celui de la bipolarité de type II. À partir de ce moment, avec un suivi et un traitement adapté, elle a pu atteindre un équilibre durable. Dans ce récit touchant, elle se livre avec transparence, pour briser les tabous et la solitude, plaider pour un meilleur accès aux soins et apporter de l'espoir à tous ceux qui connaissent les aléas vertigineux d'un trouble de santé mentale.

Énonciation, sexualités et genre en musique chez Philémon Cimon, Pierre Lapointe et Ariane Moffatt - Konaté, Khady (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Dans ce texte est proposée une « lecture du genre » (Boisclair 2002) des oeuvres de Philémon Cimon (L’été, Les femmes comme des montagnes), Pierre Lapointe (Pierre Lapointe, Sentiments humains) et Ariane Moffatt (Aquanaute, Le coeur dans la tête, Tous les sens). L’étude des chansons contenues sur ces albums prend pour point de départ une interrogation des subjectivités genrées de ces trois artistes, entre personne réelle et persona, et montre que ces dernières façonnent leurs compositions. La sollicitation du concept de sexe/genre ouvre dès lors la porte à l’exploration des représentations des identités sexuelles et de genre dans ces chansons, où les identités des artistes se trouvent mises en abîme. En s’intéressant à l’énonciation et au discours (en particulier, au discours amoureux) contenu dans le texte des chansons sélectionnées, il est possible de rendre compte de la reproduction des injonctions à l’hétérosexualité et des poncifs qui cloisonnent le genre, ainsi que des glissements et brouillages qui autorisent des resignifications du genre. Ainsi, chez Cimon, on observe la reconduite du point de vue masculin où la valeur du féminin réside dans sa capacité à émerveiller le sujet et à susciter son désir. À l’opposé, les textes de Lapointe et Moffatt dépeignent des personnages et des récits queer, bien que leur identité queer n’ait pas été revendiquée à l’heure de la parution de leurs oeuvres.

Une chanteuse épanouie : Renée Claude (1939-2020) - Laberge, Yves (Cap-aux-Diamants : la revue d'histoire du Québec, 2021)
Un article de la revue Cap-aux-Diamants, diffusée par la plateforme Érudit.

Chronologie de plus de cent ans de présence féminine dans la création d'œuvres musicales au Québec : un premier survol - Lefebvre, Marie-Thérèse (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Lynda Lemay. Il était une fois mes chansons - Lemay, Lynda; Vignol, Baptiste (Éditions Gründ, 2021)

Genre, rap et enjeux de la visibilité dans l'espace public des rappeuses à Montréal : de la gestion de l'apparence physique pour être reconnue en tant qu'artiste - Lesacher, Claire (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Avant-propos. Björk, Montréal et le Nunavut - McKinley, Maxime (Circuit : musiques contemporaines, 2021)
An article from Circuit, on Érudit.

Mary Travers Bolduc ou Madame Édouard Bolduc, pionnière de la chanson populaire au Québec - Melançon, Johanne (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Longtemps dénigrée par une certaine élite et plus ou moins ignorée des ouvrages sur la chanson, Mary Travers Bolduc (1894-1941) est aujourd’hui considérée comme étant la première autrice-compositrice-interprète, ainsi que la toute première vedette de la chanson populaire québécoise. À une époque où les femmes bénéficient de peu ou pas d’autonomie, sa carrière semble à la fois une anomalie et un exploit. Cependant, l’image de la femme indépendante qui gère sa carrière et organise ses tournées apparaît en contradiction avec les chansons où elle reste fidèle aux valeurs traditionnelles de sa génération et de son public quant au rôle de la femme dans la société. Réécouter les chansons de Mme Bolduc et parcourir les archives permettent de mieux comprendre qui était celle que l’on surnommait « La Bolduc », — à la fois femme, épouse et mère, ainsi qu’artiste autodidacte et « reine de la chanson comique », à mi-chemin entre le folklore et la chanson populaire —, et aident à la compréhension de ce pourquoi sa réception critique a été aussi longtemps mitigée. On peut également mieux mesurer la valeur de son oeuvre en lien avec la société dans laquelle elle a évolué, ainsi qu’émettre le constat que la condescendance de certains à son égard au cours de sa carrière, tout comme le silence qui a suivi son décès, relèvent de préjugés ; non pas parce qu’elle était une femme, mais à cause de la classe sociale à laquelle elle appartenait et dont elle a été le miroir. Ce n’était pas tant le propos de ses chansons qui dérangeait mais bien son niveau langue, le ton parfois grivois et le style de sa musique, ce qui a pourtant garanti son succès auprès des spectateurs. Sa réhabilitation au cours des années 1960, dans le contexte d’une revalorisation du folklore et de l’âge d’or de la chanson joualisante, s’explique par l’évolution de l’horizon d’attente et du goût du public.

Dream visions: The Art of Alanis Obomsawin - Obomsawin, Alanis (Perceval Press, 2021)

The Double Bind That Is Not a Bond: Cohen and Women - Pally, Marcia (From This Broken Hill I Sing to You: God, Sex, and Politics in the Work of Leonard Cohen, 2021)
Leonard Cohen's troubled relationship with God is here mapped onto his troubled relationships with sex and politics. Analysing Covenantal theology and its place in Cohen's work, this book is the first to trace a consistent theology across sixty years of Cohen's writing, drawing on his Jewish heritage and its expression in his lyrics and poems.Cohen's commitment to covenant, and his anger at this God who made us so prone to failing it, undergird the faith, frustration, and sardonic taunting of Cohen's work. Both his faith and ire are traced through: · Cohen's unorthodox use of Jewish and Christian imagery · His writings about women, politics, and the Holocaust · His final theology, You Want It Darker, released three weeks before his death.
Keywords: Music / General; Religion / Judaism / Theology; Religion / Theology

Alys Robi a été formidable. Nouveau regard sur une figure d'avant-garde - Ringuet, Chantal (Québec Amérique, 2021)
Flamboyante et indépendante, Alys Robi a marqué le Québec en étant sa première star internationale puis en voyant sa carrière s’interrompre brutalement, à vingt-cinq ans à peine, lorsqu’elle est internée contre son gré. Mais au-delà de ces deux grands axes à partir desquels on la raconte toujours, qui était-elle ? Pourquoi a-t-elle été internée ? Pourquoi, surtout, a-t-on oublié à quel point elle a été formidable ?Chantal Ringuet a plongé dans les archives de cette femme qui était sa grand-tante afin d’en brosser enfin un portrait exhaustif et de réhabiliter la mémoire d’une artiste exceptionnelle. Dans cette émouvante biographie qui flirte avec l’essai littéraire, elle nous entraîne dans l’envers du décor, sur les traces de cette diva qui a été tour à tour reine de la chanson, féministe avant l’heure, traductrice littéraire, porte-parole pour la santé mentale, incarnation du kitsch et égérie de la communauté gaie. Une femme qui, malgré les épreuves inouïes qu’elle a affrontées, a poursuivi son chemin la tête haute.

Les femmes et la chanson au Québec : quels cadrages ? pour quelles histoires ? - Savoie, Chantal (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Black Media Reporting on Theater, Dance, and Jazz Clubs in Canada: From Shuffle along to Rockhead’s Paradise - Thompson, Cheryl; Jabouin, Emilie (Journal of Communication Inquiry, 2021)
Canada has a history of de facto Jim Crow (1911–1954). It also has a historical Black press that is intimately connected to Black America through transnational conversations, and diasporic migration. This article argues that Canada’s Black newspapers played a pivotal role in promoting Black performance during a time when they were scarcely covered in the dominant media. Drawing on news coverage from the 1920s through 1950s of black dance, musicals, and jazz clubs this article examines three case studies: Shuffle Along (1921–1924), the first all- Black Broadway musical to appear at Toronto’s Royal Alexandra Theater, Alberta-born dancer Len Gibson (1926–2008), who revolutionized modern dance in Canada in the 1940s and 1950s, and the Montreal jazz club Rockhead’s Paradise (1928–1980), a pivotal site in the city’s Little Burgundy, a Black neighborhood that thrived in the 1930s through 1950s. The authors argue that when Black people were excluded from and/or derogatorily portrayed in the dominant media, Canada’s Black press celebrated collective achievement by authenticating Black performance. By incorporating Canada’s Black Press into conversations about Jim Crow and performance, we gain a deeper understanding of Black creative output and resistance during the period.

Situer les femmes dans l'Electronic dance music culture (EDMC) à Montréal, entre 1950 et 1955 : premier survol - Van Vliet, Kiersten (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Quadruple défi pour les artistes femmes, immigrantes et allophones : Le cas du premier Sarau das Minas Montréal - Vasconcellos de Carvalho, Dalila (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Fracturing Patriarchal Objectivity through Electro-Pop: Purity Ring and the vicissitudes of sight - Watkinson, Philip (Performance Research, 2021)
This article examines the deviated modes of seeing in the work of Canadian electro-pop band Purity Ring. Bringing their recent music into conversation with the theory of Tim Ingold and Eugenie Brinkema, I suggest that Megan James and Corin Roddick perform seeing as a granular, augmented act that continually shapes the boundaries between our bodies and the world around us. Particular attention is paid to James and Roddick’s creative engagement with optical touch and the formal capability of music to engage affectively with the act of seeing.By integrating musical examples, Tallulah Fontaine’s artwork for the band and the poetry of Kiran Millwood Hargrave, this article offers an expanded reading experience that spans the textual, the aural and the visual. I argue that the political crux of Purity Ring’s performance of perception lies in them moving beyond a reactionary response to patriarchal objectivity and towards a creative refiguration of perception as a form of subjectivation. The eyes that Purity Ring instantiate do not passively observe the world; they change it, both consoled and engulfed by the vicissitudes of perception.

« Changer le monde un hit à la fois » ? Programmation et diversité à CKOI-FM - Watson, Jada (Les Cahiers de la Société québécoise de recherche en musique, 2021)
En mars 2019, Stéphanie Vallet a publié un article dans La Presse portant sur la sous-représentativité des artistes féminines dans le palmarès Billboard « Canadian Hot 100 ». Les résultats de son étude démontrent une forte décroissance de la présence des femmes dans l’industrie musicale canadienne — un écosystème dans lequel les ondes radio continuent de jouer un rôle important quant à la découvrabilité et à la professionalisation des artistes. Cependant, au-delà des questions de genre abordées par Vallet, les enjeux liés à la représentativité des artistes issu·es de la diversité ethnoculturelle et linguistique à la radio doivent également être soulevés. Les théories de « social remembering » (Misztal 2003 ; Strong 2011) offrent un cadre critique pour se pencher sur les « Big Data » compilées par des industries où les femmes et les artistes racisé·es semblent systématiquement désavantagé·es. Dans le but d’entamer le portrait de la représentativité sur les ondes de la radio commerciale au Québec, cet article aborde la représentativité des artistes minorisé·es sur les ondes de CKOI-FM (96.9) de Montréal. CKOI-FM a été choisie non seulement parce qu’il s’agit d’une station francophone « top 40 » (diffusant tous les genres musicaux), mais aussi parce qu’entre 2015 et 2017 elle utilisait le slogan « Changeons le monde un hit à la fois » (Girard 2017) — un message à fortes résonances avec les slogans militants visant la justice sociale. Ce projet offre donc l’occasion d’investiguer la validité des déclarations faites par une radio qui se vante de « changer le monde ». En adoptant une approche féministe intersectionnelle à l’analyse des données appelée « data feminism » (d’après D’Ignazio et Klein 2020), cette étude évaluera les différents taux de représentativité à CKOI-FM parmi les 100 chansons les plus jouées chaque année entre 2010 et 2020 afin de considérer le rôle que jouent les ondes radio dans la formation de la culture musicale populaire au Québec et, par extension, de la mémoire sociale.

Sounding the Arctic in Chantal Bilodeau’s Climate Change Plays - Balestrini, Nassim W. (Nordic Theatre Studies, 2020)
Quebec-born playwright Chantal Bilodeau has been responding to the challenges of dramatizing anthropogenic climate change by developing an eight-part Arctic Cycle, each play of which is set in one of the nations that claims Arctic territory. Sila (2014) immerses audiences into a complex network of humans, animals, and mythical beings crisscrossing the Canadian Arctic. These movements circle around the Inuit concept of sila, which is the life-giving force of breath and voice. Thus, the sonic world of Sila focuses on voices speaking words, on performance poetry, and on the sounds of breath and wind. Bilodeau’ s second Arctic Cycle play, Forward (2016), addresses the long-term impact of Fridtjof Nansen’s polar exploration of the 1890s on Norway’s economy and society. In terms of sound, Forward features multiple musical performances rangingfrom traditional songs to European opera arias and Lieder to contemporary Norwegian electro-pop. The sonic features of both plays stress interdependence across time, space, as well as (non-)human, earthly, and metaphysical realms. Sila and Forward address climate change in a non-universalizing manner which promotes a heterarchical (rather than hierarchical) aesthetic fit for a growing awareness of planetary relationality.
Keywords: Theory and practice

Gender and Embodiment in the Contemporary Montreal Swing Dance Community - Batty, Megan (Université McGill, 2020)
"This thesis explores embodiment and gender within the contemporary Montreal swing dance community. Drawing on scholarship in musicology, dance studies, jazz studies, and gender studies, I investigate the relationship between dancers and musicians/DJs. I explore the many facets of this choreomusical conversation and trace this dialogic and collaborative relationship on the social dance floor. The contemporary community is a product of the swing revival and navigating issues of authenticity thus becomes an important consideration for dancers, musicians, and DJs alike. One product of this revival is the set of heteronormative values that underpin the contemporary community. I investigate to what extent these values are reified, challenged, or altogether subverted by participants through musical and choreomusical choices. To this end I conducted interviews with six informants, each of whom has experience as both a dancer and musician and/or DJ. Their privileged position arising from their dual experience affords them insight on the ways in which dancers and musicians/DJs function within the community. This thesis builds on existing scholarship by situating the voices of individuals with choreomusical experience in dialogue with existing scholarship, and ultimately revalues the importance of both embodied knowledge and gender within the swing community"-- Author's abstract

Louise Campbell. Une médiatrice dans l’être - Bertomeu, Fanny (Revue musicale OICRM, 2020)
Formed as a musician and a clarinetist, Louise Campbell is now a music mediator. Based in Montreal, she practices her profession through several structures and for a wide variety of audiences (schoolchildren, professionals, people with disabilities ...) all around Canada, but mainly in Quebec. In this interview, Louise Campbell recounts her experience as a mediator, her (non)-formation in this profession, as well as many aspects in her practice. With the musical object and the creation at the heart of her workshops, Louise Campbell always seeks to establish a “horizontal” exchange relationship with each person she meets.
Keywords: Louise Campbell; creation; création; music mediation; médiation de la musique; partage; relation; relationship; sharing

“Maple Leaf Rag” in Maple Leaf Country: Impressing Jazz upon Vera Guilaroff - Blais-Tremblay, Vanessa (Women and Music: A Journal of Gender and Culture, 2020)

Pauline Julien, intime et politique (2018) - Carlos, Jean-Philippe (Bulletin d'histoire politique, 2020)

Bïa Krieger versionista: Três cançoes de Chico Buarque em francês [Bïa Krieger, versionista. Trois chansons de Chico Buarque en français] - Cassiano, Raissa Conde (Université de São Paulo, 2020)

TAGS de Joane Hétu et TanGRAM de Danielle Palardy Roger : signatures plurielles et figure continue - Dall’Ara-Majek, Ana (Circuit : musiques contemporaines, 2020)
TAGS by Joane Hétu and TanGRAM by Danielle Palardy Roger are two written works that showcase graphic scores in improvised music. TAGS creates an encounter between Ensemble SuperMusique, the saxophone quartet Quasar, and the Bozzini Quartet. The musicians make “sound graffiti” on an imaginary wall represented by a sequence of timed sections on a descriptive score where the composer uses different instrumental combinations. Using an aesthetic of articulated gestures, the work is made through these multiple signatures. TanGRAM brings together twenty instrumentalists from Ensemble SuperMusique. The game of Tangram is represented in the form of a graphic score where each piece has specific musical properties to be interpreted by the musicians. Rich in combinatorial and symmetrical games, the work presents Orion: a continuous figure, a slowly moving flow where each musician seeks their own way in a global sound.
Keywords: Analyse musicale; Danielle Palardy Roger; Joane Hétu; Musical analysis; graphic score; improvised music; musique improvisée; partition graphique

Blondie B, rappeuse des premières heures au Québec - Desfossés, Félix B. (Les racines du hip-hop au Québec. Tome 1, 2020)

Wavy Wanda et Baby Blue, pionnières du rap à Montréal - Desfossés, Félix B. (Les racines du hip-hop au Québec. Tome 1, 2020)

Mouffe. Au cœur du showbiz - Dumas, Carmel; Monfette, Claudine (Éditions La Presse, 2020)
La parolière d’Ordinaire et du Mur du son, c’est elle. La muse du jeune Charlebois, c’est encore elle. La metteure en scène de spectacles mythiques (Magie rose, J’ai vu le loup, le renard, le lion) et d’innombrables galas, c’est toujours elle. « Elle », c’est Mouffe, figure légendaire du Québec en marche, née Claudine Monfette, alouette ! Diplômée de l’École nationale de théâtre, interprète de chansons en duo et de rôles d’ingénue, éternelle tête chercheuse, semeuse de bonnes idées et mentore de la relève, elle a contribué à faire de notre milieu artistique ce qu’il est. Journaux personnels de Mouffe, entrevues avec celle-ci mais aussi avec sa famille, ses amis, ses collègues : Carmel Dumas a remonté pendant plus de dix ans le fil de cette vie palpitante et trace ici le portrait d’une femme omniprésente et effacée, fantaisiste et sage. Une vieille âme enveloppée de candeur, extraordinaire survivante.
Keywords: Biography & Autobiography / Artists, Architects, Photographers

Sacred Song Sisters: Choral and Solo Vocal Church Music by Women Composers for the Lenten Revised Common Lectionary - Elliott, Lisa A. (Université du Nevada, 2020)
This document explores sacred music by women composers for the Revised Common Lectionary (RCL) of the Catholic and Christian churches. The study researches exclusively choral and vocal solo music by women composers for the church season of Lent. Other primary limitations include music in English, and music from the nineteenth century to the present. The main question answered in this document is: what sacred music has been published by women composers that may be programmed in church services? This question is answered in the included appendices. These appendices list the music by women composers appropriate for the specific RCL readings for each Sunday of Lent, as well as the holidays of Ash Wednesday, Maundy Thursday, and Good Friday. There are also appendices of choral and solo vocal pieces that are generally appropriate for the Lenten season. Every attempt was made to be as thorough as possible in identifying this music, with the understanding that no one compilation of this kind can ever be complete. Additionally, selected works by six composers are explored in this document: Emma Lou Diemer (b. 1927), Arletta O’Hearn (b. ca 1928), Jane M. Marshall (1924 – 2019), Rebecca Clarke (1886 – 1979), Violet Archer (1913 – 2000), and Undine Smith Moore (1904 – 1989). These composers are representative of the variety of styles, diversity, history, and levels of musical complexity within this body of music.
Keywords: Choir; Christ; Female; Service; Sing; Worship

Renée Claude. Donne-moi le temps - Girard, Mario (Éditions La Presse, 2020)
À l’aube des années 1960, Renée Claude fait ses débuts de chanteuse en interprétant Ferré, Béart et Brassens, mais aussi, et surtout, les siens (Ferland, Léveillée, Vigneault, DesRochers, Lelièvre). Sa rencontre avec l’auteur-compositeur Stéphane Venne, puis son association avec le parolier Luc Plamondon marqueront un point tournant dans sa carrière. Pendant plus d’une décennie, Renée Claude enchaînera les succès. « C’est notre fête aujourd’hui », « Le début d’un temps d’un nouveau », « Le tour de la terre », « Viens faire un tour », « Tu trouveras la paix », « Un gars comme toi », « Ce soir je fais l’amour avec toi » ... Au début des années 1980, alors que d’autres chanteuses de sa génération rendent les armes, Renée Claude connaît une incroyable renaissance avec un cycle d’hommages à Clémence DesRochers, Georges Brassens et Léo Ferré. Offerts aux quatre coins du monde pendant plus de 30 ans, ces spectacles confirmeront son grand talent d’interprète. Grâce à des dizaines d’entretiens, le journaliste Mario Girard retrace le fascinant parcours de plus de 50 ans de cette artiste incomparable. À travers son histoire, il raconte aussi celle du Québec qui a émergé de la Grande Noirceur pour se tailler une identité à sa mesure. Et on peut affirmer que Renée Claude y a largement contribué.
Keywords: Biography & Autobiography / Entertainment & Performing Arts; Biography & Autobiography / General; Biography & Autobiography / Music

Jocelyne Binet's Cycle de Mélodies: Unearthing a Forgotten Song Cycle - Hoch, Matthew (Journal of Singing, 2020)
Montreal composer Jocelyne Binet's "Cycle de Melodies sur des Poemes de Paul Eluard" was programmed in 1955 by the French baritone Gerard Souzay in a performance that was most likely the world premiere. Unfortunately, Binet's song cycle never was published, and the work soon was forgotten. In the fall of 2016, the author discovered Bineet's original handwritten manuscript pages in holdings of Bibliotheque et Archives Nationales du Quebec and began the process of reconstructing the score. This article discusses the editorial journal undertaken when resurrecting Binet's forgotten song cycle, which was subsequently published in 2018 by Classical Vocal Reprints.
Keywords: Archives & records; Education; French language; Manuscripts; Music; Musical performances; Online data bases; Piano; Spelling; Vocal music

(Re)Presenting Indigenous Activism in the Nation's Capital: Signifying Resistance across Time and Place through Music in Alanis Obomsawin's Trick or Treaty? (2014) - Hoefnagels, Anna (Contemporary Musical Expressions in Canada, 2020)

Music, Geography and the Greatest Rewards: A Geohistorical Analysis on the Prestigious Awards of Céline Dion - Iconic Artist - Jucu, Ioan-Sebastian (Review of Historical Geography and Toponomastics, 2020)
In the present academic research connecting geography and music,a real gap remains in the study of different issues associated with both music and geography and, particularly, to the recent music geographies. This paper advances a new geographical approach in music geography highlighting the relevance of time and space in music, in the artist‟s outstanding contribution to music and in their recognition from the local to the global. Particularly the study is focused on one of the most emblematic music artists of the world, analyzing through a spatio-temporal investigation the prestigious awards achieved by the singer Celine Dion, since this singer remains both a real music legend and an iconic artist gaining multiple awards and thoroughly appreciated and admired for her outstanding contribution to music and global popular culture. The research bases on such specific methods as internet research, visual methodologies, bibliographical analysis and geographic information systems (GIS). The latter is used to provide a professional map illustrating the spatio-temporal distribution of the multiple awards received by Dion the artist. The findings of the research highlight the highest scale of appreciation an artist can receive. The results of the study also suggest that the outstanding contribution of the greatest artists of the world, acknowledged by the highest national, international and global forums, provide significant information about their artistic involvement in the global popular culture. They have a strong relevance both in space and in time, thus labeling different cultural decades and distinct places and spaces throughout the world.

Monique Leyrac : notre grande dame de la chanson québécoise du XXe siècle - Laberge, Yves (Cap-aux-Diamants : la revue d'histoire du Québec, 2020)
Un article de la revue Cap-aux-Diamants, diffusée par la plateforme Érudit.

Céline, es-tu queer ? - Leblanc, Thomas (QuébeQueer. Le queer dans les productions littéraires, artistiques et médiatiques québécoises, 2020)
En plus d’offrir un portrait des productions culturelles queer au Québec tant francophones qu’anglophones, dont certaines autochtones, cet ouvrage s’attarde à révéler le caractère queer de celles qui ne le sont pas de facto. Il se présente comme un manuel de référence sur le sujet, avec des essais critiques – qui portent autant sur la littérature et le monde du spectacle que sur les arts médiatiques ou la presse gay – et des textes expérimentaux – fictions, dessins, récits autobiographiques. Plus de 27 œuvres de fiction publiées entre 1965 et 2017 y sont analysées sous différents aspects, avec des méthodologies diverses, mais toujours sous l’éclairage queer (un terme à la nature instable, paradoxale, que calque la forme éclatée de l’ouvrage). Du polyamour à l’inceste, en passant par le racisme, l’urbanité, le suicide, le non-désir d’enfant, l’alimentation ou les processus de production, le queer met en scène des personnages hétéros ou homosexuels, intersexués, cis, trans, travailleur·euse·s du sexe, gros et plusieurs autres… Cette juxtaposition d’états, de genres, de thèmes, de formes et de pratiques constitue l’une des forces de ce livre qui intéressera bien sûr un lectorat d’intellectuel·le·s et de personnes issues des communautés LGBTQIA2S+, mais pas seulement. Il deviendra, sans nul doute, une ressource indispensable pour l’enseignement de nouvelles perspectives dans le cadre des sciences humaines et sociales.

Venus On Venus: CKUT’s Women’s Collective Music Show Dishes on Feminist Radio - Leventhal, Anna; McInnis, Catherine; Wilson, Angela (Women in Radio: Unfiltered Voices from Canada, 2020)
Three volunteer hosts and programmers of a feminist music show at a campus-community radio station, Anna Leventhal, Catherine McInnis, and Angela Wilson, sat down in 2008 to chat about feminist radio. They discussed the concept of a feminist music show and the possibilities and limitations of female-only spaces; the “fem-con” concept that campus-community radio stations be mandated to play a certain amount of music by women, in the same way they are mandated by the CRTC to play Canadian content; the transformative social and political potential of community radio; and the inclusion of trans and gender-nonconforming voices on the show.

Ageing with Waves: The Im/material Worlds of Two Quebec Ondists - Madden, David (A Senior Moment: Cultural Mediations of Memory and Ageing, 2020)
Ageing and memory - two aspects of life everybody has to face eventually. The contributions to this volume explore the cultural mediations of these categories. Through a series of approaches focused on practices and acts of memory, narratives, reminiscence, representation and collective memory, they seek to better understand and critically reflect on how ageing is experienced in variegated ways across the lifespan. By covering a variety of phenomena, from biopics, music by the elderly, and artefacts, among other, they all contribute to further the understanding of memory as a cultural process always in the making - situated in particular contexts, and shaped by its material conditions of existence.

Imaginary Women, Imaginary Audience: Gender and Top 40 Radio in Montréal - Maki, Christine (Women in Radio: Unfiltered Voices from Canada, 2020)
Though they no longer call themselves Top 40, popular music radio stations remain present on the dial today, complete with loud, mostly male DJs, hoping to attract a mainly female audi ence. Using the talk on two Montréal music stations, which hire mainly male announcers who select music assumed to fit wom en’s tastes, Christine Maki examines the continuing perception that women’s voices aren’t low or authoritative enough and that emotional issues prevent them from presenting difficult news stories. Her conclusion: the overall medium remains relatively unchanged over the decades, despite massive evolution in the wider media landscape.

Tuning a Room: Designs for Hearing According to Nancy Tobin - Rewa, Natalie (Canadian Theatre Review, 2020)
In this review, I discuss the architectonics of sound composition according to sound artist and designer Nancy Tobin. This chapbook advocates for a comprehensively integrated presence of a sound artist in the processes of rehearsal and espouses a dramaturgy of hearing. Tobin’s distinction between hearing and listening gives forth onto a series of self-studies of her experience of spatial and temporal arrangements presented in the form of e-mails to mentees. Her appreciation for the acoustics of the performance space extends to the composition of sound to be heard (on occasion as boldly interventionist) and the technologies of broadcasting it: the choice and placement of speakers, as well as their interaction with the performers. Tobin argues for a definition of sound composition for performance as a complex collaboration with the production—curatorial in terms of the space of ephemerality. My review concurs with the efficacy of her approach by my recognition of the moments in productions that have remained as some of the most memorable of my theatregoing.
Keywords: Nancy Tobin; acoustic space; rehearsal processes; sonic/acoustic dramaturgy; sound artist; speaker specifications and broadcasting sound

Blue Oil, premier groupe punk féminin au Québec - Desfossés, Félix B. (Ici Radio-Canada, 2019)

Palmarès musicaux: où sont les femmes? - Vallet, Stéphanie (La Presse, 2019)

L'adaptation de chanson dans l'album ”Cœur vagabond” de Bïa. Une brise de Brésil - Abbrugiati, Perle (ATeM – Archiv für Textmusikforschung, 2019)
Perle Abbrugiati's article explores Coeur vagabond/Coraçao vagabundo, the fourth record by the French-Brazilian artist Bïa, released in 2006. The bilingual album comprises an equal number of Brazilian-Portuguese adaptations from French songs and French adaptations from Brazilian songs. The aim of the present article is to identify the strategies applied in the translation of songs. To this end, the article's author herself uses translation within the framework of a comparative approach, confronting Bïa's translations with her own literal translations (not suitable to be sung) of the original lyrics. The objective is not to trace 'mistranslations' but to point out in how many different and intricate ways a translation can be faithful while being creative, and in what way and to what degree the song translator may take the liberty of 're-semantisation'.
Keywords: Chanson; traduction

Une approche sensible du son - Bertin, Raymond (Jeu : revue de théâtre, 2019)
Article sur l'artiste sonore Nancy Tobin.

“Where You Are Accepted, You Blossom”: Toward Care Ethics in Jazz Historiography - Blais-Tremblay, Vanessa (Jazz & Culture, 2019)

“Portrait en Noir et Blanc”: Chico Buarque em francês por Bïa Krieger [“Portrait en Noir et Blanc”: Chico Buarque en français par Bïa Krieger] - Cassiano, Raissa Conde (Tradução em Revista, 2019)

L'improvisation jazz : une pratique fondamentale dans le processus de reconnaissance des musiciennes de Montréal - Champagne, Lysandre (Université du Québec à Montréal, 2019)
À partir des dimensions spatiale, temporelle et musicale, ce mémoire expose les modalités de reconnaissance des improvisatrices de jazz dans les jam-sessions de Montréal. En se référant au concept de Jeu chez Mead, l'autrice montre que l'authentification des musiciennes en situation d'improvisation est le produit de la communication mise en forme par ce type d'interaction. Toutefois, le contexte des jam-sessions montréalais maintient un «entre-soi» masculin défavorable à la reconnaissance des musiciennes comme improvisatrices distinctes dans ce jeu musical. Ainsi, l'improvisation dans ces événements de jazz participe à la reconduction des inégalités de genre.

Jouer les femmes : les concerts de musique contemporaine au Québec - Couture, Ariane (Recherches féministes, 2019)

Festivals de musique québécois : où sont les femmes ? - Croteau, Laurianne (Ici Radio-Canada, 2019)

Sexisme en musique : des trucs pour s’assurer une programmation paritaire et inclusive – Partie 1 - Daguzan Bernier, Myriam (Gazette des femmes, 2019)

Sexisme en musique : des trucs pour s’assurer une programmation paritaire et inclusive – Partie 2 - Daguzan Bernier, Myriam (Gazette des femmes, 2019)
Solutions constructives pour des rendez-vous musicaux plus vivants, diversifiés et… paritaires!

Monique Leyrac. Le roman d'une vie - Dompierre, François (Éditions La Presse, 2019)

We Appreciate Power: A Multimodal Critical Discourse Analysis of Grimes' Music Video Posted on YouTube - Enguídanos Gómez, Adrià (Université autonome de Barcelone, 2019)
The aim of this dissertation is to produce a multimodal critical discourse analysis of Grimes' video We Appreciate Power. This will serve to explore issues of ideology, identity and multilingualism in both the music video and the YouTube polylogues generated in the same web page. In this work I suggest that Grimes adopts a poststructuralist view that inherits Haraway's cyborg concept (1991) in this piece of multimedia. I claim that Grimes wanted to show the conflictive moral boundaries that the idea of the cyborg and trans-humanism casts upon Western civilization, such as the loss of free will but also the transgression of problematic dichotomies. The fact that the comment section of the video is available to use might signal that Grimes wanted to raise awareness about trans-humanism. By doing virtual ethnography research, examples of discussion about the relationship between the video and the studied polylogues will be examined regarding the notions of the cyborg and multilingualism.

Je donnerai de la joie. Entretiens avec Dina Bélanger - Gauthier, Jacques (Éditions Novalis, 2019)
Dina Bélanger (1897-1929) s’est donnée très jeune au Christ, ne voulant que lui plaire dans l’intimité de la prière. À vingt-quatre ans, elle renonce à une brillante carrière de pianiste pour entrer au couvent des Religieuses de Jésus-Marie à Québec. Elle expérimente l’union mystique avec la Trinité par le cœur eucharistique de Jésus. Béatifiée par Jean-Paul II en 1993, elle laisse à l’Église et au monde un héritage spirituel d’une richesse exceptionnelle, qui rappelle celui de Thérèse de l’Enfant-Jésus, qu’elle avait prise pour patronne, avec sainte Cécile. Dans le sillage de ses ouvrages sur Thérèse de Lisieux et Marie-Léonie Paradis, Jacques Gauthier nous offre un autre entretien chaleureux et instructif avec une «?amie de Dieu?» qui avait dit avant de mourir, à trente-deux ans?: «?Je donnerai de la joie.?» Ses questions pertinentes facilitent cet échange intime avec Dina qui, par l’intermédiaire de son autobiographie, témoigne d’une sainteté unique et inspirante.

Why Lhasa de Sela Matters - Goodman, Fred (University of Texas Press, 2019)

The “Manic Pixie Dream Girl of the Synth-Pop World” and Her “Baby Doll Lisp”: Grimes and the Disabling Logics of the Feminization and Infantilization of Lisping - Holmes, Jessica A. (Journal of Popular Music Studies, 2019)
Audible in speech and song, electro-pop singer Grimes’s so-called “baby doll” lisp generates endless buzz online, ranging from light-hearted adoration, to infantilization, to sexual fetish and even to ableist, misogynist anti-fandom. This article uses the reception of her lisp to build an intersectional theory of lisping across its medical and socio-cultural constructions, bridging work in disability studies, dysfluency studies, voice studies, and popular music studies in the process. I situate the slippage between adoring, infantilizing, fetishistic, and violent characterizations of Grimes’s lisp as reflective of the infantilization of “communicative disorders” in speech language pathology, and the dysfunction associated with feminine coded-speech patterns (e.g. vocal fry and up talk) in the popular imaginary. Lisping is profitably understood as an audible form of “liminal” difference relative to visible physical disabilities (St. Pierre), and to certain ableist, gendered, and racialized conceptions of normative vocality. Ultimately, in the English-speaking world, the lisp is symbolically-coded feminine while exceeding the norms of female vocality, thereby giving rise to a polarizing set of associations that work against female authority and, by extension in Grimes’s case, female musical authorship. Grimes’s reception thus offers a valuable case study for interrogating how misogynist fantasies regarding femininity are thought localized in the female voice, and the symbolic ties between disability and femininity.

Musical Geographies and Iconic Music Legends: Mapping Céline Dion's Outstanding Contribution to Music and Global Popular Music Culture - Jucu, Ioan-Sebastian (Territorial Identity and Development, 2019)
Between music geography and iconic music legends, a strong connection has been established in terms of spatial and temporal analysis of popular music and the representation of national identities in the contemporary global cultures of popular music. The existing literature unveils a gap in the analysis of music geography and famous musicians, real global music icons identified with particular cultures. This paper argues that such music legends must be geographically studied to unveil their outstanding contribution to the world music cultures. Against such a background, a geographical approach that takes Canadian singer Céline Dion as a case studyis developed. The research aims to analyse Dion’s outstandingcontribution to global music culture in both spatial and temporal terms. Based on the music industry emergence, the paper focuses on how and why Céline Dion appeared in global music culture and examines her outstanding contribution with specific referenceto music cartographies and statistical research.National identity and related cultural issues beyond the music, lyrics, and performances are also addressed.The empirically led study is based on a multi-method approach and makes use of statistical data analysis, GIS methods, biographicalinquiry, the analysis of lyrics and visual methodologies,all suggesting that Dion’s contribution has greatly influenced the global popular music culture of the last few decades.Although the topics in question cannot be fully discussed within the limits of this paper, it highlights the importance of these issues and calls for further in-depth research to provide a new critical understanding of the intimate connections between popular music, legendary music icons and the recent perspectives in music geographies

Ton métier, le mien, le Québec. Fragments de correspondance amoureuse et politique 1962-1993 - Julien, Pauline; Godin, Gérald (Leméac Éditeur, 2019)
Dix ans après la parution de La renarde et le mal peigné,quatre cents nouvelles lettres échangées entre Gérald Godin (1938-1994) et Pauline Julien (1929-1998) ont été découvertes dans leurs fonds d’archives respectifs. Soixante-dix d’entre elles ont été choisies par Emmanuelle Germain et Jonathan Livernois, dans cette édition qui vient compléter le portrait forgé en 2009. On y retrouvera les débuts de la relation entre le journaliste et la chanteuse, les longues tournées en Europe de Pauline Julien, la maladie de Godin, puis celle, en filigrane, de Julien. De nouveaux aspects apparaîtront également : l’érotisme de plusieurs de leurs échanges ; les rapports d’amitié ; les aléas d’une vie familiale où un jeune homme de vingt-cinq ans doit s’occuper de deux adolescents, alors que Julien doit concilier sa vie professionnelle et sa vie de mère ; l’épuisement des dernières années, tandis que les tournées européennes sont de plus en plus difficiles pour Julien. Les lettres réunies ici permettront également aux lectrices et aux lecteurs de revivre de grands moments de l’histoire québécoise, vue à la hauteur de ses acteurs : le « Vive le Québec libre ! » lancé par Pauline Julien à Niamey, en 1969, interrompant le ministre fédéral Gérard Pelletier ; la crise d’Octobre et l’emprisonnement sur lequel on ne reviendra guère ; la campagne électorale de 1976, l’enthousiasme et la victoire, inattendue ; l’engagement du député puis ministre Gérald Godin. Ce n’est donc pas un hasard si ce petit livre est sous-titré « Fragments de correspondance amoureuse et politique ». La suture des deux univers, de l’intime et du public, de l’amour et du politique, y est plus claire que jamais.

La mélancolie dans la chanson québécoise contemporaine : Tu m'intimides de Mara Tremblay, La forêt des mal-aimés de Pierre Lapointe, À Paradis City de Jean Leloup - Laliberté St-Pierre, Audrey (Université Laval, 2019)
La chanson québécoise actuelle paraît réconcilier la chanson dite «à texte» et la chanson populaire, comme ce fut le cas pour la chanson engagée des années 1970. Si le thème de l’engagement soutenait plusieurs œuvres chansonnières de cette décennie, celui de la mélancolie semble pouvoir définir une certaine tendance actuelle. Ce mémoire s’intéresse au thème de la mélancolie dans la chanson québécoise contemporaine et plus précisément dans les albums Tu m’intimides de Mara Tremblay, La forêt des mal-aimés de Pierre Lapointe et À Paradis City de Jean Leloup. À la fois auteurs, compositeurs et interprètes, ces trois artistes s’inscrivent dans le champ populaire de la chanson québécoise en créant des œuvres où le texte et la musique mettent la mélancolie en valeur. Dans cette étude, la mélancolie est étudiée en fonction de trois aspects, soit l’être mélancolique, la temporalité mélancolique et l’espace mélancolique. C’est à travers l’exploration de ces trois aspects que sont analysées les chansons du corpus, surtout à partir des textes, mais en considérant aussi certains éléments musicaux.

« Cohérence d’une œuvre métissée » : extrait de thèse de doctorat (2007) - Makdissi-Warren, Katia (Circuit, 2019)

Katia Makdissi-Warren : étapes et œuvres marquantes - Pascal, Noémie (Circuit, 2019)

L’univers de Katia Makdissi-Warren (un diagramme) - Pascal, Noémie (Circuit, 2019)

"A Jewish Maestra and a Lady too": Reflections on Femininity in the Career of Ethel Stark - Rachwal, Maria N. (Canadian Jewish Studies, 2019)
Ethel Stark (1910-2012) was one of the most important conductors and concert violinists in Canada in the Twentieth century. This article highlights how an Austro-Canadian Jewish woman who lived outside the constraints of conventional domesticity, both navigated through and defied the ideals of the “Cult of True Womanhood” and spearheads a movement of feminism in music. I argue that Stark’s exposure to Jewish cultural traditions of social justice and womanhood in her childhood formed a critical dimension of her feminist activism later in her life, and in particular in the founding of The Montreal Women’s Symphony Orchestra (1940).

The Expression of the Tragic in the Chamber Cantata Dați-Mi Lampa Lui Aladin [Give Me Aladdin's Lamp] by Dora Cojocaru - Seraz, Roxana Maria (Musicology Papers, 2019)
Dora Cojocaru is recognized as an outstanding representative of the Cluj school of composition, but also as a strong voice in Romanian musicology. While her musicological output includes books, studies, articles, radio programs, conference papers, master classes and scientific communication sessions, her most important contribution remains the book entitled Creația lui Gyӧrgy Ligeti în contextul stilistic al secolului XX [Gyӧrgy Ligeti's Work in the Stylistic Context of the Twentieth Century], which was the first book about Ligeti that appeared in the Romanian musicological landscape. Dora Cojocaru’s compositional portrait can be drawn by following the language characteristics and compositional devices used in the chamber cantata Dați-mi lampa lui Aladin [Give Me Aladdin's Lamp]. The composer’s work is characterised by a propensity for chamber music. The composer confesses that it is also a consequence of the fact that this genre comes with a plethora of expressive possibilities. In terms of the musical language used by the composer, its first characteristic is the concern to avoid repetition in expression and the variation of an already used musical material. This is strikingly evident in the chamber cantata Dați-mi lampa lui Aladin [Give Me Aladdin's Lamp]. Another peculiarity is the construction based on a developmental discourse, while a third characteristic is the frequent construction of the discourse based on an economy of means and on a musical material consisting of only a few notes. In the case of this cantata, it is essential to note the historical context, which is closely linked to the symbolic title suggesting the composer’s desperate desire to bring her brother back to life, although she is aware that this is only possible by magic. The composer’s choice of lyrics is derived from the fact that Trakl’s and Rilke’s texts allude to the theme of death, which is one of the frequent themes of late Expressionism, and are therefore pervaded by a tragic note, in tune with the composer’s musical intentions. If we follow the text-music relationship, we notice some extremely significant moments, in which music creates sonic images that are suggestive of the message of the text.

Serving Each Other: Sharing Economies and Affective Labour in Montréal's Kiki Scene - Tailor, Jesse (Université Carleton, 2019)
Against a tense socio-political backdrop of white supremacy, intensifying pressures of neoliberal fiscal austerity, and queer necropolitics, this thesis addresses performance-based activist forms of place-making for urban-based queer, trans, and gender nonconforming communities of colour. Using participant observation and qualitative interviews with pioneering members of Montréal’s Kiki scene and Ottawa’s emerging Waacking community and interpreting my findings through the theoretical lens of queer of colour theory, critical whiteness studies, queer Latinx performance studies and Chicana feminism, I argue that Kiki subculture, which is maintained by pedagogical processes of ‘each one, teach one’, is instrumental in facilitating i) life-affirming queer kinship bonds, (ii) alternative ways to simultaneously embody and celebrate nonnormative gender expression with Black, Asian, and Latinx identity, iii) non-capitalist economies of sharing, and iv) hopeful strategies of everyday community activism and resilience to appropriative processes during economic insecurity and necropolitical turmoil.

Reality Sounding: Annesley Black’s not thinking about the elephants - Tan, Anthony (Circuit, 2019)
This paper presents an analysis of Annesley Black’s not thinking about the elephants (2018), for saxophone quartet and live electronics. Written for Montreal’s Quasar Saxophone Quartet, this work explores concepts of suppression and emergence through traditional musical dimensions such as melody, counterpoint, and form, but also through contemporary musical dimensions such as psychoacoustics (difference tones), theatrical elements, and live electronics. Black’s practice engages critically with the compositional process itself by formulating dialectic relationships between material and compositional strategies (both intuitive and systematic). This work encourages the listener to engage in a multidimensional listening experience where conceptual extremes become a catalyst for the building of narrative and tension.

Mon Starmania. Par la première serveuse automate - Thibeault, Fabienne (Éditions Flammarion Québec, 2019)
Né il y a 40 ans de la collaboration entre Michel Berger et Luc Plamondon, le phénomène Starmania est probablement le plus grand succès musical franco-québécois. Outre les Français Daniel Balavoine et France Gall, la distribution originale réunissait quatre immenses interprètes d’ici : Claude Dubois, Diane Dufresne, Fabienne Thibeault et Nanette Workman. La carrière de chacun a été marquée par cette aventure qui a aussi laissé sa trace indélébile dans notre imaginaire collectif. Fabienne Thibeault, qui avait 26 ans à l’époque, nous fait partager cette épopée dans l’intimité du couple formé par Michel Berger et France Gall chez qui elle a vécu à Paris. Pour compléter son récit, elle se remémore des anecdotes personnelles et donne la parole aux artisans moins connus (choristes, doublures, musiciens) de cette réalisation magistrale qui surprend toujours par son actualité.

Empowering Diversity: A Study Connecting Women in Leadership to Company Performance in the Canadian Music Industry - Women In Music Canada (Women In Music Canada, 2019)
Gender diversity in the music industry is low, both in Canada and internationally. The lack of diversity may represent a competitive disadvantage, as diversity is known to promote innovation and broad thinking, which is precisely what the music industry needs as it undergoes rapid change. This study, performed by Women in Music Canada in collaboration with PwC, assesses the impact of gender diversity of leadership within the Canadian music industry and the impact on company performance.

A Landscape of Memories through the Music of Hope Lee - Feliz, Juro Kim (Nomadic Sound Worlds, 2018)
Produced by Juro Kim Feliz under the Canadian Music Centre Library Residency, Nomadic Sound Worlds is a four-part blog/podcast series exploring Canadian contemporary music through the lens of present-day global migration. A collection of essays named Letters of Transit: Reflections on Exile, Identity, Language, and Loss (ed. André Aciman, 1999) informs and inspires this project, with trajectories branching out from related themes including mobility, displacement, loss, reconciliation of polarized truths, and invention of selves. In this regard, the series will feature selected immigrant Canadian composers whose musical worlds collide with various personal stories of immigration.

Ana Sokolović. Robots musicaux et kolo serbe - Harman, Brian (La création musicale au Québec, 2018)

Their Own Agenda: The History, Development, and Culture of Women's Orchestras Outside the United States - Alger, Bonnie Eve (Université du Maryland, 2018)
Women have been active as performers of instrumental music since the Medieval period, and yet their contributions are often overlooked. This dissertation examines the history of women’s orchestras outside the United States, and explores their development, as well as reasons for existing. Several factors regarding their development are taken into consideration, including time period, country, and culture in which the ensemble is present. The birth of the women’s orchestra is traced from the ospedali of the 18th century Venice to today. All-female ensembles from England, Canada, Cuba, and Afghanistan are profiled, as well as the Women’s Orchestra in Auschwitz. Two modern-day women’s orchestras – the Allegra Chamber Orchestra in Vancouver, British Columbia, and my recital orchestra at the University of Maryland – were surveyed in an attempt to learn more about the culture of women’s orchestras. This paper seeks to answer the questions “What is the culture of women's orchestras today, and should they continue to exist?”

Jazz, gender, historiography: a case study of the "Golden Age" of jazz in Montreal (1925-1955) - Blais-Tremblay, Vanessa (Université McGill, 2018)
This dissertation maps the interaction between jazz, identity, modernity and nation during the so-called "golden age" of jazz in Montreal (1925-1955). Drawing on the fields of musicology, women's studies (black feminist theory and feminist research methods in particular), critical dance studies, and cultural studies, this project provides a critical re-writing of the history of Montreal jazz, one which acknowledges various roles that racialized and ethnicized women played in the shaping of modern identities, pleasures and sounds in Quebec. Montreal's particular status as a "showtown" makes it a rich laboratory to study the collaborative creative relationships between jazz music and dance on the black variety stage in the first half of the twentieth century. I also map the specific parameters that articulate the discursive relationship between jazz and vice, in particular as these relate to the gendered and racialized embodiment of morality in interwar Quebec. Finally, this dissertation produces the first extensive biographical accounts and critical listening of several prominent Montreal-based female jazz artists, including pianists Vera Guilaroff and Ilene Bourne, all-girl groups such as The Spencer Sisters and the Montreal Melody Girls Orchestra, black women performers such as Tina Baines Brereton, Bernice Jordan Whims, Marie-Claire Germain, Mary Brown, Natalie Ramirez, as well as piano teacher Daisy Peterson Sweeney and dance teachers Ethel Bruneau and Olga Spencer Foderingham.

Entrevista com a cantora e compositora Bïa Krieger [Entretien avec l'autrice-compositrice-interprète Bïa Krieger] - Cassiano, Raissa (Tradterm, 2018)
Radicada há mais de vinte anos na França e no Canadá, Bïa Krieger conquistou um público cativo nesses países, onde recebeu prêmios importantes, como o Grand Prix de l’Académie Charles Cros (França), Prix de l’Adisq (Canadá) e Félix du Meilleur Album Musiques du Monde (Canadá). Esta entrevista contempla o seu trabalho como versionista, com enfoque nas versões em francês para canções de Chico Buarque.

Aller à la quête de l’œuvre : Véronique Lacroix et les 30 ans de l’ECM+ - Champagne, Éric (Circuit : musiques contemporaines, 2018)

Pauline Julien, intime et politique - Ferland, Pascale (Office national du film du Canada, 2018)
Suivant un minutieux choix d'extraits d'entrevues, de spectacles et de photos, puisés à même un colossal et riche fonds d'archives, Pauline Julien, intime et politique nous entraîne dans le sillage de cette femme résolument libre et engagée, figure emblématique de la chanson et d'une époque charnière de l'histoire du Québec.

La renarde et le mal peigné - Julien, Pauline; Godin, Gérald (Leméac Éditeur, 2018)
Dans ces « fragments de correspondance amoureuse », on découvre Pauline Julien et Gérald Godin comme jamais on ne les avait vus, comme jamais plus on ne les verra. Lui, jeune loup puis loup mature, passionné, dévoué à la cause et amoureux. Elle, mère, chanteuse, absente souvent, incertaine et amoureuse. Elle que le doute assaille, toujours. Lui, de plus en plus sûr. C’est un magnifique tango qui se déroule sous nos yeux, on s’attire et se repousse dans le même paragraphe. Et c’est beau. Que c’est beau! La poésie qui les habite en permanence est suffisante pour rendre n’importe quel esprit jaloux, suffisante pour affadir n’importe quel amour. Pascale Galipeau, fille de Pauline Julien, a dû braver objections et réprimandes pour publier ces lettres. On ne peut que la remercier à genoux et lui baiser les mains de ne pas avoir cédé.

Les épreuves du travail musical : la persévérance des musiciens et musiciennes au Québec - Lavoie-Ricard, Olivier (Université de Montréal, 2018)

A Rich Musical Legacy from Québec: Baroque Motets of the Ursuline and Hôtel-Dieu Monasteries of New France - MacIsaac, Elizabeth Kathleen Norah (Université de Washington, 2018)
Carefully preserved in the archives of the Ursuline and Hôtel-Dieu Monasteries of Quebec are several manuscripts containing Canada’s first sacred works for female voices. The manuscripts contain dozens of intricate motets composed in the French Baroque style, a repository of music which has not been sung for hundreds of years. These motets form a neglected part of Canada’s musical heritage which is waiting to be unearthed and explored. Ursuline and Augustinian nuns arrived to the French territories of the New World to educate and evangelize young women. Singing formed a core element of their teaching and worship. For over one hundred years (1639-1760), church music provided a backbone to Canada’s vibrant musical culture. When the French territories were lost to Britain and Spain, musical culture shifted radically and the sacred French music simply faded into obscurity. An overview of the sweeping events of the French Baroque era includes discussion of France’s social conditions, the political and religious climate, the flowering of the arts and the exploration of the New World. In France, the seventeenth and eighteenth centuries were a time of great strife which heralded the massive social changes to come in the nineteenth century. France’s struggles directly impacted the colony of New France, including that of its religious institutions and music. This study traces the musical activities in the Ursuline community of New France as the nuns lived their mission on the frontier, teaching Aboriginal and colonial girls. The evolution of female emancipation stemming from religious evangelism is considered. Examination of a trove of 160 motets located in the female monasteries of Québec City reveals the high caliber of music practiced by the nuns. No interpretive editions for performance purposes exist. Newly transcribed works have been generated from the manuscripts, with period performance guidance for appropriate ornamentation and ensemble requirements. An in-depth discussion of New France Baroque vocal and choral musical styles is provided, with reference to historical records of how it was taught, as described in contemporaneous music treatises and many original documents specific to these religious female communities.

L’intermédialité autochtone dans l’œuvre de Natasha Kanapé Fontaine : mémoire, oralité et territoire - Morin-Martel, Florence (Université de Montréal, 2018)
Ce mémoire explore la notion d’intermédialité autochtone au sein de l’oeuvre de Natasha Kanapé Fontaine. Les imbrications entre les médias seront notre point d’appui pour penser les questions de l’esthétique dans l’art autochtone actuel. Par le biais de la représentation d’un média dans un autre, nous aborderons ainsi la réactualisation des traditions orales telles que le conte, le mythe, le chant et le tambour au sein des productions de cette artiste. Notre parcours observera les structures intermédiales qui mettent en exergue la mémoire ainsi que les connaissances ancestrales. Les croisements entre l’identité et le territoire seront également discutés dans l’optique des représentations intermédiales. Ainsi, les phénomènes d’affirmation et de réactualisation des savoirs se déploient par l’utilisation de divers médias. De ce fait, la résistance environnementale et culturelle ainsi que la néo-oralité sous-tendent l’oeuvre de l’artiste et s’expriment à travers les territoires imaginaires et médiatiques.

Isabelle Panneton. De la rigueur à la liberté de création - Nattiez, Jean-Jacques (La création musicale au Québec, 2018)

Lhasa de Sela et la traversée des espaces - Proulx, Robert (Archiv für Textmusikforschung, 2018)
The singer-songwriter Lhasa de Sela (1972-2010) launched her career and produced her three records in Montreal where she arrived in 1991. Not only did she change the face of migrant song in Quebec, but she also enjoyed international success, embarking on long world tours and selling more than a million records. This analysis will focus on the songs from her second album, The Living Road, and will show that Lhasa de Sela transcended linguistic and artistic frontiers by crossing the geographical border when she made Montreal her home and creative hub.

Guerre ou pas, j'irai danser la veille du jour de l'an. Chroniques d'une danseuse invétérée - Roquigny, Peggy; Saint-Jacques, Denis; Des Rivières, Marie-Josée (Les médias parlent et chantent. Chroniques de la vie culturelle à Montréal durant la crise et la guerre, 2018)

L’apport de Maryvonne Kendergi à la SMCQ - Bail, Louise (Circuit : musiques contemporaines, 2017)
To measure Maryvonne Kendergi’s contributions to the smcq, it is necessary to revisit her career in Quebec, which was based on the solid academic and professional training she received at Parisian institutions from 1929 to 1952. Thereafter, in Montreal, she was hired by Radio-Canada for her exceptional voice, and in September 1956, she embarked on a brilliant radio career as a promoter of contemporary music. Kendergi gradually introduced the listening public to the arcana of the Montreal avant-garde. In this endeavour she was encouraged by Stockhausen’s arrival in Montreal in 1958, by composers’ efforts in organizing International Music Week in 1961, by the foundation of the smcq in 1966, and by the influence of the latter organization, particularly in its collaboration with the Université de Montréal in establishing the Musialogues in 1969. The role of Kendergi’s exceptional skills in broadening the influence of the smcq is explored in this article.
Keywords: Maryvonne Kendergi; Musialogues; Société de musique contemporaine du Québec (smcq); animatrice; host; music journalist; musicographe de radio

D’exil et d’américanitude : un entretien avec Linda Bouchard - Bertrand, Simon (Circuit : musiques contemporaines, 2017)
Quebec composer Linda Bouchard (born 1957) is an extremely prolific composer, particularly active on the new music scene in the u.s. where she has lived for lengthy periods since 1989. She has composed a rich and diverse catalogue of works, ranging from orchestral music to more intimist instrumentations, and also using multimedia or improvisation. In this interview, the composer reflects on the question of exile and identity in light of her own experience, thus reliving her own artistic path while also addressing some still burning questions about the place of music creators in the global culture.
Keywords: composer; compositrice; exil; exile; identity; identité; parcours; society; société; trajectory

Femmes et jazz dans le Québec de l’entre-deux-guerres : entre le récit historique, les archives et le passé - Blais-Tremblay, Vanessa (Les Cahiers de la Société québécoise de recherche en musique, 2017)
Cet article porte sur les rôles que les femmes ont joué dans le développement d’une scène jazz à Montréal. Les archives témoignent de l’importance des pianistes Vera Guilaroff et Ilene Bourne, de l’enseignante de piano Daisy Peterson Sweeney, des enseignantes de danse Olga Spencer Foderingham et Ethel Bruneau, ainsi que des danseuses de variétés dans le développement de la plus grande scène jazz du Canada au cours de la première moitié du xxe siècle. Cet article contextualise la présence des femmes dans ces espaces performantiels précis (le piano, l’enseignement, la danse) et explore les processus historiographiques liés à leur exclusion des récits historiques.

Claudette Dion: La soeur de... - Girard, Jean-Yves (Éditions La Presse, 2017)
Ce livre donne la parole à une femme authentique, sereine, pétillante et attachante qui sait son privilège de s'appeler Dion, tout en portant fièrement son prénom. Avec humour et tendresse, elle révèle ce que c'est que d'être la sœur de... Entre une mère très médiatisée et une petite sœur devenue mégastar, au milieu de treize frères et sœurs, Claudette a su trouver sa place au soleil. Un regard unique. Des propos inédits.
Keywords: Biography & Autobiography / Entertainment & Performing Arts; Biography & Autobiography / General; Biography & Autobiography / Personal Memoirs; Biography & Autobiography / Women

Buena vida - K, Florence (2017)
« Il y a de ces moments où l'on peut avoir l'impression de patauger dans une boue solide, presque opaque, à travers laquelle la lumière peine à passer. Et pourtant, lorsqu'on s'y attarde un peu, combien de fois tirons-nous nos initiatives les plus courageuses, nos créations les plus belles, nos décisions les plus sages au moment où nous sommes nous-mêmes couverts de boue, lorsque nous nous retrouvons dans la merde jusqu'au cou ? » Florence K a vécu une enfance de saltimbanque. Elle baigne dans la musique et les tournées. Dans Buena vida, elle livre un récit rempli d'humanité, de musique, de voyages, et dévoile une partie de son existence qu'elle surnomme « l'abysse ». Sa vingtaine a été parsemée de grandes joies, entre le bonheur de la maternité et celui d'avoir réussi à faire de la musique son gagne-pain. Mais Florence est aussi passée par un trou noir qui a bien failli l'engloutir et duquel elle est sortie encore plus amoureuse de la vie. C'est en toute transparence qu'elle partage sa descente aux enfers et sa renaissance, car « la vie, c'est tout ce qu'on a ».

Cool Control, Occam, and Océan: The Radigue and Bozzini Game - Majeau-Bettez, Emanuelle (Les Cahiers de la Société québécoise de recherche en musique, 2017)
Cet article analyse la nouvelle collaboration entre la compositrice et pionnière de musique électronique, Éliane Radigue, et le Quatuor Bozzini. Débutant vers la fin des années 1960, la carrière d’Éliane Radigue se caractérise par de très longues oeuvres de musique électronique qui semblent de prime abord ne pas changer, et dans lesquelles les micro-oscillations naturelles entre les hauteurs remplacent la rythmique traditionnelle. Depuis 2001, Radigue ne travaille plus qu’avec des instrumentistes et utilise un « processus de composition intuitif » semblable à la « transmission orale de musiques traditionnelles anciennes » (Sonami 2017). Alors que les quelques intellectuels qui ont fait montre d’intérêt envers la musique de Radigue ont concentré leur attention sur l’aspect oral de ses compositions, cet article cherche ici à amener l’analyse au-delà des paramètres formels « non-écrits » de sa musique afin d’explorer comment la sonorité d’une pièce de Radigue génère de nouvelles manières de concevoir la performance et la composition. Les notes d’observation de l’auteure, la correspondance entre l’auteure, la compositrice et le quatuor, et les enregistrements des rencontres entre les Bozzini et Radigue seront utilisés pour retracer les moments de grande réaction émotionnelle causés par la sonorité très particulière que demande la musique de Radigue. Ces réactions affectives du côté de Radigue et du quatuor révèlent des points de tension entre différentes conceptions de la création collective, et réorientent complètement ce que cela signifie que de posséder, transmettre, interpréter et composer de la musique. Des spectrogrammes et des enregistrements des tentatives entreprises par les Bozzini seront utilisés dans l’étude de ces points de tension, et démontreront qu’afin de pouvoir jouer avec succès une pièce instrumentale de Radigue, les Bozzini doivent reproduire chaque élément des pièces électroniques de la compositrice; le quatuor à cordes doit se « transformer » en un étrange instrument.

Björk Digital : escale à Montréal - Marcotte, Nicolas-Alexandre (Circuit : musiques contemporaines, 2017)
An article from Circuit, on Érudit.

L'âme en tannage de Natasha Kanapé Fontaine : Souveraineté orale, territoriale et mémorielle - Marcoux, Gabrielle (Canadian Review of Comparative Literature / Revue Canadienne de Littérature Comparée, 2017)

A performer's perspective on three works for pianist and moving images : analysis with performance and practice strategies for Michel van der Aa's 'Transit', Nicole Lizée's 'Hitchcock Études', and 'Surface Tension' by Eve Egoyan and David Rokeby - Morano, Christopher (Université de Colombie-Britannique, 2017)
Interest in audio-visual works of art that are performed by a live pianist while integrating projected moving visual images has waxed and waned over a period of almost 300 years. The past twenty years or so has seen a re-emergence of this genre of classical music composition which places extra demands on the pianist performing these works. This dissertation explores the history of this genre, proposes a framework for analysis of these pieces, and examines from both analytical and performance perspectives three contrasting works for this medium: Michel van der Aa’s 'Transit', Nicole Lizée’s 'Hitchcock Études', and 'Surface Tension' by Eve Egoyan and David Rokeby. This research was

Partition pour femmes et orchestre. Ethel Stark et la Symphonie féminine de Montréal - Rachwal, Maria Noriega (Éditions du remue-ménage, 2017)
En 1940, deux femmes élégantes prennent le thé dans le lobby du Ritz-Carlton. Ne vous fiez pas aux apparences: leur rencontre annonce un grand chambardement dans l’univers de la musique classique. La mécène Madge Bowen et la violoniste Ethel Stark fondent à Montréal ce qui deviendra le premier orchestre symphonique canadien composé uniquement de femmes. […]

Louise Beaudet. De Lotbinière à Broadway - Saint-Pierre, Marjolaine (Éditions du Septentrion, 2017)

Le son au théâtre et en danse contemporaine : les principes conceptuels récurrents de ma pratique - Tobin, Nancy (Université du Québec à Montréal, 2017)
Ce mémoire-création porte sur la conception sonore pour le théâtre et la danse contemporaine. Il vise à fournir des connaissances qui puissent faciliter l'intégration du son au sein d'une création scénique. La recherche dont il est question ici se concentre uniquement sur les aspects conceptuels et non techniques, toutes deux intrinsèques au processus de création du son. Me basant sur mon expérience de concepteure sonore, plus précisément à partir de l'étude de mes notes de chantier de création entre 1999 et 2014, je dégage dix principes récurrents qui indiquent des conditions optimales pour concevoir le son. Ce mémoire-création est l'analyse d'une approche personnelle et le processus méthodologique a été autopoïétique et heuristique. L'étude se présente en trois sections. La première s'intéresse aux récits des processus de création où chaque principe émerge à partir de l'expérience qui est racontée. Dans la deuxième section, les principes s'explicitent davantage au travers l'étude de textes sur la conception du son. Un corpus d'auteurs, surtout des praticiens de la création sonore, est déterminé pour cette partie. Un livret compose la troisième section. Il incarne la partie « création » de ce mémoire. Il s'agit encore de préciser les principes, mais cette fois au travers de dix lettres fictives, destinées à des étudiants-es. Chaque lettre, dont le sujet est un problème rencontré en cours de processus de création, vise à expliquer un principe dans un contexte concret. Le titre du livret est La conception sonore selon Nancy Tobin 01. Mon nom apparaît dans le titre pour signifier qu'il est surtout question de mon approche personnelle. La mention des chiffres « 01 » indique que le livret démarre une série où d'autres personnes conceptrices sont invitées à écrire sur leur propre expérience. Peu de textes sur la conception sonore - sur l'expérience concrète du faire - existent. Ce mémoire-création vise à combler en partie cette lacune et à inviter d'autres créateurs à écrire sur leur pratique. L'expression par le sonore est riche et diversifiée. Plus les pratiques seront partagées et diffusées, plus il sera possible de multiplier les possibles de l'espace de l'écoute.

Bilan et perspectives sur la situation des compositrices au Québec : vers un décloisonnement des identités - Tremblay, Vicky (Les Cahiers de la Société québécoise de recherche en musique, 2017)
In the field of composition in Quebec, women composers are still less numerous than men composers. While the profession of composer has difficulty being recognized in Quebec society, women composers are twice as marginalized. Many of give evidence to the challenges they face when it comes to integrating into the musical community, and several musicologists have tried to better understand—and eventually solve—the problems specific to women in the field of composition.

Animating the Object: Marcelle Deschênes and acousmatic education in Quebec - Valiquet, Patrick (Organised Sound, 2017)
This article examines the early reception of Pierre Schaeffer’s theoretical work in Quebec through the teaching of Marcelle Deschênes, principal author of the first electroacoustic theory and ear training curricula at both Université Laval and Université de Montréal. An account of Deschênes’s educational career is provided, along with remarks on the contents of her early courses in Morpho-typology and her listening workshops for children, using newly excavated primary material from her private archives. While existing scholarship presumes that Schaefferian thinking arrived in Quebec with the ‘orthodox’ acousmatic approach of Francis Dhomont, this article asserts that a pluralist and multidisciplinary interpretation of Schaeffer’s work can be discerned which pre-dated Dhomont’s teaching and has had an equally lasting impact overall. A methodological argument is also made for including education and other forms of ‘reproductive labour’ in the history of electroacoustic music.

Nicole Lizée : adepte de la hantologie - Van Vliet, Kiersten (La Scena Musicale, 2017)

Where Is She? Finding the Women in Electronic Music Culture - Abtan, Freida (Contemporary Music Review, 2016)
The author discusses the visibility and participation of women in electronic music culture. She argues that most electronic music social networks privilege male inclusion and success, and that skill-sharing is an important strategy to encourage women in the field. To seed this discussion, the author examines her own history with reflections on the gender dynamics within electronic music communities outside the academy, and the role that social and technical currencies play within them. She also discusses Ladies club, a music distribution project that led to several solo female electronic musicians taking the stage and organising events in Montreal during 2007.
Keywords: Culture; Electronic Music; Feminism; Gender; Skills-Sharing

Creative layers and continuities: A case study of Nicole Lizée and the Kronos Quartet - Bayley, Amanda; Lizée, Nicole (Musicae Scientiae, 2016)
This study examines the creative layers and continuities evident within the composition and rehearsal processes of Nicole Lizée’s Golden Age of the Radiophonic Workshop (Fibre-Optic Flowers), written for the Kronos Quartet in 2012. Lizée’s compositional approach to the historic and the new, and the mechanical and the human, are interpreted through Simon Emmerson’s three themes of combination, transformation, and control, and his three “impulses within composition” that combine live and acousmatic soundworlds – integration, antithesis, and co-existence. These concepts also help to articulate the way the players engage with the physical, psychological, and expressive demands of the piece. Discussions arising from the Kronos Quartet rehearsing the piece with the composer reveal how extensions are made to the performers’ mind and body experiences when they are required both to initiate and integrate sounds emanating from unfamiliar, analogue machines into their acoustic, yet amplified soundworld. Creative layers and continuities are seen to evolve from compositional experimentation and from composer–performer and co-performer dialogues in rehearsal in the BBC Maida Vale studio prior to the world premiere at a BBC Prom concert on 24 July 2012.
Keywords: Delia Derbyshire; Kronos Quartet; Radiophonic Workshop; composition; creativity; electronic sounds; interaction; notation; rehearsal; string quartet

Le Club musical de Québec : 125 ans - Bernier, Emmanuel (Cap-aux-Diamants, 2016)

Éva Gauthier. La voix de l’audace - Cazelais, Normand (Fides, 2016)

The Songs of Violet Archer: Tracing the Evolution of One of Canada's Most Prominent Composers - Dauphinais, Paul (Université de Boston, 2016)
In this study, four sets of songs composed by Violet Archer are examined, all of which were written at different points in her career. Archer studied with Paul Hindemith in 1948 – 49, and his teachings had a tremendous impact on the young composer. The first set of songs to be analyzed, Moon Songs, was written before her time with Hindemith, and will provide a baseline from which her later, post-Hindemith, works can be compared. Following her studies with Hindemith, Archer wrote three songs, “Cradle Song,” “April Weather,” and “First Snow,” all of which show evidence of Hindemith’s influence. Her later, more mature works, Northern Landscape and Caleidoscopio Quatro, demonstrate a refined compositional technique; one in which Archer has created her own style, while maintaining aspects of the approach taught by Hindemith at Yale. This study will elaborate on the aspects of Archer’s music that evolved throughout her compositional career.
Keywords: Archer; Communication and the arts; Hindemith; Music analysis; Paul; Social sciences; Violet

Paroles inuites : création et transmission dans la chanson du Nunavik - Duvicq, Nelly (Recherches amérindiennes au Québec, 2016)
Among the forms of oral history, the song, within the Inuit culture, was general practice and quite versatile. Inheriting this tradition, the contemporary Inuit song has risen in popularity starting in the 1970’s and has not diminished since. Within the literary field, the lyrics to the Inuit songs demonstrate a remarkable vitality in which the author-composers explore various aesthetics, navigate languages and transmit a part of their culture. Taking into consideration the historical context, this article aims to reflect on the formal evolution of the modern Inuit song and examine the relations that are maintained through more traditional portrayals. Finally, the ultra-contemporary body of musical works in Nunavik is notable for being particularly trilingual yet reveals an upsurge of texts in Inuktitut. What significance will this have on the overall discourse?
Keywords: Inuit literature; Inuit songs; Inuktitut; Nunavik; canción inuit; chanson inuite; inuktitut; literatura inuit; littérature inuite; oralidad; orality; oralité

Rap, genre, langage et québéquicité : enjeux et tensions sociolinguistiques de l’accès aux espaces médiatiques à Montréal - Lesacher, Claire (Cahiers internationaux de sociolinguistique, 2016)

DJ Mini and Montreal’s Vulgar Dance Music - Madden, David (Dancecult, 2016)
This article advances claims about Montreal’s electronic dance music scene through mapping the career of one of the key actors who shaped the electroclash scene from the early 2000s onwards—music producer/DJ Mini (née Evelyne Drouin). By way of detailing the career of DJ Mini, this text attempts to add to the queer musical narratives currently emerging from music scene analyses. Counter to the experiences of many women DJs and musicians participating in heterosexual and male-dominated music scenes, Drouin received extensive mentoring and support from various informal queer social networks spread throughout the circuits of the city. Not only did she gain access to a local production network of equipment and skill sharing, Drouin was also given access to spaces where she was able to develop production skills on her own time and at her own pace. DJ Mini’s story offers a telling case for the ways in which the politics of access—institutional, social, technological—remain central to the vitality and inclusivity of local music scenes.

Analyses of Organ Etudes Opp. 38, 66 and 72 by Rachel Laurin - Mateva, Silviya (Université d'Oklahoma, 2016)

Listening to "Mes lames de tannage": Notes toward a Translation - Moyes, Lianne (Canadian Literature, 2016)

On the Internet by Means of Popular Music: The Cases of Grimes and Childish Gambino - Ohlendorf, Kristopher R. K. (Université Western Ontario, 2016)
What is the internet? It began as a military research experiment, but the internet has since become a sweeping cultural phenomenon. One of the most prevalent areas of the internet’s cultural dominance is in popular music, and this thesis addresses how the internet is being understood and discussed by popular music artists. I study the works of Grimes and Childish Gambino, two popular music artists who grew up alongside the internet’s rise to cultural dominance and explicitly address this experience as an integral component of their lives and works. I look specifically at discourse surrounding Grimes’ “post-internet” music and Childish Gambino’s expansive conceptual work Because the Internet (2013). This research concludes by addressing how popular music artists like Grimes and Childish Gambino are helping produce the ways in which we understand and discuss the cultural phenomenon of the internet, and how they provide a foundation for future artists and research to build upon.

« La terre qui nous a vus grandir ». Le sujet et le monde chez Mara Tremblay, Ariane Moffatt et Salomé Leclerc - Pirie, Nathan (Université de Waterloo, 2016)
Cette étude inclut les œuvres de Mara Tremblay, Ariane Moffat et Salomé Leclerc et vise un objectif double : d’une part, il s’agit d’analyser des textes lyriques qui ont une indéniable qualité poétique et d’autre part, de réaliser une étude intermédiale alliant texte, musique et clip-vidéo afin de voir comment le sens d’un de ces éléments est infléchi, modifié ou complété par celui des autres éléments. L’hypothèse de recherche est qu’aujourd’hui, les auteurs-compositeurs-interprètes conçoivent leur art à travers trois langages esthétiques (le texte, la musique et la vidéo), faisant de la musique une expérience plurisensorielle et intermédiale. Pour faire émerger le message de ces artistes, on mobilisera les théories du care et l’écoféminisme afin d’analyser le discours portant sur le sujet et le monde. On vise à dégager les grands thèmes de ces œuvres à travers une synthèse de ces trois approches critiques. L’analyse du corpus vise à déterminer la qualité poétique des textes et la vision du monde que ces trois artistes diffusent.

Vers une reconstitution de la vie culturelle des femmes à Montréal dans les années 1940 - Savoie, Chantal (Voix et Images, 2016)

Écritures chorégraphiques et sonores imbriquées : récits de collaborations avec Danièle Desnoyers - Tobin, Nancy (L’Annuaire théâtral : revue québécoise d’études théâtrales, 2016)
Ce texte revient sur le processus de création de trois spectacles chorégraphiques auxquels j’ai participé comme conceptrice sonore : Concerto grosso pour corps et surface métallique (1999), Duos pour corps et instruments (2003) et Là où je vis (2007). Ces parcours de recherche-création, traversés avec la chorégraphe Danièle Desnoyers (compagnie Le Carré des Lombes), permettent d’observer comment l’écriture sonore se développe in situ avec l’écriture chorégraphique. Les deux se forment ensemble en s’influençant l’une l’autre. Les trois spectacles choisis témoignent de différents modes de création de la matière sonore : amplification des danseurs, diffusion avec des haut-parleurs inusités, invention d’instruments et citation de musiques transformées. Les récits de collaborations qui suivent révèlent les manières dont la matière sonore a émergé de l’écriture chorégraphique et vice versa.

A Study of Selected Representative Organ Pieces by Rachel Laurin - Cheng, S.S. (Université du Kansas, 2015)
Over the course of the last decade the organ works of Canadian composer Rachel Laurin (b. 1961) have gained critical acclaim among professional organists. Her organ music has captured the attention of American and Canadian organists, resulting in a series of commissions for new organ works. To date, there are over thirty-two compositions for organ solo. This document explores stylistic issues in Laurin's compositions for solo organ and for organ with other instruments. Pieces that have been selected for in-depth study include Chromatic Fantasietta, Scherzetto, Toccatarina (to Katarina) and Asian Legend from Twelve Short Pieces, Volume 3, op. 64, Étude Héroïque, Op.38, and the Sonata for Organ and Horn, Op.60, II. On a Painting by Thomson. At the outset of the document an overview of Canadian organ culture is provided, followed by an introduction to Laurin's life and works. Subsequently, a structural and harmonic analysis of Laurin's compositions is presented. As this analysis will reveal, the expressive dimensions of her works embrace elements of Romanticism and Impressionism.

La Bolduc. Parlure et accents de ses chansons - Duguay, Sylvie (Éditions Sylvie Duguay, 2015)

ECM+ Génération 2014 : regards sur les quatre compositeurs lauréats (1re partie) - Henry, Symon (Circuit, 2015)

ECM+ Génération 2014 : regards sur les quatre compositeurs lauréats (2e partie) - Henry, Symon (Circuit, 2015)

Elkahna Talbi : femme de paroles - Lalonde, Catherine (Jeu : revue de théâtre, 2015)

Willie Eckstein, Harry Thomas, Vera Guilaroff: Three Montreal Pianists from the Jazz Age - Litchfield, Jack (Autoédition, 2015)

Mountain City Girls: The McGarrigle Family Album - McGarrigle, Anna; McGarrigle, Jane (Random House Canada, 2015)

Dans un grand champ nu. Des récits, des images, des chants - Miville-Deschênes, Monique (Éditions Trois-Pistoles, 2015)

Vie musicale à l'église Saint-Viateur-d'Outremont. Victoria Cartier, première grande figure - Panneton, Hélène (Mémoire vivante, 2015)

From Kitchen To Carnegie Hall: The Story of the Montreal Women's Symphony Orchestra - Rachwal, Maria Noriega (Second Story Press, 2015)
In the 1940s it was unheard of for women to be members of a professional orchestra, let alone play "masculine" instruments like the bass or trombone. Yet despite these formidable challenges, the Montreal Women's Symphony Orchestra (MWSO) became the only all-women orchestra in Canadian history. Formed in 1940, the MWSO became the first orchestra to represent Canada in New York City's Carnegie Hall and one of its members also became the first Canadian black woman to play in a symphony in Carnegie Hall. While the MWSO has paved the way for contemporary female musicians, the stories of these women are largely missing from historical records. From Kitchen to Carnegie Hall illuminates these revolutionary stories, including the life of the incredible Ethel Stark, the co-founder and conductor of the MWSO. Ethel's work opened doors of equal opportunity for marginalized groups and played an important role in breaking gender stereotypes in the Canadian music world.
Keywords: History / Canada / Post-Confederation (1867-); Music / History & Criticism; Music / Individual Composer & Musician

Les chemins de ma liberté - Simard, Nathalie (Éditions des Intouchables, 2015)

Marketing, Merch, and Media: Nicole Lizée, in Conversation - Wiseman, Howard; Disman, Adriana (Canadian Theatre Review, 2015)
Nicole Lizée is an award-winning classical music composer and performer who composes for string quartet, electronic music, turntable, film, and other media. She has emerged as a major new voice in new classical composition, winning the coveted Canada Council for the Arts Jules Léger Prize (2013) for new Canadian chamber music with her work White Label Experiment. She has been commissioned by the Kronos Quartet among many other prestigious ensembles. This interview engages her relation to various aspects of her work, from marketing and promotion to inspiration and creation in the context of “avant garde” music. How can marketing continue to be part of the art itself? Does instinctively not fitting into a box allow for greater freedom to explore classical and chamber music in the broader context of film and other media? What other factors may be contributing to the inspired vitality of her work?
Keywords: Entretien

Women in Leonard Cohen's Work - Álvarez Pérez, Maria Icíar (Multidisciplinary Views on Popular Culture: Proceedings of the 5th International Selicup Conference, 2014)

Glimpses Into My Compositional Style and Techniques : Text and Musical Examples - Badian, Maya (Lucian Badian Editions, 2014)

La Bolduc en tournée : un patrimoine matériel unique - Boulay, Vicky (Magazine Gaspésie, 2014)
An article from Magazine Gaspésie, on Érudit.

Soprano Pierrette Alarie (1921-2011), tenor Léopold Simoneau (1916-2006). Part 1 - Duffie, Bruce (Opera Journal, 2014)
Keywords: Interviews; Music; Musical performances; Musicians & conductors; Singers

Soprano Pierrette Alarie (1921-2011), tenor Léopold Simoneau (1916-2006). Part 2 - Duffie, Bruce (Opera Journal, 2014)
Keywords: Accompanists; Composers; Librettists; Music; Musical performances; Musicians & conductors; Opera; Singers

Les Daraîche, la famille royale du country - Dumas, Carmel (Magazine Gaspésie, 2014)
Un article de la revue Magazine Gaspésie, diffusée par la plateforme Érudit.

Mad Je Deviendrai : Les divas dans le hip-hop au Québec - Lamort, Kapois (Les boss du Québec. R.A.P. du fleur de lysée. Analyse socio-historique et sociologique du hip-hop dans la société québécoise, 2014)
Keywords: Italique avant les deux-points

Rap, langues, « québéquicité » et rapports sociaux de sexe : pratiques et expériences de rappeuses montréalaises d’origine haïtienne - Lesacher, Claire (Diversité urbaine, 2014)
In the stories recounting the early days of the rap scene in Montreal, actors of Haitian descent were particularly active on the rap scene: this is evident in rap texts, where frequent occurrences of Haitian Creole can be found. Considering this characteristic of Montreal rap, we propose a reflection on the issues around the visibility of Haitian migrants, and descendants of Haitian migrants, in Quebec public space by focusing on the practices and experiences of Montreal female rappers of Haitian descent. In this contribution, which aims at understanding the processes of hegemonization and minoritization at work in the Montreal and Quebec context, we will examine in particular how the vectors of differentiation involving language, “québéquicité” or gender, are manifested and reproduced in the media coverage of artistic productions.
Keywords: Haitian community; Rap; communauté haïtienne; gender; genre; languages; langues; « québéquicité »; “québéquicité”

In Search of a Different History: The Remains of Burlesque in Montreal - Mansbridge, Joanna (Canadian Theatre Review, 2014)
: Taking Elin Diamond’s and Rebecca Schneider’s recent work in drama and performance studies as a starting point, this essay looks at two eras of burlesque in Montreal—the 1940s-50s and 2012—tracing a shifting landscape of popular entertainment, politics, religion, and social attitudes toward female sexuality. There is a central question underlying this examination: Why burlesque? Why now (or, rather, again?). I argue that burlesque offers an archive that evokes a different, more glamorous history than the one passed down to women by second-wave feminism. Burlesque also provides an alternative to popular culture’s commodification of female sexuality, technology’s mediation of social life, and heteronormative culture’s privatization of sexuality, giving women—and men—a stage on which to make fun of our cultural fixation with sex and the female body. Both nostalgically looking back and eagerly reaching for the new, neo-burlesque repeats the past as it simultaneously reinvents it.

Nicole Lizée. Faisceaux imaginaires et cool media - McKinley, Maxime (La création musicale au Québec, 2014)

“We Paved the Way for Whatever Tolerance They Have in Their Lives”: An Interview with Michelle De Ville, “The First Door Bitch in Montreal” - Namaste, Viviane (Trans Activism in Canada: A Reader, 2014)
Centring the voices and experiences of trans identified people as experts on their own lives and agents of change, Trans Activism in Canada opens up a dialogue between scholars and community members in an effort to improve the lives of sex and gender variant people

Le voyage, la danse et la représentation des femmes dans la culture de grande consommation (1936-1947) - Savoie, Chantal (Les Cahiers de l'IREF, 2014)

Layers of creativity in composition, rehearsal and performance: Nicole Lizée and the Kronos Quartet - Bayley, Amanda; Lizée, Nicole (Tracking the Creative Process in Music Second International Conference, 2013)

Le son tactile ou la sensorialité excentrique dans les performances solos de Magali Babin - Abenavoli, Lorella (Circuit : musiques contemporaines, 2013)
How can the ephemeral touch of a caress become an aesthetic object? How can a fingernail scratching the mineral surface of a sheet of schist become music? How can intimate tactile experience become the scene of a collective artistic ritual? How does Magali Babin turn electronic sound into a medium for eccentric sensoriality? This article takes us into one region of Magali Babin’s artistic practice: the tactile world of sound that she uses in her solo performances. Author of a polymorphic sonic oeuvre, Magali Babin is a Quebec artist, performer, and composer whose artistic practice has incorporated sonic installations for the past two years. She is a key figure in Montreal’s alternative audio art, “edgy” improvisation, and experimental music scenes, moving freely among cutting-edge artistic categories.
Keywords: Magali Babin; art audio; art haptique; audio art; device; dispositif; eccentric sensoriality; electronic; haptic art; improvisation; performance sonore; sensorialité excentrique; sonic performance; électronique

Providing the Taste of Learning: Nadia Boulanger’s Lasting Imprint on Canadian Music - Boivin, Jean (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2013)
This article traces the rich Canadian legacy of the twentieth-century French musical legend Nadia Boulanger (1887–1979). Through teaching her more than seventy Canadian students, both French- and English-speaking, the renowned French pedagogue played a crucial role in the development of concert art music in this country from the 1920s, notably in Montreal and Toronto. Her numerous Canadian students went on to distinguish themselves as composers, teachers, performers, musicologists, theorists, administrators, and radio producers. Drawing on extensive archival and primary research, this study demonstrates the decisive impact Boulanger had on the development of musical styles and compositional practices in Canada in the last century.

Du rôle de l'interprète-chercheur en création et re-création musicale : théories, modèles et réalisations d'après les cas de Kathinkas Gesang (1983-1984) de Karlheinz Stockhausen et de La Machi (2007-2011) d'Analía Llugdar - Breault, Marie-Hélène (Université de Montréal, 2013)
Cette thèse est basée sur une approche méthodologique hybride relevant de recherche-création en musique et de musicologie appliquée à l’interprétation. Elle s’intéresse à cette question centrale : « Quels rôles l’interprète-chercheur occupe-t-il dans un contexte de création ou de re-création (ou d’interprétation) musicale » ? Pour y répondre, l’auteure examine et rend compte du processus créateur et re-créateur de deux œuvres significatives dans son parcours en tant qu’interprète, soit Kathinkas Gesang als Luzifers Requiem (1983-1984) de Karlheinz Stockhausen et La Machi, rituel pour flûtes, électronique et regards (2007-2011) d’Analía Llugdar. Le travail de ces œuvres mixtes qui comportent toutes deux une dimension théâtrale tout en mettant en scène des personnages instrumentaux l’amène aussi à traiter des problématiques de l’appropriation de l’œuvre par l’interprète-chercheur et de la liberté de celui-ci face aux œuvres présentant un haut degré de déterminisme notationnel. La première partie situe les contextes disciplinaires et théoriques des recherches de l’auteure. Le premier chapitre permet de comprendre comment s’exerce la recherche de l’interprète en musique et de situer les différentes modalités dans lesquelles ce type de recherche s’effectue. Le deuxième chapitre explique les notions d’interprétation, d’improvisation et de composition et il situe l’interprète par rapport à ces trois champs d’activités. L’auteure y compare aussi les modes créatifs du théâtre à ceux de la musique tout en s’intéressant aux divers types d’authenticité inhérents au travail d’interprétation. Le troisième chapitre pose le principal angle d’investigation et d’analyse adopté dans cette thèse, soit celui du timbre instrumental. La deuxième partie porte sur Kathinkas Gesang de Stockhausen. Le quatrième chapitre présente une chronologie récapitulative des différentes grandes périodes d’appropriation de l’auteure. Le cinquième chapitre présente et met en contexte le symbolisme du cycle Licht, die sieben Tage der Woche (1977-2003), dans lequel Kathinkas Gesang s’insère. Le sixième chapitre est voué à une analyse du symbolisme attribué au timbre des principaux instruments que l’on retrouve dans Licht. Le septième chapitre évalue l’impact de la présence des interprètes dans le processus compositionnel chez Stockhausen tout en traitant de la question du casting dans Licht. Le huitième chapitre s’articule en un lexique timbral présentant une exégèse des techniques de jeu employées dans Kathinkas Gesang pour produire divers types de timbres. La troisième partie porte sur La Machi d’Analía Llugdar. Dans le neuvième chapitre, l’auteure présente la structure générale de l’œuvre et son synopsis et elle traite du rôle qu’elle a joué dans le processus de création de cette œuvre. Le dixième chapitre prend la forme d’un lexique timbral présentant une exégèse des différentes techniques de jeu employées dans l’œuvre pour produire divers types de timbres. Dans la conclusion, trois sphères d’action et six rôles-types de l’interprète-chercheur en création et en re-création musicale sont identifiés. De plus, des réponses aux problématiques de l’appropriation de l’œuvre et de la liberté de l’interprète sont apportées. L’auteure y suggère également des pistes de réflexion pour la recherche- création en musique et elle y présente les principales retombées de la thèse.

Ginette Reno - Chanonat, Michelle (Éditions des Intouchables, 2013)
Ginette Reno est l'une des plus grandes chanteuses de toute l'histoire du Québec. C'est aussi la personnalité dont on a le plus parlé au cours des cinquante dernières années. Ses deux mille chansons, ses trente-huit albums et ses rôles au cinéma et à la télévision ont fait d'elle une véritable icône.

Parcours dans la programmation des concerts du Nouvel Ensemble Moderne - Couture, Ariane (Circuit : musiques contemporaines, 2013)
During its 25 years of activities, the nem has played 635 works by 374 composers at local concerts, public workshops or world tours. Collectively, these works cover most of the aesthetic tendencies of the music of the 20th century. However, it is possible to define the repertoire of the ensemble along two main axes: on one hand, works that have become “classics” of contemporary music, and, on the other hand, new works engaged in musical innovation. Thus, the policy for disseminating works through concerts established by Lorraine Vaillancourt introduces a new culture within the world of musical creation, based on the development of a repertoire of works from the 20th and 21st centuries.
Keywords: Nouvel Ensemble Moderne; concert; musical programming; programmation musicale; repertoire; répertoire

La Bolduc : une pionnière de l’émancipation des femmes au Québec - Dupuis, Andréann (Magazine Gaspésie, 2013)
Un article de la revue Magazine Gaspésie, diffusée par la plateforme Érudit.

« Donner le temps » : entretien avec Lorraine Vaillancourt - Goldman, Jonathan (Circuit : musiques contemporaines, 2013)
In an interview with Lorraine Vaillancourt, the founder and artistic director of the Nouvel Ensemble Moderne (nem) recounts her musical education in Quebec, Montreal and Paris, and goes on to describe the establishment and development of her ensemble, the choice of repertoire and her plans for the future.
Keywords: Lorraine Vaillancourt; Nouvel Ensemble Moderne; contemporary music ensemble; direction musicale; ensemble de musique contemporaine; musical conducting

Auditeurs en exil : le cas des Chiliens à Montréal et leur rapport à deux chansons emblématiques - Gonzalez, Laura Francisca Jordán (Volume !. La revue des musiques populaires, 2013)
Cet article examine l’expérience des auditeurs chiliens exilés à Montréal, se concentrant spécifiquement sur leurs écoutes pendant la dictature militaire (1973-1989). Issus d’une méthodologie mixte qui combine l’histoire orale et l’analyse musicale, les résultats de cette recherche musicologique révèlent la place primordiale que l’audition musicale eut chez les exilés dans la reconstruction d’un lien avec leur pays d’origine, ainsi que dans le développement du mouvement de solidarité avec le peuple chilien. L’article explique, d’abord, le déploiement des goûts musicaux et identifie les répertoires canoniques qui demeurent au centre des écoutes. Ensuite, il aborde le rôle de l’usage des enregistrements en vinyle et cassette, et de la radio dans la diffusion des musiques. Enfin, les deux dernières sections explorent les significations associées aux pièces musicales ‘Gracias a la Vida’ et ‘Vuelvo’, mettant en relief la complexité de la réception en ce qui concerne la construction des identités culturelles, le récit des histoires personnelles et communautaires.
Keywords: bootleg / piratage / contrefaçon; cassette / bande magnétique; communautés / minorités; migration / diaspora / exil; réception; écoute / auditeur

Construire le corps, construire la star : une agentivité à l'œuvre dans deux clips de Marie-Mai - Labrosse, Claudia; Melançon, Johanne (Chanson et performance. Mise en scène du corps dans la chanson française et francophone, 2013)
La moustache de Georges Brassens, la robe noire d’Edith Piaf, les paillettes de Claude François, les cheveux de Dalida… Les chanteurs ont un corps indissociable de leurs chansons, et ce livre s’intéresse précisément à la présence physique de la musique populaire, à sa performance sur scène et sur disque. Si le dualisme historique entre le corps et l’esprit a eu tendance, en France, à inluencer la réception de la chanson en attribuant plus de prestige à la modestie d’un Brassens qu’à la séduction démonstrative d’un chanteur de ‘variétés’, cet ouvrage est l’occasion de revenir sur cette opposition et de la nuancer, en identiiant les artistes qui ont su l’ignorer ou la contester. En légitimant l’étude de la performance (au sens de mise en scène du corps), cette étude met sur un pied d’égalité des genres aussi différents que la chanson ‘à textes’, le rock, le disco, le zouk ou le cabaret, et recadre les études sur la chanson loin de l’analyse de paroles. Il démontre, notamment, qu’en tant que véhicule de la chanson, le corps du chanteur reflète des a priori sociaux sur les rapports entre physique et séduction, genre et sexualité, apparence ethnique et identité, artiice et authenticité. Cet ouvrage est le fruit d’une collaboration entre chercheurs de GrandeBretagne, des États-Unis, du Canada, de Nouvelle-Zélande et de France, et dont la qualité commune est une fraîcheur d’analyse pluridisciplinaire inspirée des études culturelles. Observant les corps de chanteurs et chanteuses en France, aux Antilles et au Québec, ce livre offre une rélexion comparatiste sur les codes esthétiques en vigueur dans chaque contexte national, et observe les tensions sociales, sexuelles et identitaires qui sous-tendent la performance musicale.

Cross-dressing to Backbeats: An Exploration of the Practices, Wo/men Producers, and History of Electroclash - Madden, David (Université Concordia, 2013)
This research-creation dissertation focuses on the emergence of electroclash as a dominant form of electronic dance music in the late 1990s and early 2000s. Electroclash combines the extended pulsing sections of techno, house and other dance musics with the trashier energy of rock and new wave. The genre signals an attempt to reinvigorate dance music with a sense of sexuality, personality and irony. Electroclash also emphasizes, rather than hides, the European, trashy elements of electronic dance music. This project addresses the following questions: what is distinct about the genre and its related practices, both in and out of the studio? Why do rock and electro come together at this point and in this way? Why is electroclash affectively powerful for musicians, audiences and listeners? And, what does the genre portend in terms of our understandings of the politics of electronic music? The coming together of rock and electro is examined vis-à-vis the ongoing changing sociality of music production/distribution and the changing role of the producer. Numerous women, whether as solo producers or in the context of collaborative groups, significantly contributed to shaping the aesthetics and production practices of electroclash, an anomaly in the history of popular music and electronic music where the role of the producer has typically been associated with men. These changes are discussed in relation to the way key electroclash producers often used a hybrid approach to production involving the integration of new(er) technologies, such as laptops containing various audio production software with older, inexpensive keyboards, microphones, samplers and drum machines to achieve the ironic backbeat laden hybrid electro-rock sound.

In and out of the studio - McCartney, Andra (Université Concordia, 2013)
In and out of the studio was a collaborative multimedia project which aimed to examine and document the working methods of several female sound producers, from a variety of media (such as radio, film sound, television, hypermedia, performance art) and in different institutional contexts. The website, which is compiled in this document, was one element in an effort to establish a greater sense of community among women sound producers who are separated by geographic space, occupation or disciplinary boundaries.

Faisceaux imaginaires et cool medias : This Will Not Be Televised de Nicole Lizée - McKinley, Maxime (Circuit : musiques contemporaines, 2013)
The imagination of composer Nicole Lizée brings together disparate elements, largely drawn from cinema, philosophy, visual arts, and so-called popular music, with a pronounced penchant for the period from 1960-1980 and the ghostly effect thus conveyed. This article illustrates Lizée’s creative process through one of her characteristic works, This Will Not Be Televised (2005-2007), scored for DJ and seven instruments. Our analysis illustrates how the composer’s “beams of imagination” take form through a unique musical language, based here on a meticulously notated DJ part and extended through the instrumental ensemble, and which draws on cultural references, repetitive effects, and montages of juxtapositions and superpositions, and whose continuous form achieves cohesion through the use of repeats. In this way, the composer focuses on the connections that are generated in the memory and subjectivity of the hearer – the tabula rasa characteristic of McLuhan’s “cool” media.
Keywords: Nicole Lizée; This Will Not Be Televised; analyse; analysis; cool medias; tables tournantes; turntable; “cool” media

Notre Clémence. D'amour et d'humour - Pedneault, Hélène (Éditions de l'Homme, 2013)
Humoriste, poète, monologuiste, comédienne: Clémence DesRochers s'est constamment réinventée au cours de sa prolifique carrière. Prenant la parole au nom des gens d'ici, elle a tour à tour exprimé avec justesse les joies et les peines des ouvriers, des femmes, des laissés-pour-compte et des homosexuels. Chaque fois, ses mots nous ont touchés droit au cœur, nous faisant à la fois sourire et réfléchir. Ce livre rend hommage au parcours exceptionnel d'une auteure profondément humaine, accessible et chaleureuse qu'un prénom suffit à désigner. Redécouvrez Clémence, la femme, l'artiste, la peintre du quotidien qui n'a jamais cessé d'esquisser notre portrait.

„A Moncton“ von Marie-Jo Thério. Chiac in Literatur und Alltag [« À Moncton » de Marie-Jo Thério. Le chiac dans la littérature et la vie quotidienne] - Reinsberg, Franziska (Grin Verlag, 2013)
„C'est boring à soir“ - Vielfältiger und vermischter zeigt sich eine Sprache nur selten. Doch was ist das, was dort zu lesen ist? Das Ziel dieser Arbeit ist die Untersuchung der sprachlichen Strukturen dieser besonderen hybriden Sprachvarietät - dem Chiac, eine Varietät des akadischen Französisch, das im Osten Kanadas gesprochen wird.

Inégalités et minorisation des identités chez les femmes artistes dans la francophonie canadienne - Robineau, Anne (Nouvelles perspectives en sciences sociales : revue internationale de systémique complexe et d'études relationnelles, 2013)
Even if women artists are wishing for recognition of their work, independently from their gender, language and belonging to a cultural group, their practices conditions are sometimes linked to these statuses. Through a sociodemographic study of French Canadian artists, we will analyze more specifically the data on women artists. We will show that, even if they have a higher education than man, women artists usually are considerably less paid for their services. We will also try to understand if minorization processes of women from professional artistic francophone communities can explain some gender inequalities and how the production of identity discourses (women, francophonie, linguistic minority) reinforce tensions between art and the identity perspective.
Keywords: Artiste; Artists; Canadian Francophonie; femmes; francophonie canadienne; inequalities; inégalités; minorisation; minorization; women

La chanson à succès dans les années 1940. Une modernité culturelle par acclamation ? - Savoie, Chantal (Globe, 2013)
Dans le contexte de travaux plus larges portant sur l’histoire de la chanson à succès par l’analyse des préférences musicales des lectrices du Bulletin des agriculteurs dans les années 1940, nous nous intéressons ici aux éléments qui permettent de comprendre les modalités par lesquelles les goûts musicaux témoignent de l’émergence d’une modernité culturelle au Québec dans les années 1940. Deux postulats orientent notre perspective. Le premier consiste à supposer l’existence d’une modernité culturelle « populaire » qui transite par la forme, les supports et la technologie. Le second sonde la façon dont les thèmes intimes et la focalisation sur l’expression du sentiment amoureux marquent une transformation des valeurs et, surtout, explore les marques formelles et discursives qui portent ces valeurs dans la chanson à succès. , As part of a larger research project on the history of popular song, which analyzes the musical preferences of the female readers of the Bulletin des agriculteurs in the 1940s, this article focuses on those elements that allow for an understanding of the modalities by which these women’s musical tastes reflected the emergence of a cultural modernity in Quebec during that decade. Two basic premises orient my perspective on the subject. The first presupposes the existence of a “popular” cultural modernity based on form, equipment, and technology. The second explores both the way in which intimate themes and the importance given to expressions of love reflected a shift in values, as well as the formal and discursive markers that transmitted these values in popular song.

Feminism, Media Technologies, and Studio XX: An Interview with Kim Sawchuk - Sawchuk, Kim; Tripp, Stephanie (Media-N: Journal of the New Media Caucus., 2013)
Kim Sawchuk is a feminist media studies scholar and a founding member of Studio XX, a feminist-run new media arts collective based in Montreal. A professor in the Department of Communication Studies at Concordia University, she is the former editor of the Canadian Journal of Communication and co-editor of wi: journal of mobile media. Sawchuk’s work encompasses the roles of women in science and technology, as well as issues surrounding media technology access and use by women, elders, and immigrant communities. Her more recent research involves the use of mobile devices by older adults. During a Skype interview with guest editor Stephanie Tripp on March 22, 2013, Sawchuk discussed her collaboration in Studio XX, her research on women and technology, her work on mobile communications technologies, and her outlook on issues facing women working in new media today.

Diane Dufresne - Villeneuve, Anne-Marie (Paroles de femmes, 2013)
Croyez-vous que chaque individu a le devoir de trouver sa vocation ? Vous trouvez-vous douée pour le bonheur ? Peut-on se préparer à la souffrance ? Avez-vous déjà regretté d'être née femme ? Y a-t-il des choses qui vous révoltent actuellement dans notre société ? Voilà un aperçu du type de questions qui ont été posées à nos cinq personnalités publiques. Des questions qui demandent temps et réflexion, mais ô combien nécessaires pour faire le point sur le chemin parcouru et pour porter un regard philosophique sur l'avenir.

Maryvonne Kendergi (1915-2011) : hommage et mémoire - Bail, Louise (Circuit, 2012)

L'extase figurative : incarnation du Verbe dans l'espace scriptural (une analyse du Cantique d'actions de grâce ou Chant d'amour de Dina Bélanger) - Bergeron, Carlos (Université du Québec à Chicoutimi, 2012)
En 1924, les supérieures de la communauté des Jésus-Marie, à Sillery (Québec), demandent à Dîna Bélanger (1897-1929), Mère Marie Sainte-Cécile de Rome alors supposément aux portes de la mort, d'écrire son autobiographie qu'elle intitula Cantique d'actions de grâces ou Chant d'amour. C'est ce texte mystique écrit par obéissance, inachevé et dans lequel une énonciatrice multiplie les procédés rhétoriques pour faire valoir son droit à la sainteté, sainteté qu'elle lie à une écriture missionnaire ayant l'étonnant pouvoir de sauver des âmes, qui constitue l'objet de la présente thèse. L'originalité du texte analysé réside surtout dans la combinaison qu'il propose : autant la volonté d'inscrire une Parole de Dieu que l'étude des paramètres énonciatifs par lesquels l'énonciatrice en vient à en proposer un équivalent langagier, dans un cadre scriptural clamant son appartenance à l'autobiographie, sont des éléments nous assurant des assises pertinentes. Les notions théoriques créées pour rendre compte du fonctionnement d'une écriture prenant le pari de figurer l'indicible sont relatives à la « transcendance » comme principe actif présidant à l'encodage comme au décodage du texte mystique: «l'extase figurative », c'est-à-dire la prise en charge d'une insurmontable absence entre le langage et ce à quoi il réfère dans un cadre discursif où il s'agit souvent de donner des mots à la Parole de Dieu (l'indicible), et « l'indice trans », fonction imputée à une figure obligeant une interprétation de son énonciation au détriment de son contenu qui semble irrécupérable, nous conduisent précisément à théoriser une lecture originale du Cantique de Dina Bélanger. Ainsi, la rhétorique comme champ disciplinaire nous permet de rendre compte du mode de fonctionnement du texte analysé que nous avons divisé en trois phases complémentaires. La première phase est constituée d'une introduction (« Loués soient à jamais Jésus et Marie ») dans laquelle, d'une part, la narratrice explique la genèse de son acte scriptural : il s'agit de répondre à la volonté divine; d'autre part, elle cible les principaux objectifs de ce travail qu'elle s'apprête à accomplir. La seconde phase, soit les chapitre I à XIX (pp. 41-192), construit le portrait d'une sainte qui est supposément digne d'être le messager d'une « voix » entendue intérieurement; ce portrait est organisé par la narration de certains faits biographiques auxquels Dina accorde un traitement qui souscrit, grâce à l'alternance de deux isotopies principales (terrestre et spirituelle), à l'établissement d'une polysémie inductrice des premiers balbutiements d'un effet de « transcendance », d'où une possible diffusion de la « Parole », mais dans l'optique où l'énonciatrice, piégée par sa « tiédeur » humaine (son manque de foi), ne fait ici que « donner la parole à la Parole » afin de sanctionner sa propre prédestination. La troisième phase est constituée de deux parties complémentaires que nous avons intitulées «Abandon», débutant le 15 août 1924 pour se terminer le 25 janvier 1925 (essentiellement les chapitres XX et XXI, pp. 193-208) et «Message», ce journal spirituel resté inachevé (les chapitres XXII à XLVI, pp. 209-391), qui illustre l'entrée graduelle de l'énonciatrice dans ce qu'elle nomme la « Trinité », c'est-à-dire un espace « fabuleux » (relatif à la fable) où le Verbe est incarné dans l'espace scriptural par une sainte organisant effectivement son discours pour un lectorat composé de religieux tièdes qui doivent être persuadés de cette sainteté, puisque il en va du salut de toutes les âmes (la reconnaissance de la sainteté de Dina, sans preuve, supposant le passage de la tiédeur à la ferveur). La narratrice, substituée, donne alors la Parole au lecteur. Cette troisième phase du Cantique, dans laquelle l'alternance des isotopies cède sa place à la substitution de l'une par l'autre, impose la dominance du thème spirituel et, dans le contexte, la poétisation de l'écrit qui lui est indissociable. Cette étape ultime, qui est néanmoins représentative de tout cheminement mystique « canonique », crée le sentiment que la narratrice s'est libérée de tous ses liens terrestres et que son écriture est Union en acte. La transition de la « Parole » au « Verbe », produit d'un renversement nous faisant passer d'un univers plutôt factuel (seconde phase) à un monde généralement fabuleux (troisième phase), nous amène à analyser l'évolution suivante : de simples faits biographiques acquièrent rétrospectivement la possibilité de prendre une envergure poétique de par cette capacité qu'a une figure de « contaminer » l'énoncé dont elle fait partie. Finalement, les lecteurs idéals du Cantique, ces religieux plutôt tièdes par rapport à la narratrice, font à leur tour un acte de foi en prenant la parole (Parole) dans le paratexte afin de faire valoir le droit à la sainteté de l'énonciatrice. Leurs commentaires sont en grande partie relatifs au texte qu'ils jugent souvent comme un élément de preuve de cette sainteté que, comme Dieu, ils souhaitent pour Dina. Ils seraient prêts à la soutenir devant le Pape qu'une convention fait le représentant de Dieu sur Terre.

The Vocal Music of Ana Sokolović: Love Songs for the Twenty-First Century - Bernstein, Tamara (Circuit, 2012)
Enchanted by the vocal music of Serbian-born Canadian composer Ana Sokolović, Tamara Bernstein visited the composer at her home in Montreal. Sokolović’s music draws on several sources, including the theatrical world and the culture of the Balkans. The extended vocal techniques in Sokolović’s music are rooted not in the avant-garde music of the twentieth century, but in the oral traditions and poetic voice of Serbia. It seems that the more the composer returns to her cultural roots, the more she embraces the universality of the human soul.

Life notations of Daisy Sweeney: reflections of othermothering, musicianship and Montreal - Campbell, Arlene (Université York, 2012)
The life story of Mrs. Daisy Sweeney, an African Canadian native of Montreal, Quebec, helps fill a void in the historical documentation of Montreal Blacks (especially female elders). Of particular significance is her prominence as a music educator and othermother during her life. The current literature on African Canadian othermothering experiences is not synonymous with both White or African American females and inclusion of their voices in academic, as well as mainstream spaces, is virtually non-existent. This dissertation asks: What did it mean to be a first generation 'Negro' working class bilingual female in a largely hostile White francophone Quebec metropolis in the early 20th Century? How can her narratives help shape and inform life history and African Canadian othermothering research? My sojourn with Mrs. Daisy Sweeney referenced African centered epistemology in my conceptual understanding of herself and community mothering. Capturing her conversations meant engaging with multiple methodologies articulated through African oral traditions, life history, archival canons and interdisciplinary inquiries. It is striking to note that there were not only certain tensions associated with memory loss and physical limitations (prompted by the aging process) that destabilized and enriched our 'interactive' communication, but also revealed a rupture and reversal of the participant/researcher dynamic. In spite of blatant racial discrimination that plagued Montreal's Black communities during that time, Daisy Sweeney fulfilled a life-long dream and taught hundreds of children the canon of classical piano for over 50 years. She lived her voice through her music, finding ways to validate her own identity and empowering others in the process. She used the musical stage as her platform to draw invaluable connections between race, gender, language and social class. Daisy Sweeney's generation of othermothers is dying out and, as the carriers of culture, the urgency to tell their stories must be emphasized. The account respects, reclaims and reflects those voices. It is time to write in African Canadian female elders and diversify the exclusionary genre of life history and archival research.

De l’ombre à la lumière : fragments pour une analyse des trois premiers albums d’Ariane Moffatt - Doyon, Noémie (Canadian Folk Music, 2012)

Femme-acrobate, femme-automate : Le Fil de Camille et Le Cœur dans la tête d'Ariane Moffatt - Doyon, Noémie (Chanson et performance. Mise en scène du corps dans la chanson française et francophone, 2012)
La moustache de Brassens, la robe noire d'Edith Piaf, les paillettes de Claude François, les cheveux de Dalida ... Les chanteurs ont un corps indissociable de leurs chansons. Ce livre s'intéresse à la présence physique de la musique populaire, à sa performance sur scène et sur le disque. Voici observées les tensions sociales, sexuelles et identitaires qui sous-tendent la performance musicale

La famille Daraîche. Une page du country au Québec - Dumas, Carmel (Éditions Pratiko, 2012)
Lorsque la barmaid du Rocher Percé que fréquente la diaspora à Montréal se met à chanter avec les portiers pour secouer la nostalgie des clients, commence à s'écrire une page de la petite histoire du Québec et de sa populaire chanson country. Les trois disques d'or enregistrés au début des années 70 par les Gaspésiens Julie Daraîche, Bernard et Fernand Duguay ont donné au répertoire des chansons immortelles et c'est sur cette base solide que s'est bâtie la légende de la Famille Daraîche, ralliant sur quatre décennies et deux générations l'authenticité de Julie, la musicalité de Paul, l'énergie de Dani et la douceur de Katia. Leur histoire en est une d'audace, de solidarité et d'appartenance qui rejoint et inspire depuis plus de 45 ans les artistes et le public qui retrouvent en eux leurs propres racines.

Forestier selon Louise. Pas d'choker pas d'collier - Forestier, Louise (Éditions La Presse, 2012)
De Louise Belhumeur, née à Shawinigan, élevée à Montréal et étudiante à l'École nationale de théâtre elle est devenue Louise Forestier, grande artiste ayant louvoyé toute sa vie entre chanson, théâtre, cinéma, radio et télévision. Dans son autobiographie qu'elle qualifie d'autoportrait, Louise Forestier se raconte avec générosité et franchise. Ses rencontres, ses triomphes et ses défaites ainsi que les moments déterminants de la vie d'une femme sensible et d'une artiste passionnée. Celle qui a connu le succès avec entre autres l'Osstidcho, Demain matin, Montréal m'attend, Starmania, IXE-13, Les Ordres et son rôle dans Le Négociateur a su toujours se renouveler avec audace, humour, créativité et authenticité. Nous la suivons de son enfance, au sein d'une famille pas toujours facile, à ses amours tumultueuses, à son état de mère absente, de femme déterminée à vaincre la dépression, à celle qui a vécu des heures de gloire professionnelle nombreuses. Un voyage au centre des événements culturels qui ont marqué le Québec et notre histoire collective et qui incluent des gens comme Robert Charlebois, Yvon Deschamps, Mouffe, Ginette Reno, Les Cyniques, Isabelle Boulay et Zachary Richard. Un récit touchant, dans lequel la femme artiste laisse libre cours à ses pensées, à ses souvenirs et à sa passion.

Introduction : la voix d’Ana Sokolović - Goldman, Jonathan (Circuit, 2012)

Musical Robots and the Serbian Kolo: A Narrative Analysis of Ana Sokolović’s Géométrie sentimentale (1997) - Harman, Brian (Circuit, 2012)
Composer Ana Sokolović divided her instrumental work Géométrie sentimentale into large sections inspired by pure geometric shapes — Triangle, Cercle and Carré — describing these sections as three contrasting perspectives of the same musical materials. This article uses a narrative analytical approach as a lens through which to understand these distinct sections and the materials populating them. Inspired by Sokolović’s employment of musical objects in her compositions and by the extra-musical concepts inspiring many of her works, this analysis uses a collection of colourful robot toys as metaphors for the work’s materials. Three unique perspectives of these toys are described: in Triangle, the robots interact as characters on a dramatic stage; in Cercle, they peacefully coexist in slow motion; and in Carré new combinations of robot elements are abruptly juxtaposed against each other. The characteristics and interactions between these toys, as well as the various harmonic ‘masks’ that the composer has them wear, are helpful in understanding Sokolović’s harmonic structure, variation/transformation techniques, formal organization and rhythmic characteristics. The Serbian kolo is also shown as influential on the work, relating directly to the physicality and kinetics of the metaphorical robots.

El cancionero judeoespañol en transición: Un estudio de dos compilaciones de mujeres sefarditas del siglo XX [Le répertoire de chansons judéo-espagnoles en transition : étude de deux compilations de femmes sépharades du XXe siècle] - Havassy, Rivka (Ladinar, 2012)

Different Folk: The Discreet Charm of Kate and Anna McGarrigle - Jelly-Schapiro, Joshua (American Quarterly, 2012)

Diane Dufresne : muse en scènes - Lebrun, Barbara (Chanson et performance. Mise en scène du corps dans la chanson française et francophone, 2012)
La moustache de Georges Brassens, la robe noire d’Edith Piaf, les paillettes de Claude François, les cheveux de Dalida… Les chanteurs ont un corps indissociable de leurs chansons, et ce livre s’intéresse précisément à la présence physique de la musique populaire, à sa performance sur scène et sur disque. Si le dualisme historique entre le corps et l’esprit a eu tendance, en France, à inluencer la réception de la chanson en attribuant plus de prestige à la modestie d’un Brassens qu’à la séduction démonstrative d’un chanteur de ‘variétés’, cet ouvrage est l’occasion de revenir sur cette opposition et de la nuancer, en identiiant les artistes qui ont su l’ignorer ou la contester. En légitimant l’étude de la performance (au sens de mise en scène du corps), cette étude met sur un pied d’égalité des genres aussi différents que la chanson ‘à textes’, le rock, le disco, le zouk ou le cabaret, et recadre les études sur la chanson loin de l’analyse de paroles. Il démontre, notamment, qu’en tant que véhicule de la chanson, le corps du chanteur reflète des a priori sociaux sur les rapports entre physique et séduction, genre et sexualité, apparence ethnique et identité, artiice et authenticité. Cet ouvrage est le fruit d’une collaboration entre chercheurs de GrandeBretagne, des États-Unis, du Canada, de Nouvelle-Zélande et de France, et dont la qualité commune est une fraîcheur d’analyse pluridisciplinaire inspirée des études culturelles. Observant les corps de chanteurs et chanteuses en France, aux Antilles et au Québec, ce livre offre une rélexion comparatiste sur les codes esthétiques en vigueur dans chaque contexte national, et observe les tensions sociales, sexuelles et identitaires qui sous-tendent la performance musicale.
Keywords: France; Music; Popular music; Social aspects

Quand le rap dit la ville : perceptions sociolinguistiques des rappeuses de Montréal - Lesacher, Claire (Dynamiques sociolangagières de l’espace algérois. Discours et représentations, 2012)

De la cuisine au studio - Lupien, Anna (Éditions du remue-ménage, 2012)
De la cuisine au studio explore les parcours de douze artistes issues de trois générations différentes : femmes signataires du manifeste Refus global en 1948, premières cinéastes qui ont œuvré à l’ONF dans les années 1970 et artistes médiatiques impliquées au Studio XX. À partir d’entrevues avec les artistes, Anna Lupien pose un regard sociologique sur l’expérience de créatrices qui ont investi l’art en tant qu’espace d’expression dans la sphère publique. De quelle façon ont-elles élaboré des stratégies créatives et par le fait même donné corps à des transformations sociales engendrées par le mouvement féministe, notamment en ce qui a trait à la conciliation travail-famille ? Comment ont-elles intégré des milieux artistiques qui ne leur étaient pas ouverts d’emblée ? Comment se sont-elles engagées pour le bien commun à travers leur parcours artistique ? Les histoires de ces artistes – Madeleine Arbour, Christine Brault, Mireille Dansereau, Dorothy Todd Hénaut, Stéphanie Lagueux, Bérengère Marin-Dubuard, Helena Martin Franco, Terre Nash, Anne-Claire Poirier, Françoise Riopelle, Bonnie Sherr Klein et Françoise Sullivan – témoignent des luttes inachevées du mouvement féministe et des brèches qu’elles ont pratiquées dans l’ordre des choses, suscitant des rencontres originales entre l’art et le politiqu

Crossdressing to Backbeats: The Status of the Electroclash Producer and the Politics of Electronic Music - Madden, David (Dancecult, 2012)
Addressing the international emergence of electroclash at the turn of the millenium, this article investigates the distinct character of the genre and its related production practices, both in and out of the studio. Electroclash combines the extended pulsing sections of techno, house and other dance musics with the trashier energy of rock and new wave. The genre signals an attempt to reinvigorate dance music with a sense of sexuality, personality and irony. Electroclash also emphasizes, rather than hides, the European, trashy elements of electronic dance music. The coming together of rock and electro is examined vis-à-vis the ongoing changing sociality of music production/distribution and the changing role of the producer. Numerous women, whether as solo producers, or in the context of collaborative groups, significantly contributed to shaping the aesthetics and production practices of electroclash, an anomaly in the history of popular music and electronic music, where the role of the producer has typically been associated with men. These changes are discussed in relation to the way electroclash producers Peaches, Le Tigre, Chicks on Speed, and Miss Kittin and the Hacker often used a hybrid approach to production that involves the integration of new(er) technologies, such as laptops containing various audio production softwares with older, inexpensive keyboards, microphones, samplers and drum machines to achieve the ironic backbeat laden hybrid electro-rock sound.

Choral, Public and Private Listener Responses to Hildegard Westerkamp's École - McCartney, Andra; McCarthy, Marta (Music and Arts in Action, 2012)
Hildegard Westerkamp's (1990) composition École Polytechnique is an artistic response to one of Canada's most profoundly disturbing mass murders, the 1989 slaying of fourteen women in Montreal, Quebec. Using the theoretical model, derived from Haraway, of the cyborg body, and analyzing the import of the mixed media (voices, instruments and electroacoustic tape) incorporated in the music, the authors examine the impact this work has had on some of those who have heard it and performed it, based on the responses of choristers and listeners in several studies. The authors explored how those who engaged significantly with the music, (including those who had no personal association with the actual events of the 1989 massacre), were able to make relevant connections between their own experience and the composition itself, embrace these connections and their disturbing resonances, and thereby experience meaningful emotional growth.

Cartographie de l’apprentie - Messier, Anne (Circuit, 2012)
La compositrice québécoise Ana Sokolović est d’origine serbe et plusieurs de ses oeuvres font référence à son pays d’origine, que ce soit par l’utilisation de mélodies et de rythmes traditionnels ou par des références culturelles. Pour approfondir son héritage serbe, l’auteure s’est entretenue avec la compositrice en mars 2012. L’article relate les paysages de son enfance et de son adolescence, l’environnement musical, culturel et politique de ses années d’apprentissage. Le portrait de sa vie familiale et de son quotidien nous permet de saisir des éléments constituants de sa personnalité d’artiste en devenir. Sa décision de s’établir à Montréal est explorée et elle raconte comment elle a pris conscience de son héritage slave.

« J’aime quand on explose de joie ! » : entretien avec Ana Sokolović - Panneton, Isabelle (Circuit, 2012)
Lors d’un entretien réalisé par la compositrice Isabelle Panneton, Ana Sokolović discute de ses inspirations, de ses méthodes et de son rapport avec les interprètes de sa musique.

Le pouvoir créateur d’Alfred et de Clémence - Roy, Julie; Fortier, Hélène (Revue de Bibliothèque et Archives nationales du Québec, 2012)

Sociologie et vecteurs de la popularité : l'mpact de la réception féminine sur la chanson québécoise des années 1940 - Savoie, Chantal (25 ans de sociologie française de la musique en France. Réflexivité, écoutes, goûts, 2012)

L'intuition de/dans l'œuvre de la compositrice québécoise Isabelle Panneton: un défi à la bipartition du genre - Stévance, Sophie (Le genre à l'œuvre, 2012)

La réalité socioprofessionnelle des musiciennes au Québec : un engagement vers l’écriture du féminin - Stévance, Sophie (Loin des yeux près du corps. Entre théorie et création,, 2012)

Violet Archer's "The Twenty-Third Psalm" (1952): An Analytical Study of Text and Music Relations Through Fibonacci Numbers, Melodic Contour, Motives, and Piano Accompaniment - Wan, Jessica Jane (Université d'Ottawa, 2012)
This study explores text and music relations in Canadian composer Violet Archer's “The Twenty-Third Psalm” by analysing the text of Psalm 23, Fibonacci numbers, melodic contours, motives, and the role of the accompaniment. The text focuses on David's faith in God and his acceptance of God as his shepherd on earth. The four other approaches allow us to examine the work on three different structural levels: background through Fibonacci numbers, middleground through melodic contour analysis, and foreground through motivic analysis and the role of the accompaniment. The measure numbers that align with Fibonacci numbers overlap with some of the melodic contour phrases, which are demarcated by rests, as well as with the most important moments at the surface level, such as the emphasis on the word “death” through recurring and symbolic motives. The piano accompaniment further supports these moments in the text.
Keywords: Archer; Canadian music; Communication and the arts; Fibonacci numbers; Melodic contour; Motivic analysis; Music analysis; Psalm 23; Text and music relations; The Twenty-Third Psalm (1952); Theory; Violet

Selanikli Humour in Montreal: the Repertoire of Bouena Sarfatty Garfinkle (1916-1977) - Cohen, Judith R. (Judeo Espaniol: Textos satíricos judeoespañoles: de salonicenses o sobre salonicenses/Satirical Texts in Judeo-Spanish by and about the Jews of Thessaloniki, 2011)

National Affection: Céline Dion - Hurley, Erin (National Performance: Representing Quebec from Expo 67 to Celine Dion, 2011)
In National Performance, Erin Hurley examines the complex relationship between performance and national identity. How do theatrical performances represent the nation in which they were created? How is Quebecois performance used to define Quebec as a nation and to cultivate a sense of 'Quebec-ness' for audiences both within and outside the province? In exploring Expo 67, the critical response to Michel Tremblay's Les Belles Soeurs, Carbone 14's image-theatre, Marco Micone's writing practices, Cľine Dion's popular music, and feminist performance of the 1970s and 80s, Hurley reveals the ways in which certain performances come to be understood as 'national' while others are relegated to sub-national or outsider status. Each chapter focuses on a particular historical moment in Quebec's modern history and a genre of performance emblematic of the moment, and uses these to elaborate the nature of the national performances. Winner of the Northeast Modern Language Association's Book Prize, National Performance is sophisticated yet accessible, seeking to enlarge the parameters of what counts as 'Quebecois' performance, while providing a thorough introduction to changing discourses of nation-ness in Quebec

Entretien avec Isabelle Panneton - Lefebvre, Marie-Thérèse (Les Cahiers de la Société québécoise de recherche en musique, 2011)
Sous forme d’entrevue, la compositrice se remémore les moments importants des cours d’analyse de Gilles Tremblay, plus particulièrement sa manière d’aborder le rapport de la poésie et de la musique, ainsi que son souci du traitement vocal, une approche qui se démarque par son caractère instinctif et sa vision organique des oeuvres. La compositrice parle également de sa propre approche de la poésie et présente quelques-uns de ses projets.

De la cuisine au studio : le rapport public/privé interrogé au fil des parcours d'artistes québécoises de trois générations - Lupien, Anna (Université du Québec à Montréal, 2011)

Ethel Bruneau: Montreal’s Rhythm Tap Legend - Lys, Stevens (Dance Collection Danse, 2011)

Lara Fabian. Toutes les femmes en elle - Patinier, Jérémy (Lulu Press, 2011)
Peu de chanteuses sont aussi multiples : auteur, compositeur, comédienne et bien sûr chanteuse, Lara Fabian est une artiste, au sens plein du terme : extrêmement sensible, vibrant pour son art, elle ne laisse pas de marbre ! Soit on l’aime, follement, comme les milliers de fans qui la suivent, soit on l'attaque, avec acharnement… Belgo-sicilienne de naissance et québécoise de cœur, elle est devenue en 25 ans de carrière (en 2011, soit plus de 12 millions de disques vendus) une star dans ses deux pays, puis en France et aussi en Russie et au Brésil… Retour sur un parcours en chansons, en portraits, tout en émotion, dans l’intimité de l’artiste et de son travail, de son entourage jusqu'à ses fans, mais aussi sur les zones d’ombre... Anecdotes, révélations.

La poétesse de l'ombre [entretien avec l'artiste sonore Nancy Tobin] - Siaud, Florent (Théâtre/Public, 2011)

"Give Me Aladdin's Lamp”: A Possible Perspective of Modernism - Ştefan, Angi (Musicology Papers, 2011)
Defining the differentiated semantics of new and novelty, reversing the dictum non nova sed nove into non nove sed nova, the author of the chamber cantata „Give me Aladdin’s lamp” is based on the rich experience of leading myriad of mid-century modernism. The investigation of the paradigms of new relationships between vocal and instrumental in creation of Dora Cojocaru, is directed in present at the chamber cantata for mezzo-soprano, brass quintet and percussion on lyrics by Emil & Dan Botta, Georg Trakl, Rainer Maria Rilke and Ady Endre (1998). The relations text - melody by their phenomenological reduction to fruitful combinations between poetic word - musical sound in Dora Cojocaru’s cantatas represent a stylistic-rhetorical subsumption of autochthonous and foreign experiences in promoting new compositional and interpretive skills meant for adaptation of appropriate musical expression in portraying contemporary aesthetic message. They are designed on the wide range of contemporary aesthetic values from the grotesque in nascendi to the absurd in morendi. As long as the Cantata Galgenlieder in der Nacht with lyrics by Christian Morgenstern (1995) is conceived at the grotesquely pole on the axis of the field of contemporary aesthetics, the Cantata Give me Aladdin’s lamp is designed in the sphere of the tragic. In the composer’s vocal and instrumental creation (and not only in them) the experiences of today’s musical composition and interpretation are rethought creatively, suggesting in perspective the permanence of modern horizons.

Le 'principe de contrainte stimulante' dans l'œuvre de la compositrice Isabelle Panneton - Stévance, Sophie (Médecine des arts, 2011)

Survivre aux naufrages - Thalie, Lynda (Éditions La Semaine, 2011)
Elle en a fait du chemin, la petite Lynda qui a débarqué au Québec après avoir quitté une Algérie à feu et à sang! De l'intégrisme religieux à la liberté d'être, nous découvrons le parcours de la jeune fille affranchie, la naissance de l'artiste, de la conférencière, de la femme et de la mère qu'elle est aujourd'hui.

La fille du Saint-Laurent - Thibeault, Fabienne (Éditions du Moment, 2011)
Fabienne Thibeault retrace les péripéties de sa légende familiale, aux sources de son ascendance canadienne française, dans le Charlevoix de son enfance. Fille de maçon, petite-fille de cultivateurs, fille de la ville, petite-fille de la campagne, elle relate le destin de ses grands-parents, oncles et tantes, nombreux cousins et cousines, tous incarnant avec force un peuple qui s'est forgé à travers une vie âpre, une foi simple et l'amour de la musique.Autour de la figure très aimée de son père, la chanteuse ressuscite le Québec d'autrefois, terre de pionniers, de mariniers et de bûcherons. Une ode à la nature et à des figures inoubliables. Plus tard ses parents s'installent dans les quartiers ouvriers de Montréal, où elle grandit. Dans les années 1970, la jeune fille, qui se destine à la pédagogie, chante aussi avec sa bande, sa «gang de chums». Découverte par Luc Plamondon, elle est choisie pour l'un des premiers rôles de Starmania, qui se monte à Paris. Choc des cultures, rencontre avec des stars, Michel Berger et France Gall notamment, elle dévoile les coulisses de cet opéra-rock devenu un spectacle-culte.Tragique, drôle, tendre, corrosif, ce récit foisonnant dessine aussi le portrait d'une femme entière, originale, que la France a adoptée et à qui le public est fidèle depuis trente ans.

Kanadisches Französisch im Unterricht - Lynda Lemay: Les maudits Français [Le français canadien en classe - Lynda Lemay : « Les maudits Français »] - Thiele, Sylvia (Varietäten im Französischunterricht. 1. Französische Fachdidaktiktagung [Les variétés dans l'enseignement du français. 1er colloque de didactique du français], 2011)

"Si mosós no las vamos a recoger...": The Songbooks of Emily Sene and Bouena Sarfatty-Garfinkle - Havassy, Rivka (Los sefardíes ante los retos del mundo contemporáneo. Identidad y mentalidades [Les sépharades face aux défis du monde contemporain. Identité et mentalités], 2010)

Diane Dufresne, sentiments partagés. Hommages de personnalités et de fans - Rousseau, Denis (Les Éditions Québec-Livres, 2010)
À la fois superstar et femme secrète, Diane Dufresne est une des rares artistes à susciter autant de passion au Québec, en France et dans toute la francophonie. Depuis quatre décennies, ses admirateurs sont légion des deux côtés de l'Atlantique et le milieu artistique reconnaît unanimement son audace et son immense talent de créatrice

Être compositeur aujourd'hui : entretien de Sophie Stévance avec Isabelle Panneton - Stévance, Sophie (Composer au XXIe siècle. Pratiques, philosophies, langages et analyses, 2010)

Quelle place pour les femmes dans la création musicale au XXIe siècle ? - Stévance, Sophie (Composer au XXIe siècle. Pratiques, philosophies, langages et analyses, 2010)

Reprise et intertextualité musicale. L’hommage à La Bolduc par des compositrices engagées vers l’avant - Stévance, Sophie (Volume ! La revue des musiques populaires, 2010)
Cet article étudie la notion de reprise sous l’angle de l’Hommage à La Bolduc rendu par sept compositrices à Mary Travers (alias La Bolduc), icône de la musique populaire au Québec dans les années 1930, à l’occasion du Festival SuperMicMac. Par des allusions, des références précises et explicites ou par de simples emprunts et citations, ces hommages sont autant de lectures que de relectures des chansons sélectionnées en abordant différents modes de jeux d’«  intertextualité musicale  ». Celle-ci se situe à deux niveaux  : le pôle de la production, qui montre que les chansons engagées de La Bolduc sont elles-mêmes le témoignage d’une époque  ; le pôle de la réception, pour exposer les résonances de ces chansons à partir de références autres et communes à la fois, comme la place des femmes dans la création musicale. Cette étude envisage ainsi la reprise à partir des aspects, des significations et des enjeux musicaux posés par l’intertextualité musicale, ici abordée sous l’angle de l’hommage alors conçu comme «  réactivateur  » de sens.
Keywords: concert / live / festival; féminité / masculinité / genre; intertextualité (musicale); politique / militantisme; reprise / pastiche / parodie; réception

Chansons fleuve suivi de Les lieux de l'intime dans "Arbre à fruits, arbre à fruits" de Marie-Jo Thério. Analyse narratologique et paralinguistique - Boucher, Mélanie (Université Laval, 2009)
Ce mémoire de création littéraire se divise en deux parties. La première propose une série de chansons intitulée Chansons Fleuve. Ce sont huit pièces créées autour de l'idée de l'intime, dont j'ai composé les paroles et la musique1. Elles ont été enregistrées sur un support audio qui accompagne la copie papier de ce mémoire. La seconde partie consiste en une analyse des rapports qu'entretiennent le texte et la musique d'"Arbre à fruits, arbre à fruits" de Marie-Jo Thério, avec l'intime. À travers les paroles de la pièce, les marques de l'intime sont présentes comme contenu (l'essence de l'intime, les thématiques) et comme forme (les relations, les situations, le temps, l'espace). Dans l'enregistrement de la voix et l'interprétation, sont véhiculées plusieurs émotions qui installent un climat d'intimité, appuient le texte et contribuent à rapprocher le public de l'artiste.

Chansons de travail, chansons de chômage : une lecture du monde ouvrier pendant la crise à travers l’œuvre de La Bolduc - Charest, Marie-Josée (Études littéraires, 2009)
In the 1930s, Mary Travers wrote folk songs dealing with the thorny issue of the working poor during hard times. A self-styled “woman at the service of the community”, she focused on those who lost their jobs as a result of the economic crisis. Heeding tradition, she lauded the work of famers whom she perceived as the mythical representatives of an idealised “old era”. How did she reconcile her songs praising tradition with an increasingly industrial labour market ? How did she react to women entering the workforce ? What did she think of government actions in the face of dwindling employment and pressing poverty ? Did she consider herself to be a career woman, what with hers being the first successful recordings of Quebec folk songs ? Confronting or buttressing established taboos such as those about women in the workforce, she wrote songs reflecting those societal issues prevalent at the time. Yet, she set herself apart both through her trade as a songwriter and her depiction of it. The economic situation in the province of Quebec influenced how labour was perceived, and her writings, favouring the standpoint of a working woman from the lower classes where employment is a matter of both survival and pride, echoed this perception with originality. A sociological and critical analysis of her songs illustrates the societal discourse on labour that prevailed during hard times.

Canadian Women Composers in Modernist Terrain: Violet Archer, Jean Coulthard and Barbara Pentland - Danielson, Janet (Circuit, 2009)
The successful compositional careers of Jean Coulthard, Barbara Pentland, and Violet Archer spanned all but the first three decades of the twentieth century. Entering a compositional career at this time had many challenges: as Western Canadians, these composers had to establish their credibility with a public that could not be counted on to recognize the worth of their work due to sexist bias and a prevailing critical stance: public approval was evidence of a lack of true creativity. This was especially problematic for women, who had to keep to the center of progressive composition, away from the experimental and conservative margins, in order to gain recognition. Following World War II, the pressure of modernism increased, due at least in part to initiatives by the U. S. Government in occupied Germany, countering the stereotype of the unsophisticated American with a new narrative of American experimental tradition.

Mots de tête - Dufresne, Diane (Éditions Michel Lafon, 2009)
J'écris c'qui m'chante , dit-elle. Et elle a bien raison ! Au lieu d'une biographie pompeuse, Diane Dufresne nous livre avec bonheur une vie en éclats. Écrivain, peintre, chanteuse : nous la retrouvons sous ses multiples facettes – l'existentialiste, la rockeuse, l'amoureuse impudique (sur scène) et la femme secrète, inattendue. Nous nous retrouvons aussi nous-mêmes, à travers les émotions que Diane exprime. Des pages magnifiques sur l'amitié, l'amour, la solitude... D'intimes confidences où resurgissent nos peurs : peur de l'inconnu, de la mort, du destin de la Terre et du nôtre. Et parmi toutes ces craintes un oubli capital : celui de savourer la vie. Pourquoi sentons-nous toujours qu'on a quelque chose à faire au lieu de quelque chose à vivre ? Avec ses splendeurs d'écriture, sa fantaisie, son humanité, son humilité, cette diseuse de belle aventure nous enchante et nous fait du bien.

The Piano Sonatas of Violet Archer: The Creative Influences of Bartók and Hindemith - Friesen, Darryl Shane (Université de l'Illinois à Urbana-Champaign, 2009)

Introduction : Compositrices sur la scène contemporaine - Goldman, Jonathan (Circuit: Musiques contemporaines, 2009)

Diane Dufresne : toute l'émotion du monde - Havard, Constance (Écouter la chanson, 2009)

Micheline Coulombe Saint-Marcoux et Marcelle Deschênes : pionnières dans le sentier de la création électroacoustique - Lefebvre, Marie-Thérèse (Circuit : musiques contemporaines, 2009)
A review of “masculine” and “feminine” attitudes towards music composition of the past fifty years highlights the contributions of Micheline Coulombe Saint-Marcoux and Marcelle Deschênes to the development of Québécois electroacoustic music. The author re-creates the historical context for the composers’ childhoods, adolescences, and periods of training in Montreal and Paris, and follows this with a discussion of how they negotiated the dominant trends of the 1970s. She then turns to the composers’ roles as pioneers: in their wish to depart from well-trodden paths, Coulombe Saint-Marcoux and Deschênes turned to new technological tools that would allow them to express a new artistic sensibility. From this perspective, they should be considered the “sherpas” of Québécois electroacoustic music.

Diane Dufresne, la diva de la chanson québécoise - Oberhuber, Andrea (BAT – Das Bulletin des Archivs für Textmusikforschung, 2009)

Des pratiques d’artistes et de chercheuses en écologie sonore - Piché, Claire (Recherches féministes, 2009)
This article is an incursion into the domain of sound ecology based on interdisciplinary research about artists and researchers. We expose the fundamental principles of sound ecology, a discipline that emerged during the seventies, and discuss the best practices of women in sound ecology, demonstrating how this constitutes a relevant research area for women’s studies. The link between feminism and sound ecology being established, we summarize three sociopolitically relevant research projects whose methods resemble feminist action research. We conclude by reflecting on the best means to foster interdisciplinary collaboration.

De la musique de geste à la musique du son, de SuperMémé à I8U - Prévost, Hélène (Circuit, 2009)
La musique actuelle née au tournant des années 1970-1980 a connu ses heures de gloire pendant de nombreuses années. Trois femmes font partie de la lancée et demeurent à ce jour des musiciennes actives et des administratrices hors pair. Mais d’autres, artistes sonores plutôt qu’instrumentistes, émergent, au moment du tournant technologique et plus particulièrement au milieu des années 1990. Un nombre important de ces femmes développent des pratiques non instrumentales d’art audio, de musique bruitiste, de musiques mixtes, électroniques expérimentales, d’installation et de multimédia. Elles sont mal connues, méconnues des grands médias et de la plupart des lieux d’enseignement de la musique, bien que plusieurs d’entre elles les aient fréquentés. Ce moment de rencontre avec certaines d’entre elles souhaite les faire apparaître, en plein jour.

Les femmes et la chanson au Québec : jalons d'une histoire et esquisses de perspectives - Savoie, Chantal (Écouter la chanson, 2009)

Interpreting success and failure: the eclectic careers of Eva and Juliette Gauthier - Slominska, Anita (Université McGill, 2009)
My dissertation explores the eclectic singing careers of sisters Eva and Juliette Gauthier. Born in Ottawa, Eva and Juliettte were aided in their musical aspirations by the patronage of Prime Minister Wilfred Laurier and his wife Lady Zoë. They both received classical vocal training in Europe. Eva spent four years in Java. She studied the local music, which later became incorporated into her concert repertoire in North America. She went on to become a leading interpreter of modern art song. Juliette became a performer of Canadian folk music in Canada, the United States and Europe, aiming to reproduce folk music “realistically” in a concert setting. My dissertation is the result of examining archival materials pertaining to their careers, combined with research into the various social and cultural worlds they traversed. Eva and Juliette’s careers are revealing of a period of transition in the arts and in social experience more generally. These transitions are related to the exploitation of non-Western people, uses of the “folk,” and the emergence of a cultural marketplace that was defined by a mixture of highbrow institutions and mass culture industries. My methodology draws from the sociology of art and cultural history, transposing Eva and Juliette Gauthier against the backdrop of the social, cultural and economic conditions that shaped their career trajectories and made them possible.

Tunes That Bind: Paul J. Seelig, Eva Gauthier, Charles T. Griffes, and the Javanese Other - Spiller, Henry (Journal of the Society for American Music, 2009)
The powerful concept of orientalism has undergone considerable refinement since Edward Said popularized the term with his eponymous book in 1978. Orientalism typically is presented as a totalizing process that creates polar oppositions between a dominating West and a subordinate East. U.S. orientalisms, however, reflect uniquely North American approaches to identity formation that include assimilating characteristics usually associated with the Other. This article explores the complex relationship among three individuals—U.S. composer Charles T. Griffes, Canadian singer Eva Gauthier, and German-trained Dutch East Indies composer Paul J. Seelig—and how they exploited the same Javanese songs to lend legitimacy to their individual artistic projects. A comparison of Griffes's and Seelig's settings of a West Javanese tune (“Kinanti”) provides an especially clear example of how contrasting approaches manifest different orientalisms. Whereas Griffes accompanied the melody with stock orientalist gestures to express his own fascination with the exotic, Seelig used chromatic harmonies and a chorale-like texture to ground the melody in the familiar, translating rather than representing its Otherness. The tunes that bind Griffes, Gauthier, and Seelig are only the raw materials from which they created their own unique orientalisms, each with its own sense of self and its own Javanese others.

La composition musicale et la marque du genre : l’examen conscient de l’« écriture féminine » - Stévance, Sophie (Circuit, 2009)
Si les spéculations idéologiques concernant les différences biologiques entre les sexes persistent dans le domaine de la création, elles ont été mises en valeur dès 1970 par des écrivaines et plasticiennes pour oeuvrer en fonction de mythes spécifiques touchant à leur féminité, au corps de la femme chargé de stigmates, afin qu’émerge un « art féminin ». D’une certaine manière, des compositrices vont emprunter cette voie en affirmant entretenir un rapport différent de celui des hommes à l’écriture musicale. Selon elles, leur sensibilité spécifique et leur situation d’être au monde les poussent à travailler autrement, à partir de thématiques « existentielles » inspirées de leur condition sociale et culturelle. De telles circonstances ont provoqué cette quête identitaire par l’invention d’un style artistique particulier qui, paradoxalement, use de ce qui était considéré par un féminisme radical comme les pièges de la féminité. Cet article tente de montrer que ces spécificités, du moins ces constantes relevées par les créatrices expliquant leur démarche, sont le résultat de recherches esthétiques pour caractériser une création universelle au féminin, et non le produit de diktats biologiques.

Réactiver le sens de l’hommage : L’exemple du Festival SuperMicMac au Canada - Stévance, Sophie (Itamar, 2009)
Cet article étudie la notion d’hommage à partir du Festival SuperMicMac organisé en 2000 par sept compositrices à la mémoire de Mary Travers (alias La Bolduc), icône de la musique populaire au Québec dans les années 1930. Par des allusions, des références précises et explicites ou par de simples emprunts et citations, ces hommages sont autant de lectures que de relectures des chansons sélectionnées en abordant différents modes de jeux d’« intertextualité musicale ». Celle-ci se situe à deux niveaux : le pôle de la production, qui montre que les chansons engagées de La Bolduc sont ellesmêmes le témoignage d’une époque ; le pôle de la réception, pour exposer les résonances de ces chansons à partir de références autres et communes à la fois, comme la place des femmes dans la création musicale. Cette étude envisage ainsi l’hommage à partir des aspects, des significations et des enjeux musicaux posés par l’intertextualité musicale. L’hommage est ainsi conçu comme un « réactivateur » de sens.

Isabelle Boulay - Bescos, Pierre-Alexandre (K&B, 2008)
La petite fille qui chantait debout sur un juke-box en Gaspésie pour divertir les clients du restaurant de ses parents a parcouru bien du chemin... De starmania à la country, en passant par la variété et la chanson réaliste, la carrière d'Isabelle Boulay est un fascinant mélange de styles et d'émotions. Sa voix, entre brisure et éclat, lui a assuré l'admiration et la collaboration des plus grands, de Francis Cabrel à Johnny Hallyday, en passant par Serge Lama, Julien Clerc ou Patrick Bruel. Entre le Canada et la France, cette artiste sincère et humble n'a jamais dévié de sa ligne directrice : trouver sa vérité profonde. Son nouvel album Nos lendemains, dépouillé et céleste, prouve une fois de plus l'immense talent d'Isabelle Boulay, qui demeure, au-delà des océans, une référence incontournable de la chanson. Cet Instant-Mag2 propose un entretien fleuve avec l'artiste, une biographie complète et détaillée, ainsi que des interviews de ses proches et/ou collaborateurs. Le tout illustré par de superbes photos en grand format. Un collector indispensable.

Colette Boky. Le chant d'une femme - Boky, Colette; Barrière, Mireille (Éditions Triptyque, 2008)
La présente biographie relate une carrière riche, autant à l'opéra qu'au concert et en récital. Le lecteur pénètre dans les coulisses parfois mystérieuses des maisons d'opéra. Colette Boky nous entretient de ses relations avec ses collègues, de sa conception des principaux rôles qu'elle a incarnés, de ses prestations devant maints personnages célèbres. Mais, plus encore, ces pages tracent le portrait d'une femme résolue, fonceuse, au franc parler, qui ne craint pas de mettre sa réputation au service de causes qui lui tiennent à coeur.

Francine-Brunel-Reeves : portrait d’une chercheuse atypique ou quand la pratique appelle la recherche... - Bolduc, Marc (Rabaska : revue d'ethnologie de l'Amérique française, 2008)
This article offers a portrait of Francine Brunel-Reeves, an independent researcher who has followed an exceptional course throughout her active life. It begins with a short biography of this artist, perfomer, educator and independant researcher who has split her life between France, Québec and the United States of America. The second section describes the current state of her work and the theoretical approaches that have delineated her research not only in the field of ethnology, but also in anthropology, musicology and mythology.

Nanette Workman. Rock'n romance - Bolduc, Mario (Éditions Libre Expression, 2008)
Issue d'une famille de musiciens, Nanette Workman chante sur scène - devant 300 personnes ! - dès l'âge de quatre ans. Le lieu : Jackson, dans le Mississippi. Suivront de nombreuses performances dans des pièces scolaires et des spectacles pour amateurs. Tout naturellement, Nanette s'inscrit en musique à l'Université de Southern Mississippi.Soudain, son univers bascule…En 1964, Nanette se retrouve sur Broadway dans une comédie musicale qui fera le tour des États-Unis. Elle rencontre alors Tony Roman, qui l'invite à partager la scène avec lui à l'occasion d'une tournée au Québec. Pour Tony, la jeune femme a le talent et les capacités pour entreprendre une carrière internationale. La chanteuse ne parle pas français, mais les Québécois l'adorent et l'adoptent ! Son séjour se prolonge… Nanette devient une vedette. S'installe entre elle et le public québécois une fidélité qui dure encore aujourd'hui.Mais la jeune Américaine a la bougeotte. On la retrouve en Grande-Bretagne, où elle travaille avec les Rolling Stones, Peter Frampton, John Lennon et plusieurs autres figures incontournables du rock britannique. Ensuite, elle part en France, où elle chante avec Johnny Hallyday et l'accompagne dans une tournée mondiale. Elle revient au Québec juste à temps pour enregistrer Lady Marmelade. D'autres succès s'ajouteront à cette liste…Tout au long de sa carrière, Nanette Workman a été le témoin privilégié de l'évolution de la musique populaire et l'une de ses dignes représentantes, ici et à l'étranger. Dans cette biographie, Nanette se livre sans retenue, avec chaleur et émotion, mais aussi avec beaucoup d'humour : ses échecs, ses succès, ses amours tumultueuses - avec Johnny Hallyday notamment -, sa descente dans l'enfer de la drogue, ses liens avec le crime organisé, la violence dont elle a été victime dans ses relations avec les hommes, sa fascination pour les armes à feu et le… bouddhisme, sans oublier l'accident tragique qui a failli lui coûter la vie.Au final, ce livre relate le parcours inusité mais palpitant d'une femme exceptionnelle, qui n'hésite pas à tout dévoiler…

Lhasa. La route chante - De Sela, Lhasa (Éditions Textuel, 2008)
La chanteuse mexicano-américaine Lhasa de Sela, également passionnée par la peinture, le dessin, la photographie et l'écriture, retrace son parcours et dévoile les lectures, les artistes et les pensées qui la nourrissent (Jung, Hugo, Géricault, Cat Stevens, etc). En 1998, la chanson la Llorona la fait connaître en Europe et au Québec.

"Eskimo chicks and word warriors": the creative cultural spaces of Elisapie Isaac and Taqralik Partridge - Foot, Johanna Maria (Université Carleton, 2008)

Les femmes et la vie culturelle à Québec avant la Révolution tranquille - Harvey, Fernand (Cap-aux-Diamants : la revue d'histoire du Québec, 2008)

Dykes on Mykes: Podcasting and the Activist Archive - Hogan, Mel (TOPIA: Canadian Journal of Cultural Studies, 2008)

Les représentations de la femme dans l'œuvre scénique de Diane Dufresne, 1975-1984 - Lafrenière, Marilyne (Université du Québec à Trois-Rivières, 2008)
Ce mémoire de maitrise vise a identifier les representations de la femme proposees par la chanteuse Diane Dufresne entre 1975 et 1984, afin de mettre en lumiere la contribution d'une artiste individuelle et officiellement non-engagée au discours public du Quebec de ces annees. Les deux dimensions de la communication - remission et la reception - y sont traitees et comparees. Une analyse thematique des paroles des chansons de Diane Dufresne, mise en relation avec differents aspects de ses mises en scene, nous ont permis de cerner l'univers de Partiste ainsi que les modeles feminins qu'elle propose. II s'agit de femmes solitaires, instables, sexuelles, sensuelles, parfois agressives et generalement apeurees face au monde dans lequel elles evoluent. Ainsi, les diverses origines du malaise existentiel des heroines - le quotidien lassant, la vitesse, le stress, les normes sociales, la vieillesse et la dictature de 1'image - sont autant d'entraves ressenties dans leur quete de liberte et de critiques adressees au monde contemporain. Leurs attaches sont d'ordre familial et professionnel. Les heroines embrassent egalement deux causes: la protection de Penvironnement et la liberte d'expression. Cette derniere - par la creativite qu'elle implique — est presentee comme un exutoire efficace au mal de vivre. Les heroines incarnees par Diane Dufresne s'inscrivent en marge des modeles generalement diffuses dans la chanson des decennies 1970 et 1980. L'etude de la presse culturelle quebecoise et des entrevues avec des fans de Partiste nous renseignent sur la reception de Diane Dufresne et de son oeuvre dans la societe ou elles sont diffusees. Etonnamment, les journalistes et les fans ne se sont pas averes etre des recepteurs si distincts. En effet, s'ils commentent parfois aprement la vie personnelle de Diane Dufresne, son comportement hors de la scene ou ses prises de position face a l'industrie, l'apparente fascination des journalistes en regard de l'art de Diane Dufresne les situe plus pres d'un public d'admirateurs que de la critique. C'est avec complaisance, sauf quelques rares exceptions, que les journalistes ont relaye 1'image que Diane Dufresne voulait donner d'elle-meme. Cette image est neanmoins incomplete puisque la douceur et la conscience sociale de Partiste y sont amenuisees par rapport aux autres dimensions de sa persona. Les journalistes culturels ont aussi contribue a creer une autre dimension au personnage public qu'est Diane Dufresne qu'ils associent a P emancipation feministe, alors qu'elle-meme refusait clairement cette etiquette. Alors que Paspect feministe est evacue du discours des fans, la force de Paffirmation de Diane Dufresne, voire son emancipation individuelle persiste et constitue un des piliers de leur attachement fidele et constant à l'artiste. Leur identification profonde a Diane Dufresne, la specificite qu'elle reconnait a chaque spectateur et Pinvitation qu'elle lance a chacun d'assumer sa difference lors de ses spectacles scelle le lien entre l'artiste et son public.

Une œuvre purement musicale ? Analyse de la spiritualité des Sœurs des Saints Noms de Jésus et de Marie à partir de l’exemple de l’École de musique Vincent-d’Indy - Laperle, Dominique (Études d'histoire religieuse, 2008)
L’École de musique Vincent-d’Indy des Soeurs des Saints Noms de Jésus et de Marie (connue avant 1951 sous le nom d’École supérieure de musique d’Outremont) fut considérée comme l’une des meilleures du genre dans la province de Québec. Cette réputation ne peut passer sous silence le fait qu’il s’agisse d’une institution catholique. Dans la vie scolaire quotidienne, quelle place occupait réellement la spiritualité ? En étudiant les Constitutions, le Coutumier, les programmes musicaux, les lettres circulaires et différents imprimés des religieuses, nous pouvons mieux identifier la spiritualité à laquelle se rattache cette communauté et comprendre comment elle l’a vécue et partagée.

L'identité culturelle dans « Montréal », d'Ariane Moffatt : une analyse musicale sémiologique - Laurier-Cromp, Mélanie (Université McGill, 2008)
La chanson « Montréal », d'Ariane Moffatt, a remporté un vif succès durant l'été 2006. Ce mémoire examine les causes de cette popularité. Après une revue des diverses méthodes existantes en recherche en musique populaire, trois types d'analyse se succèdent. En premier lieu, l'étude présentée ici décrit la chanson de manière théorique; on y observe le fonctionnement de la voix, de la mélodie, de la métrique, de la basse, des phrases, de la tonalité, des accords et des instruments utilises, images par une transcription précise de l'enregistrement de la chanson. Puis, le présent travail étudie les codes musicaux qui se retrouvent dans «Montréal». Dans cette deuxième section, le message musical du morceau est analysé, en tenant compte du contexte socioculturel de l'été 2006, de l'histoire nationale et musicale qui a précédé la sortie de cette pièce et des paroles de la chanson. Finalement, cette étude investigue la composante identitaire de «Montréal» en examinant les croyances nationalistes des Québécois, la place de la chanson dans l'imaginaire collectif de ce peuple, et la tradition musicale populaire de la province.

La faim Artaud. Le corps musical éclaté : à la recherche d'un langage musical inspiré d'Artaud - Llugdar, Analia (Université de Montréal, 2008)
Ce travail s'inscrit dans une rechcerche interdisciplinaire tendant à faire le point sur l'actualité de la pensée d'Antonin Artaud à travaers l'analyse du texte radiophonique Pour en finir avec le jugement de dieu. Ce texte conçu peu avant sa mort réunit tous les éléments propres à la pensée d'Artanud tant au niveau philosophique qu'au niveau formel: le corps sans organes, le concept de jugement, l'idée de dieu mais aussi les «sonorisations», les cris et les «glossolalies» à travers une étude profonde des différents textes d'Artaud ainsi que de ses dessins, de sa voix enregistrée, de ses mises en scènes et des différents aspects de son langage, j'ai élaboré une écriture musicale qui m'a permis de composer une oeuvre qui s'inscrit dans le domaine du théatre musical et qui se veut une lecture personnelle d'Artaud. Ainsi, les éléments de ce nouveau langage ont été incorporés aux oeuvres que j'ai composé postérieurement. Nous aborderons dans le chapitre 1 les sourecs nombreuses et hétéroclites du langage d'Artaud; la lecture de ses différentes manières d'expression artistique sont indispensables à la compréhension et à l'interprétation de sa pensée. Le chapitre 2 présente une analyse approfondie de la pièce résultat de ces recherche: La Faim d'Artaud, oeuvre de théatre musical pour sept instrumentistes, mezzo-soprano, baryton, un comédien et une bande pré-enregistrée. Cette analyse montre différents aspects du langage artaudien, présents dans la musique et dans les choix de mise en scène. Le dernier chapitre est une exemplification de l'influence qu'a exercée le langage développé à travers la composition de La Faim d'Artaud dans d'Autres oeuvres de mon répertoire. Pour démontrer cette influence, j'ai réalisé une analyse sommaire de la pièce Todos los recuerdos presentes envolvìan ese sonido y algo me miró pour orchestre de chambre de quinze instrumentistes.

The conservation of a gender fantasy: women and Top 40 radio in Montreal - Maki, Christine (Université McGill, 2008)
This work examines today's Anglophone Top 40 radio in Montreal in terms of gender. Looking at the history of commercial radio, and the historical relationship between radio and women, it argues that these radio stations have always programmed based on an imagined rather than actual understanding of their target audience. Programmers today continue to hold a conservative understanding of their female audience and their interests, and to program using a stereotypical understanding of gender.

Listening to/at/with Marilyn Lerner’s "They’re All in Families" - McNeilly, Kevin (Critical Studies in Improvisation / Études critiques en improvisation, 2008)
Marilyn Lerner’s audio-art composition “They’re All in Families” (1998) re-works a sound clip from a virulently homophobic message left on an answering machine, turning hate-speech back on itself to expose the rhythms and textures of verbal violence.

Le sacre du spectacle : Robert Charlebois et Diane Dufresne, deux cas de figure spectaculaires de la chanson québécoise - Oberhuber, Andrea (Quebec Studies, 2008)

« Un studio à soi ». Entrevue avec Bérengère Marin Dubuard, du Studio XX - Parent, Sylvie (ETC, 2008)
Un article de la revue ETC, diffusée par la plateforme Érudit.

L'émergence des chanteurs immigrants sur la scène de la musique populaire au Québec : l'exemple de Corneille et de Lynda Thalie - Proulx, Robert (Quebec Studies, 2008)
A l'instar des ecrivains de la litterature migrante, des chanteurs et des chanteuses venus de divers pays ont fait du Quebec leur port d'attache et le foyer de leur carriere artistique. Ce phenomene assez recent a fait qu'au cours des dix dernieres annees on a vu debarquer au Quebec des artistes d'Hai'ti, du Bresil, du Mexique, du Maroc, du Rwanda, du Tchad, de l'Algerie, et du Venezuela, chacun avec sa musique, sa couleur, et sa sensibilite propre. Dans cette nouvelle branche de la chanson quebecoise on trouve les themes de predilection de la litterature migrante tels que l'exil, la nostalgie, le sentiment de perte, l'adaptation a un nouveau pays, l'integration, le racisme, la xenophobie, et l'hospitalite. La chanson quebecoise s'enrichit de ces differents apports; car ces artistes apportent avec eux non seulement des voix, des sons et des styles musicaux nouveaux, mais aussi des themes inedits et des trames narratives originales qui refletent leur culture d'origine, leur passe, et leurs valeurs de meme que leurs emotions liees a leurs defis actueis et a leurs reves pour l'avenir. (1) Dans cet article, nous examinerons en detail l'ceuvre de deux d'entre eux: Lynda Thalie qui, selon Monique Giroux, l'experte en chanson francophone de Radio-Canada, "est, parmi les artistes neo-quebecois, celle qui a pris le plus de place et est la plus susceptible de conquerir un large public" (cite par Vignaux) et Corneille, celui qui a jusqu'a ce jour remporte le plus grand succes aussi bien commercial que d'estime. II a vendu plus d'un million et demi de ses deux premiers disques, et a lance son premier disque en anglais, "The Birth of Cornelius," au Japon en mai 2007. (2) Lynda Thalie: l'exilee d'Algerie

Lire Mary Travers (La Bolduc). Chansons et représentations sociales dans le Québec des années 1930 - Charest, Marie-Josée (Université de Montréal, 2007)
Ce mémoire de maîtrise intitulé Lire Mary Travers (La Bolduc). Chansons et représentations sociales dans le Québec des années 1930 a pour objet les dimensions sociales, historiques et idéologiques que les textes de La Bolduc prennent en écharpe et transforment. S'intéressant à la totalité des chansons écrites par Mary Travers entre 1927 et 1939, l'étude offre une analyse détaillée de la représentation de la société québécoise de l'entre-deux-guerres portée par son œuvre. C'est par le bais de l'analyse littéraire, de la cantologie et de la sociocritique que ces chansons humoristiques racontant la vie quotidienne et la misère des petites gens sont interprétées. Une attention particulière est portée au genre « chanson », à la narrativité, au registre linguistique, à l'humour, à la représentation des femmes et aux dérives idéologiques observées dans son répertoire. Par l'étude des chansons énumératives, des dialogues chantés et des autres ballades créées par Mary Travers, le mémoire rend compte de la mesure de l'inscription sociale de l'écriture de cette chansonnière et folkloriste populaire.

Three Canadian Sephardic Women and their Transplanted Repertories: From Salonica, Larache and Sarajevo to Montreal and Kahanawá:ke - Cohen, Judith R. (Folk Music, Traditional Music, Ethnomusicology: Canadian Perspectives Past and Present, 2007)

Culture, État et responsabilités : entretien avec Ana Sokolovic - Gendreau, Philippe (Liberté, 2007)

Keeping Time with Lesbians on Ecstasy - Halberstam, J[ack] (Women and Music: A Journal of Gender and Culture, 2007)

Itinéraire de quatre pionnières de la vie culturelle à Québec après 1945 - Harvey, Fernand (Les cahiers des dix, 2007)
À Québec comme partout ailleurs, la place des femmes dans la sphère publique est relativement récente. L’idée qu’une femme puisse poursuivre des études universitaires, travailler à l’extérieur de la maison ou entreprendre une carrière après le mariage a commencé à se généraliser peu avant les années 1960. Dans ce long cheminement, certaines femmes ont joué un rôle pionnier. Cet article examine le parcours de vie de quatre de ces femmes qui ont réussi à faire leur marque dans le milieu culturel et médiatique de la ville de Québec au cours des années qui ont suivi la seconde guerre mondiale : Francoise Larochelle-Roy, Simone Bussières, Georgette Lacroix et Monique Duval. L’itinéraire biographique de ces pionnières permet de mieux comprendre les singularités de leur insertion dans le milieu culturel et professionnel, en même temps que les points communs qui les relient toutes quatre au contexte d’une époque. On les suivra donc depuis l’enfance jusqu’à la vie adulte où elles évolueront dans l’enseignement, le journalisme, l’animation radiophonique, ainsi que dans le monde des lettres.

Kate and Anna McGarrigle: Songs and Stories - Lanken, Dane (Penumbra Press, 2007)

Récit d’une Beauceronne en Irlande ou la découverte de ‘l’irlandicité’ des Québécois - Matte, Isabelle (Cap-aux-Diamants, 2007)

Jeanne Maubourg (1875-1953) : l’apprentissage de la modernité théâtrale - Robert, Lucie (Jeu. Revue de théâtre, 2007)
Un article de la revue Jeu, diffusée par la plateforme Érudit.

Les voix des auteures-compositeures et interprètes populaires : une toile arc-en-ciel posée entre elles et nous - Tremblay, Danielle (Québec français, 2007)
Un article de la revue Québec français, diffusée par la plateforme Érudit.

Erika Mann et Pauline Julien : voix parallèles dans l'exil et l'engagement - Augustin, Myriam (Université McGill, 2006)

L’opéra pour enfants ou la quête d’identité : commentaire critique sur L’arche, d’Isabelle Panneton et Anne Hébert - Champagne, Éric (Circuit : musiques contemporaines, 2006)
Avant de rendre compte de l’opéra pour enfants L’arche (musique d’Isabelle Panneton, livret d’Anne Hébert), créé le 25 novembre 2004 par le Nouvel Ensemble Moderne et l’Atelier lyrique de l’Opéra de Montréal, cet article replace l’oeuvre dans un contexte plus large en esquissant un portrait de l’opéra pour enfants au XXe siècle. À travers diverses incarnations (parmi lesquelles l’opéra interprété par et pour des enfants), le genre est caractérisé par une durée limitée à moins d’une heure et un sujet spécifiquement destiné aux enfants, rendu aussi compréhensible que possible par un livret écrit dans la langue de son auditoire et porté par une musique claire et simple. Si ces caractéristiques ne vont pas sans soulever quelques questions, l’auteur estime qu’ils trouvent dans L’arche une illustration tout à fait réussie.

Thérèse Dion. La vie est un beau voyage - Germain, Georges-Hébert (Éditions Libre Expression, 2006)

Mais il n'a rien compris à ce que j'ai dit, celui-là! La chanson L'incompétence de Lynda Lemay - Gouvernec, Ludovic (FSU Frz, 2006)
La chanson « L'incompétence » de Lynda Lemay aborde avec humour les situations de communication gênantes du quotidien dans lesquelles on peut se retrouver, par exemple en faisant ses courses ou en allant au restaurant. Il est donc adapté - dans les cours de français à partir de la quatrième année - pour travailler des thèmes tels que les relations interpersonnelles, les différents registres de langue et la politesse. De plus, des aspects régionaux peuvent être abordés, l'accent étant mis sur les particularités géographiques et culturelles du Québec ainsi que sur les particularités dialectales du français qui y est parlé en raison des origines du chanteur. Après un examen détaillé du contenu de la chanson, divers exercices tels que l'invention d'un dialogue, un jeu de rôle et l'écriture d'un couplet de chanson sont proposés. Il y a des feuilles de travail et (à la page 95 du livret) le texte de la chanson, qui est également disponible sous forme de texte audio sur un CD qui peut être acheté avec le livret.
Keywords: Pas de lien web

Le son généreux [pour une hyper-écoute] - Laplante, Chantale (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2006)
L’article que l’artiste propose au lecteur relate le processus de transformation de sa pratique artistique durant une période particulière. L’artiste nous entretient de la transformation dans sa manière de composer la musique et de travailler avec le son. Elle développe sa réflexion autour de deux notions principales : l’hyper écoute qui favorise une approche intuitive, le son devenant la source première d’information à être transmué par la sensibilité de l’artiste, et l’espace-surface issu d’un temps musical non linéaire inscrit dans la durée. Tout au long de l’article, le lecteur prendra connaissance d’un contexte de travail précis qui a favorisé l’émergence d’un questionnement sur le processus de composition musicale et la relation avec le matériau en jeu, le son.

Alanis Obomsawin: The Vision of a Native Filmmaker - Lewis, Randolph (University of Nebraska Press, 2006)
In more than twenty powerful films, Abenaki filmmaker Alanis Obomsawin has waged a brilliant battle against the ignorance and stereotypes that Native Americans have long endured in cinema and television. In this book, the first devoted to any Native filmmaker, Obomsawin receives her due as the central figure in the development of indigenous media in North America.

The Importance of Community-Based Media for Building and Sustaining Lesbian Subcultures: The Role of Montréal’s Dykes on Mykes Radio Show - MacPhee, Marie-Claire; Hogan, Mél (Global Media Journal, 2006)
This paper was originally written for and presented at the Lesbian Lives XIII: Historicizing the Lesbian Conference in Dublin, Ireland in February 2006. The essay considers the history of Dykes on Mykes, a groundbreaking, lesbian and queer community-based radio program in Montréal, Canada. The authors, who are the show’s current hosts and technicians, collected data by examining the show’s archives and conducting individual and focus group interviews with Dykes on Mykes’ past and present hosts. These data reveal that changes in Dykes on Mykes’ programming and foci correlate closely with contemporary cultural and social developments among lesbian communities in Montréal.

The Role of Montréal’s Dykes on Mykes Radio Show - MacPhee, Marie-Claire; Hogan, Mél (Canadian Woman Studies, 2006)
Les auteures examinent le rôle historique, socio-politique de la programmation radiophonique montréalaise des années ‘20 alors que Dykes on Mykes, une émission qui a forgé et soutenu la sous-culture des lesbiennes et queers de la communauté anglophone de Montréal. Elles assurent que l’émission Dykes on Mykes a initié un courant alternatif à l’ordre établi en travaillant directement avec la communauté lesbienne et queer de Montréal et en contribuant à leur représentation positive dans les médias.

Gender, Genre and Electroacoustic Soundmaking Practices - McCartney, Andra (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2006)
This article is an exploration of how genres and practices of electroacoustic soundmaking are gendered, examining processes of gendering in language used in the early dichotomous categorization between musique concrète and elektronische Musik, then thinking about related arguments concerning abstraction, context, and compositional control in the writings of electroacoustic soundmakers including Pierre Schaeffer, Pierre Boulez, Daphne Oram, Pauline Oliveros, and several participants of the In and Out of the Sound Studio project. Analysis of their practices and ideas suggests different ways of conceptualising electroacoustic genres, their related practices, and roles of contemporary electroacoustic soundmakers (composers, artists, producers, mixers, audiences...), by examining the potentials of the concepts of empathetic knowledge and ecological thinking advanced by feminist epistemologist Lorraine Code.

In and Out of the Sound Studio: Introduction - McCartney, Andra; Waterman, Ellen (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2006)
Dans l’introduction à ce numéro spécial d’Intersections, Andra McCartney et Ellen Waterman présentent les Dedans et Dehors du Studio, un projet de recherche ethnographique inter-universitaire soutenu financièrement par le CRSH du Canada de 2001 à 2005. L’équipe de recherche a étudié les idées et pratiques des artisans sonores canadiens, se penchant particulièrement sur le sujet de la relative invisibilité et inaudibilité des femmes, réfléchissant aux différentes manières dont les technologies et pratiques sonores peuvent être orientées sexuellement. Dans leurs essais, les auteures discutent des relations trouvées entre les termes genre, son et technologie, du point de vue aussi bien terminologique, qu’esthétique, du mentorat, ou encore méthodologique et théorique. Les contributions de McCartney, Diamond, Laplante, Labrosse, Marsh et Bosma sont ici discutées.

Portrait d’Ana Sokolovic - Picard, Isabelle (Circuit : musiques contemporaines, 2006)
An article from Circuit, on Érudit.

Œuvres principales d’Ana Sokolovic - Picard, Isabelle (Circuit : musiques contemporaines, 2006)
An article from Circuit, on Érudit.

Au delà du sexe et de la technologie : les tendances du genre - Piché, Claire (eContact!, 2006)

Les préférences musicales des lectrices du Bulletin des agriculteurs, 1939-1955 - Savoie, Chantal (Communication. Information médias théories pratiques, 2006)
Au cours des vingt dernières années, plusieurs travaux s’intéressant à la chanson québécoise dans ses dimensions historiques ont contribué à renouveler notre perception du passé musical populaire québécois. Des ouvrages de référence, comme le Dictionnaire de la musique populaire au Québec (Thérien et D’Amours, 1992) et la numérisation de l’Encyclopédie de la musique au Canada (Kalmann, Potvin et Winters, 1993), sont venus baliser le domaine des études sur la chanson en rendant accessibles de ...
Keywords: chanson; femmes; goût musicaux; magazine

La alegría de hacer música contemporánea: entrevista con Lorraine Vaillancourt [La joie de faire de la musique contemporaine : entretien avec Lorraine Vaillancourt] - Stan, Luana (Doce notas preliminares, 2006)

Texte et musique dans le Journal d'Henriette Dessaulles, une disposition en abîme de type fractal - Vadean, Mirella (Université Concordia, 2006)
This master thesis aims to demonstrate that the personal diary, as a structure where several systems of signs can converge and seen from the point of view of evocation, can contribute to the structuring of a new hermeneutic figuration. For the purpose of this thesis, we analyze the limit of the literary fragment using the philosophical point of view of the Whole as a possible dynamic of restitution. Beyond this limit, we explore the emptiness that lays ahead, in the hope of, once again, recreating the Whole. References made to music (opera) throughout the diary, will be studied as a never ending "mise en abîme". We will use Lucien Dällenbach's methodology to detect and decode excerpts of Giuseppe Verdi's Trouvere and Richard Wagner's Rienzi within the diary. Throughout this thesis, we will suggest that textual and musical resonance between the word, the utterance and the code, allow for the creation of a system whose components are perpetually moving. For a better description of this system and in order to make the mechanism of sequences and resonance more clearly visible, we propose to consider this system as a fractal. This will enable us to constitute a system based on Henriette Dessaulles' diary (a "Dessaullien System"), a system erected using the science of fractals. The parameter of this system is the literary fragment, the unknown factor is the music and the interface is philosophy

Entretien avec Joane Hétu - Arroyas, Frédérique (Critical Studies in Improvisation / Études critiques en improvisation, 2005)

Y a-t-il des créatrices en musique au Québec ? - Carignan, Nicole; Leblanc (FAMEQ à la une, 2005)

Constructions of Identity in the Life Stories of Emma Albani and Glenn Gould - Elliott, Robin (Journal of Canadian Studies, 2005)
Biographical accounts of musicians have enjoyed widespread popularity since the late-Victorian era. Literary theory has recently held biography to be a literary construct, rather than a factual enterprise. Biographies and music are both governed by narrative structures and help to create a sense of individual and collective/national identity. Biographical accounts of two Canadian musicians—Emma Albani and Glenn Gould—are examined. Both musicians are Canadian national icons, but there are several problematic issues in their life stories: Albani’s elitism, class consciousness, and ambiguous relationship to Canada, and Gould’s eccentricity and uncertain sexual identity. The article examines how these issues have been handled in various auto/biographical accounts of the two musicians.

Chantal Dumas: a passion for listening and for studio art - Fenner, Victoria (Musicworks, 2005)

The Loudspeaker as Instrument: the soundworks of Nancy Tobin - Friz, Ann (Musicworks, 2005)

Violet Balestreri Archer (1913-2000) - Hartig, Linda (Music Reference Services Quarterly, 2005)
Violet Archer, one of Canada's well-known composers, passed away in 2000. This article is meant to add biographical information not previously available and to bring closure to her works list. Selected bibliographical citations are also included.
Keywords: Canadian composers; Violet Balestreri Archer

Radical Queers: A Pop Culture Assessment of Montréal's Anti-Capitalist Ass Pirates, the Panthères roses, and Lesbians on Ecstasy - Hogan, Mélanie (Canadian Woman Studies, 2005)
Cet article nous explique comment des artistes montréalaises queer radicales, Anti-Capitalists Ass Pirates, les Panthères roses et Lesbians on Ecstasy, ont transformé la sphère publique en intégrant politique et célébrations dans leurs importants messages à la population.

La contribution des femmes à l’histoire musicale et les compositrices d’aujourd’hui au Québec - Lefebvre, Marie-Thérèse (L'accès des femmes à l'expression musicale. Apprentissage, création, interprétation. Les musiciennes dans la société contemporaine, 2005)

C'était du spectacle! L'histoire des artistes transsexuelles à Montréal, 1955-1985 - Namaste, Viviane (McGill-Queen's University Press, 2005)
Le quartier chaud de Montréal a fait couler beaucoup d'encre, mais sa culture de cabaret n'a jamais été examinée dans la perspective des artistes transsexuelles et travesties qui l'ont rendu si populaire. Par le biais des récits provenant des danseuses elles-mêmes, Viviane Namaste peint un portrait honnête de quatorze transsexuelles - danseuses, chanteuses, magiciennes ou effeuilleuses - et jette un regard dans les coulisses du monde dans lequel vivent et travaillent ces hommes devenus femmes. Les années soixante et soixante-dix ont été des décennies de changement social au Québec. C'était du spectacle! raconte l'histoire de la première génération de transsexuelles ayant subi une chirurgie d'inversion de sexe. Namaste examine les conditions de travail dans les cabarets, la prostitution, les abus de pouvoir des policiers à l'égard des transsexuelles, le rôle du crime organisé dans la vie nocturne de la ville et l'accès aux soins de la santé. C'était du spectacle! offre un rare survol de la culture urbaine de Montréal, présenté dans ses propres mots par l'une de ses plus importantes communautés artistiques.

L’art de chanter… au féminin : de la prise de paroles au jeu de références postmodernes - Oberhuber, Andrea (L’accès des femmes à l’expression musicale. Apprentissage, création, interprétation : les musiciennes dans la cité, 2005)

La réception féminine de la chanson sentimentale populaire - Savoie, Chantal (Le féminin, le masculin et la musique populaire d'aujourd'hui. Actes de la journée du 4 mars 2003., 2005)

Briser le silence. Nathalie - Vastel, Michel (Éditions Libre Expression, 2005)
Un livre attendu, celui de Nathalie Simard, une jeune femme courageuse qui est devenue le symbole de toutes les femmes abusées, dont Michel Vastel signera l’histoire. Un témoignage touchant écrit par un journaliste d’envergure qui racontera l’histoire d’une femme, mais aussi celle de sa famille et de son entourage tout au long des années où elle a travaillé dans le monde du spectacle. Il y sera question de son enfance, son adolescence, jusqu’au dénouement médiatique de son histoire qui a éclaté dans les journaux en 2004 et en 2005.

La singulière pluralité de Marilyn Lerner - Denis, Dominique (Liaison, 2004)

Diane Leboeuf: from mixing boards to museums - Gasior, Lisa; McCartney, Andra (Musicworks, 2004)

Geneviève Gilardeau : le violon baroque et Jean-Marie Leclair - Melançon, Johanne (Liaison, 2004)

Étude sociologique de la musique actuelle du Québec : le cas des Productions Supermusique et du Festival International de Musique Actuelle de Victoriaville - Robineau, Anne (Université de Montréal, 2004)
Cette thèse a pour but l’étude sociologique de la musique actuelle au Québec. La musique actuelle est une pratique de création créée en dehors des institutions académiques et des centres de recherche. La professionnalisation de ce milieu artistique est décrite et analysée dans une perspective sociologique en prenant les cas des Productions Supermusique et du label DAME ainsi que du festival International de Musique Actuelle de Victoriaville. L’objectif de cette thèse est d’acquérir une connaissance sur la façon dont s’est développé ce milieu musical des années 70 à aujourd’hui.

Musique, femme et création musicale - Robineau, Anne (Dire, 2004)

Signé Louise - Forestier, Louise (Éditions du Boréal, 2003)

Les communautés féminines - Gallat-Morin, Élizabeth; Pinson, Jean-Pierre (La vie musicale en Nouvelle-France, 2003)

Analyse sociopoétique de la réception mitigée de deux œuvres de Clémence Desrochers : Le monde aime mieux... et Mon dernier show - Gauthier, Mélissa (Université Laval, 2003)

Violet Archer: Eine sozio-kulturelle Einordnung der Musik der kanadischen Komponistin unter besonderer Ber cksichtigung der Orchesterwerke [Violet Archer : une classification socioculturelle de la musique de la compositrice canadienne, avec une attention particulière à ses œuvres orchestrales] - Glathe, Kerstin (Université de la Ruhr à Bochum, 2003)
Keywords: Pas de lien web

Oralité et culture vocale inuit - Le Goff, Philippe (Revue DEMéter, 2003)

Creating and Contributing: The Expansive Spirit of Marcelle Deschênes - Mountain, Rosemary (Musicworks, 2003)

Maya Badian: Her Life and Her Music, A Privilege to Soar - Popovici, Fred (Editura Muzicalǎ, 2003)

Maryvonne Kendergi. La musique en partage - Bail, Louise (Éditions Hurtubise, 2002)

Considering Complexity in Canadian Civil Society: A Case Study of Studio XX - Gerlach, Neil; Hamilton, Sheryl (Revista Mexicana de Estudios Canadienses, 2002)

Virtually Civil: Studio XX, Feminist Voices, and Digital Technology in Canadian Civil Society - Gerlach, Neil; Hamilton, Sheryl N. (Civic Discourse and Cultural Politics in Canada, 2002)

Global Pop On The Move: The Fame of Céline Dion Within, Outside and Across Québec - Grenier, Line (Journal of Australian Canadian Studies, 2002)

Ma vie, je t'aime - Martel, Renée; Chapados, Dominique (Éditions Publistar, 2002)

New Games in the Digital Playground: Women Composers Learning and Teaching Electroacoustic Music - McCartney, Andra (Feminism & Psychology, 2002)

Les cahiers noirs de Lynda Lemay - Paquette, Claude (Éditions Contreforts, 2002)

Québec, vingtième siècle : La création musicale, une affaire de femmes ? - Galaise, Sophie (Musicanada 2000: A Celebration of Canadian Composers/Un hommage aux compositeurs canadiens, 2001)

Chansons de cours-nu-pieds - Miville-Deschênes, Monique (Éditions Triptyque, 2001)

Popularité, identité et internationalisation : les phénomènes Plamondon et Dion - Oberhuber, Andrea; Poulin, Richard (Les frontières improbables de la chanson, 2001)

L’homosexualité dans la chanson : du bout des lèvres - Perron, Gilles (Québec français, 2001)

Céline Dion, national unity and the English-language press in Canada - Young, David (Media, Culture & Society, 2001)
The national unity crisis in Canada deepened during the 1990s; it became increasingly likely that the French-speaking province of Quebec might separate from the rest of the country. This article examines how press coverage of Céline Dion, the popular francophone singer from Quebec, has intersected with the national unity debate. After providing some background on the debate and Dion, the article explores the linkages between them in Canada's English-language press. The analysis suggests the existence of a pro-unity frame in coverage of Dion. It also identifies how news stories about Dion have been shaped by binary oppositions, quoting practices and other journalistic techniques. The article concludes by noting some similarities and differences between coverage of political events in the national unity debate (such as referendums or constitutional accords) and coverage of Dion which is associated with the debate.
Keywords: Canadian,; Québécois; anglophone,; francophone,; music,; newspapers,; politics,

Les chants sacrés des Ursulines de Québec à l'époque de Marie Guyart - Courville, Louise (Marie Guyard de l’Incarnation. Un destin transocéanique (Tours, 1599-Québec, 1672), 2000)

Colloquy/Débat: Violet Archer, Jean Coulthard, and Barbara Pentland Remembered - Deaville, James (Canadian University Music Review, 2000)
In a bizarre coincidence, three important Canadian women composers from the same generation recently died within five weeks of each other: Barbara Pentland on 6 February 2000, Violet Archer on 22 February 2000, and Jean Coulthard on 9 March 2000. As a tribute to their lives and work, this colloquy gathers remembrances of them by friends and colleagues, ranging from brief anecdotes to extended memoirs. It is thus a collection of primary documents, which yield many new insights into the lives of our composers, ranging from personal habits to the way they taught composition.
Keywords: Canadian music; Careers; Composers; Composition; Music

Céline Dion. Ma vie, mon rêve - Dion, Céline; Germain, Georges-Hébert (Éditions Robert Laffont, 2000)
Enfant, j'avais deux rêves : devenir une star de la chanson, et connaître le grand amour, pour le meilleur et pour le pire, et pour toujours. J'ai eu beaucoup de chance...La chance de naître dans une famille de musiciens. Mes parents, mes treize frères et sœurs, à la maison tout le monde chantait ou jouait d'un instrument. Alors moi aussi je m'y suis mise très tôt, tout naturellement, et très vite je n'ai plus pensé qu'à ça : chanter. Je n'oublie jamais que c'est grâce à cette enfance heureuse et rieuse que j'ai pu devenir ce que je suis.Et puis la chance de rencontrer René Angélil, mon manager, mon pygmalion dans le monde du show business, mon amant, mon mari – l'homme de ma vie. Ensemble, nous avons fait des rencontres magnifiques, gravi toutes les marches du succès, traversé les plus dures épreuves. Et surtout bâti le grand amour de mes rêves de petite fille.À la veille de vivre notre bonheur le plus cher – la naissance de notre premier enfant –, j'ai eu envie de partager cette belle histoire. "Aujourd'hui, Céline Dion est une immense star. Son autobiographie lui ressemble : sincère et émouvante. Ses fans retrouveront celle qu'ils ont appris à connaître à travers les concerts, et les interviews. Mieux encore, ils découvriront l'intimité de celle qui se livre ici pour raconter ses passions, ses peurs, ses rêves...

Questions de renommée : les mises en mémoire du phénomène Céline Dion - Grenier, Line (Recherches féministes, 2000)
Dans cet article, l'auteure se penche sur le « phénomène Céline Dion » au Québec sous l'angle de la renommée. Au moyen de quelques fragments du discours qui a alimenté ce phénomène à la fin de la dernière décennie, l'auteure esquisse les contours de deux des figures concurrentes de la renommée que ce phénomène met en évidence : le « héros national » et l'« entrepreneur heureux ». Son analyse illustre comment ces figures de la renommée et les mises en mémoire auxquelles elles prêtent visibilité et valeur, lorsqu'elles sont en action dans la conjoncture québécoise contemporaine, opèrent une fusion, sinon une collusion entre la réussite individuelle et collective, entre l'intérêt personnel et national, et, par le fait même, rattachent différents ordres de matériel culturel au présent « passé » de certaines expériences privées, ressources locales et trajectoires publiques.

Le chant et la musique dans les maisons religieuses de femmes à l'époque de Marie Guyart - Hameline, Jean-Yves (Marie Guyard de l’Incarnation. Un destin transocéanique (Tours, 1599-Québec, 1672), 2000)

L’énigme de la correspondance d’Albani à Heugel - Langlois, Maryse (Les Cahiers de la Société québécoise de recherche en musique, 2000)

Quarante ans au cœur de l'Orchestre symphonique de Montréal - Lyse, Vézina (Varia, 2000)

Des cigales et des fourmis: histoire, actualité et informatisation de la chanson francophone de femmes. Bilan d'un projet de recherche - Oberhuber, Andrea (2000)
BAT – Das Bulletin des Archivs für Textmusikforschung

Les représentations sociales de l'enfant dans la chanson québécoise : l'exemple de Madame Bolduc et de Gilles Vigneault - Thivierge, Jacques (Université du Québec à Trois-Rivières, 2000)
Le présent mémoire porte sur les changements dans les représentations sociales de l'enfant, à l'intérieur du récit de la chanson québécoise. Le corpus de cette partie du discours culturel occupée par la chanson étant très vaste, nous avons limité notre recherche à l'étude des textes des chansons de Madame Bolduc et de Gilles Vigneault. Ces deux auteurs ont en commun le fait d'avoir amorcé leur carrière en des périodes particulièrement significatives de l'évolution de la société québécoise, soit la Crise de 1929 et la Révolution tranquille. Ces deux contextes socioéconomiques très typés nous ont permis d'aborder notre sujet de recherche dans une perspective diachronique. Au départ, nous posons l'hypothèse que l'enfant, représenté dans les chansons de Madame Bolduc, est un être que nous qualifions de subsumé, et que celui qui est représenté dans les chansons de Gilles Vigneault est un être que nous qualifions de sui generis. Pour faire la démonstration de cette hypothèse, notre mémoire se présente en deux grandes parties subdivisées en quatre chapitres. La première partie s'élabore autour des discours social et culturel et autour des rôles familiaux. Le premier chapitre aborde la chanson à travers les concepts de discours social, d'intertextualité , d'acceptabilité et de performance. On y retrouve aussi une mise en contexte des principaux artisans de la chanson québécoise ainsi que des outils de diffusion de cette chanson et ce, pour chacune des deux périodes étudiées. Dans le chapitre 2, en parlant des rôles familiaux et des relations parents/enfants, nous jetons un regard sur la famille et l'enfant au Québec. La deuxième partie de notre ouvrage s'intéresse directement aux chansons de Madame Bolduc et de Gilles Vigneault. Le chapitre 3 nous présente un panorama de la vie de Madame Bolduc ainsi qu'une analyse des représentations sociales de l'enfant et de la famille dans les textes de ses chansons. Cette présentation se répète au chapitre 4 mais , cette fois, relativement à Gilles Vigneault. Notre conclusion traite, dans une perspective diachronique, des changements dans les représentations sociales de l'enfant entre les chansons de Madame Bolduc et celles de Gilles Vigneault. Comme le soulevait notre hypothèse de départ, cette étude nous a permis de conclure que l'enfant, représenté dans les textes des chansons de Madame Bolduc, est un être subsumé et que, à l'opposé , les textes des chansons de Gilles Vigneault nous présentent un enfant sui generis.

Emma Albani - Vachon, Pierre (Éditions Lidec, 2000)
Biographie concise sur la carrière d'une illustre compatriote, Emma Lajeunesse dite Albani. Elle fut la première cantatrice québécoise à connaître une renommée internationale.

La carrière d’Emma Albani au Covent Garden de Londres - Vachon, Pierre (Les Cahiers de la Société québécoise de recherche en musique, 2000)

Sérieuse, audacieuse, bienheureuse... Généreuses! Rencontre avec Isabelle Panneton, Marie Pelletier et Ana Sokolovic - Davoine, Françoise (Circuit : musiques contemporaines, 1999)
In this exchange with three women composers, Françoise Davoine draws a portrait of their risks, anguish and preoccupations. The speaking-style of the text has been preserved here, giving freshness to the statements as each woman talks about her situation, and the creative process, etc.

Céline Dion et l'identité québécoise. « La petite fille de Charlemagne parmi les grands ! » - Demers, Frederic (VLB Éditeur, 1999)
Pourquoi Céline Dion est-elle une figure identitaire de premier plan aux yeux de la plupart des Québécois? Serait-ce parce qu'elle incarne l'équilibre qu'il recherchent désormais entre la préservation d'un héritage culturel particulier et l'ouverture à l'Autre sous le poids de la mondialisation et du métissage?

Pauline Julien. La vie à mort - Desjardins, Louise (Leméac, 1999)
La vie et la carrière de Pauline Julien sont un véritable roman. Née à Trois-Rivières en 1928, elle commence son parcours de comédienne à Québec et à Montréal avant de tenter sa chance à Paris où elle débute comme diseuse et chanteuse dans les boîtes à chansons de la rive gauche. Interprète de Bertolt Brecht, Boris Vian, Léo Ferré, elle côtoie Barbara, Ricet Barrier et Anne Sylvestre. Elle ajoute à son répertoire, au fil d'une carrière entre le Québec, la France, la Suisse et la Belgique, les chansons de Raymond Lévesque, Gilles Vigneault, Michel Tremblay, Réjean Ducharme, Félix Leclerc... Après son arrestation en octobre 1970, cette militante passionnée devient la figure de proue d'une nouvelle affirmation culturelle, politique et féminine du Québec. Sa vie publique d'interprète cachait une femme angoissée, passionnée d'écriture. Pauline Julien a légué ses carnets personnels, tenus pendant près de quarante ans, à Louise Desjardins qui les a utilisés pour écrire le parcours d'une femme marquante du Québec moderne, des plus attachantes aussi, une femme de cœur et de tête, une femme de parole à fleur de peau, libre, qui avait l'âme à la tendresse... Pauline Julien a mené sa vie tambour battant, emportée par son tempérament fougueux et sa voix si particulière, qui fait vibrer le cœur de toutes les générations.

Pretty in Punk: Girls' Gender Resistance in a Boys' Subculture - Leblanc, Lauraine (Rutgers University Press, 1999)
Pretty in Punk combines autobiography, interviews, and sophisticated analysis to create the first insider's examination of the ways punk girls resist gender roles and create strong identities.Why would an articulate, intelligent, thoughtful young women shave off most of her hair, dye the remainder green, shape it into a mohawk, and glue it onto her head? What attracts girls to male-dominated youth subcultures like the punk movement? What role does the subculture play in their perceptions of themselves, and in their self-esteem? How do girls reconcile a subcultural identity that is deliberately coded “masculine” with the demands of femininity?Research has focused on the ways media and cultural messages victimize young women, but little attention has been paid to the ways they resist these messages. In Pretty in Punk, Lauraine Leblanc examines what happens when girls ignore these cultural messages, parody ideas of beauty, and refuse to play the games of teenage femininity. She explores the origins and development of the punk subculture, the processes by which girls decide to “go punk,” patterns of resistance to gender norms, and tactics girls use to deal with violence and harassment.Pretty in Punk takes readers into the lives of girls living on the margins of contemporary culture. Drawing on interviews with 40 girls and women between the ages of 14-37, Leblanc examines the lives of her subjects, illuminating their forms of rebellion and survival. Pretty in Punk lets readers hear the voices of these women as they describe the ways their constructions of femininity—from black lipstick to slamdancing—allow them to reject damaging cultural messages and build strong identities. The price they pay for resisting femininity can be steep—girls tell of parental rejection, school expulsion, institutionalization, and harassment. Leblanc illuminates punk girls' resistance to adversity, their triumphs over tough challenges, and their work to create individual identities in a masculine world.
Keywords: Family & Relationships / Life Stages / Adolescence; Social Science / Popular Culture; Social Science / Women's Studies

Ana Sokolovic : entrevue avec Jean Lesage - Lesage, Jean (Présence de la musique québécoise. Vingt-deux portraits instantanés, 1999)

À propos de cinq œuvres symphoniques de Linda Bouchard - Nattiez, Jean-Jacques (Présence de la musique québécoise. Vingt-deux portraits instantanés, 1999)

Isabelle Panneton : à contretemps - Panneton, Isabelle (Présence de la musique québécoise. Vingt-deux portraits instantanés, 1999)

Estelle Lemire : portrait de l'artiste-compositeure - Provost, Serge (Présence de la musique québécoise. Vingt-deux portraits instantanés, 1999)

Maureen Forrester: Canada's Charming Contralto :a Biography for Young People - Roy, Lynette (Orchid Communications, 1999)

Linda Bouchard : la musique de Linda Bouchard - Tourigny, Maurice (Présence de la musique québécoise. Vingt-deux portraits instantanés, 1999)

Dr. Violet Balestreri Archer, Her Life, Her Vocal Literature, and Her Influence on Contemporary Canadian Music - Valente, Liana Elsie (Université de Caroline du Sud, 1999)
Keywords: Pas de lien web

Nanette - Workman, Nanette (Éditions Stanké, 1999)
La vie et la carrière de la chanteuse à travers des photos personnelles et d'archives, de sa naissance à 1995.

Céline Dion, the ADISQ Controversy, and the Anglophone Press in Canada - Young, David (Canadian Journal of Communication, 1999)
Abstract: ADISQ, the organization that honours excellence in the Quebec music industry, gave francophone singer Céline Dion an award for being the Anglophone Artist of the Year in 1990. At the ADISQ gala that year, which was televised live across Canada, Dion refused to accept the award. Dion's decision to not accept the award, and the statement she made when turning it down, became the basis for a controversy that received a great deal of coverage in Canada's anglophone press. This paper examines anglophone press coverage of the ADISQ controversy involving Dion. After outlining press coverage of Dion and ADISQ during the years prior to the controversy, the paper identifies how the controversy began and analyses the issues that dominated the coverage. The paper also examines follow-up coverage of the controversy; it identifies how subsequent news stories on Dion, including some that were written several years later, linked the controversy to other issues. Résumé: L'ADISQ, l'organisme qui reconnaît l'excellence dans l'industrie de la musique au Québec, accorda à la chanteuse francophone Céline Dion le prix du Meilleur Artiste anglophone de l'année 1990. Au gala de l'ADISQ cette année-là-qui fut télévisé en direct partout au Canada-Dion a refusé d'accepter le prix. Cette décision, ainsi que les commentaires que Dion a faites en refusant le prix, suscitèrent une controverse qui fit couler beaucoup d'encre dans la presse anglophone au Canada. Cet article examine comment la presse anglophone a couvert cette controverse de l'ADISQ impliquant Dion. Après avoir tracé les grandes lignes des reportages sur Dion et l'ADISQ dans les années précédant la controverse, cet article identifie comment la controverse commença et analyse les questions qui dominèrent dans la couverture de celle-ci. Cet article examine en outre la couverture suivant la controverse; il identifie comment des reportages ultérieurs sur Dion, y compris certains qui apparurent plusieurs années plus tard, associèrent la controverse à d'autres sujets.
Keywords: ADISQ; Anglophone press; Céline Dion; Journalism

Ginette Reno, l'hommage - Bertrand, Daniel (Les Éditions Stanké, 1998)
Album illustré évoquant la carrière et la vie de Ginette Reno, de ses débuts jusqu'à nos jours. [SDM].

L'histoire... des femmes - Fournier, Pierre (De lutte en turlutte. Une histoire du mouvement ouvrier québécois à travers ses chansons, 1998)

La marche des femmes - Fournier, Pierre (De lutte en turlutte. Une histoire du mouvement ouvrier québécois à travers ses chansons, 1998)

La victoire des Midinettes - Fournier, Pierre (De lutte en turlutte. Une histoire du mouvement ouvrier québécois à travers ses chansons, 1998)

Le mouvement féministe des années 1970 - Fournier, Pierre (De lutte en turlutte. Une histoire du mouvement ouvrier québécois à travers ses chansons, 1998)

Solidarité, mes frères et mes sœurs - Fournier, Pierre (De lutte en turlutte. Une histoire du mouvement ouvrier québécois à travers ses chansons, 1998)

Céline: The Authorized Biography - Germain, Georges-Hébert (Dundurn Press, 1998)
Simply entitled Céline, this is the long-awaited, authorized biography of Céline Dion, the rags-to-riches story of a woman who has become the leading recording artist in the world. First published in French in Quebec in December 1997, Céline has sold in excess of 120,000 copies in Quebec alone. A French-language edition will be released in France this fall, to coincide with the release of a new French album.

Il fut un temps où l'on se voyait beaucoup, suivi de Lettres africaines et de Tombeau de Suzanne Guité - Julien, Pauline (Lanctôt Éditeur, 1998)

Show Girls - Lam, Meilan (Office national du film du Canada, 1998)
Show Girls celebrates Montreal's swinging Black jazz scene from the 1920s to the 1960s, when the city was wide open. Three women who danced in the legendary Black clubs of the day - Rockhead's Paradise, The Terminal, Café St. Michel - share their unforgettable memories of life at the centre of one of the world's hottest jazz spots. From the Roaring Twenties, through the Second World War and on into the golden era of clubs in the fifties and sixities, Show Girls chronicles the lives of Bernice, Tina and Olga - mixing their memories with rarely seen footage of the era. Their stories are told against a backdrop of the fascinating social and political history that made Montreal a jazz and nightclub hotspot for decades. It is a story of song and dance, music and pride.

La contribution des femmes à l’histoire de la musique au Québec - Lefebvre, Marie-Thérèse (New Sound, 1998)
Lors d'un colloque international sur les femmes et la création musicale organise par I'Unesco en mars 1996, Mme Zaimont et Mme Ostleitner des Etats-Unis et de I'Autriche, ont démontré dans leur conférence respective à quel point la vie musicale des pays qu'elles représentent est encore puissamment dominée par les forces conservatrices et traditionnelles I'Autriche plie sous le poids d'un héritage musical ancestral alors que les Etats-Unis (et jusqu'a un certain point le Canada anglophone) vit actuellement au rythme des tendances politiques de droite. Plusieurs des acquis du mouvement féministe sont actuellement remis en question dans les milieux décisionnels et on ne peut que s'inquiéter de I' impact que pourraient avoir ces mouvements conservateurs sur la création musicale des femmes de ce pays. Mais dans ce même colloque, nous avons également pu entendre les propos de représentantes d'autres pays, je pense ici à la Corée, au Japon, à la Bolivie, à I'Uruguay où les femmes prennent une place de plus en plus importante dans le discours musical et dans la production artistique. De son côté, Le Québec, peut-être a cause de sa situation linguistique et culturelle minoritaire, a développé au cours de son histoire une vitalité artistique enviable et a été a I'avant-garde dans plusieurs domaines dont la création musicale. Le réseau de solidarité que les femmes ont bâti dans le milieu musical depuis quelques années et la place que les compositrices occupent aujourd'hui témoignent de cette vitalité.

“Outside in the Machine”: Institutional Experiences and Strategies of Canadian Women Electroacoustic Composers - McCartney, Andra (Ghosts in the Machine: Women and Cultural Policy in Canada and Australia, 1998)

The Solo Piano Music of Violet Archer: A Study of Selected Didactic Works - Willoughby, Angela Sue (Université d'État de Louisiane, 1998)

Céline - Germain, Georges-Hébert (Éditions Club Québec Loisirs, 1997)
Voici le portrait d'une femme libre, autonome, amoureuse, physiquement et mentalement saine et souple. Céline Dion est portée par une grande ambition, qui n'est pas celle des autres mais la sienne propre, et par ses rêves à elle, que son imprésario, l'homme de sa vie, René Angélil, l'aide à réaliser. L'histoire racontée ici est faite de multiples conquêtes, certaines longues et ardues, d'autres faciles ou imprévues. Certaines de ces conquêtes sont intimes, d'autres sont hautement spectaculaires et médiatisées.

Répertoire des œuvres des compositrices du Québec au XXe siècle - Labelle, Nicole (Centre de recherche en civilisation canadienne-française, 1997)

Emma Albani. La diva, la vedette mondiale - Labrèche-Larouche, Michelle (XYZ, 1997)
La vie de la célèbre cantatrice canadienne-française qui, au XIXe siècle, conquit l’Europe et l’Amérique et fut l’amie de la reine Victoria et de célèbres compositeurs tels Liszt et Brahms.

The flowers in your dustbin: Girls in the North American punk subcultures of the 1990s - Leblanc, Lauraine (Université Emory, 1997)
Girls in male-dominated youth subcultures confront ideologies of gender which remain largely invisible and often tacitly accepted in many women's everyday lives. Punk girls choose to construct their femininity within a highly male-dominated, "masculinist," context; girls are present in such youth subcultures, but the masculine definition of their norms problematizes their participation. Thus, punk girls struggle to accommodate female gender norms within subcultural identities which are deliberately coded as "masculine." Although young women in America encounter the norms of the female gender role on a daily basis, punk girls' negotiations between the norms of femininity and those of punk open these prescriptions to critical examination which they might not otherwise be accorded. In this dissertation, I explore accounts of punk girls' engagements with both mainstream and subcultural gender norms. In constructing this account of girls' lived experiences in the punk subculture, I rely primarily upon the phenomenology, or experiential narrative, of punk girls' everyday lives. I elicited these accounts within the context of conducting participant observation m the punk scenes of four North American cities (Atlanta, Montreal, New Orleans, and San Francisco) from 1993 to 1995, conducting ethnographic interviews with forty punk girls. In the following, I explore various facets of punk girls' engagements with gender norms, including punk girls' narratives of engagement with the subculture; the construction of punk as a discourse of masculinity; punk girls' stylistic, behavioral, and discursive reconstructions of femininity; punk girls' experiences of public harassment and sexual harassment, and their strategic responses to these. I argue that these girls use the punk subculture in order to carry out resistances to varied forms of gender oppression, thereby developing stronger self-concepts in the face of adversity.

Vicissitudes - Maidanik, Victoria (Université McGill, 1997)
Vicissitudes is a composition for orchestra with a duration of approximately 13$ sp prime$ 30$ sp{ prime prime}$. The main idea of the piece, the subdivision of the orchestra into small soloistic groups along with larger ensembles, was inspired by the principles of one of the Baroque forms, namely the Concerto Grosso.

À la manière des préludes non mesurés - Panneton, Isabelle (Circuit : musiques contemporaines, 1997)
Faisant état de l’influence sur elle du répertoire baroque, la compositrice montre quel rôle de modèle ont joué pour elle les préludes non mesurés de Rameau et Couperin, notamment dans son oeuvre Trait, Écart, Réparties. Elle en indique ensuite les prolongements dans quelques autres pièces.

La critique féministe étatsunienne en musique : pertinence en milieu francophone Québécois - Sabourin, Carmen (Canadian University Music Review / Revue de musique des universités canadiennes, 1997)

A Bosnian Sephardic Woman in Kahnewake, Quebec - Cohen, Judith R. (Canadian Woman Studies/Les cahiers de la femme, 1996)

Calme, étale, la mer berce un grand soleil fauve et Quel bruit fait l’arbre qui tombe dans un bois où il n’y a personne pour l’entendre ? - Hébert-Tremblay, Suzanne (Université de Montréal, 1996)

Le rapport inconnu. Quatorze femmes canadiennes dans le studio d'électroacoustique. Seconde partie : compositrices de Montréal et Waterloo - McCartney, Andra (Contact!, 1996)
Keywords: Pas de lien web

Albertine Morin-Labrecque : pionnière dans le domaine de la pédagogie musicale au Québec au XXe siècle - Simard, France (Études en musique des futur(e)s diplômé(e)s du Département de musique de l'Université du Québec à Montréal, 1996)

Commentaires sur Ambient V, Secret de polichinelle et Danga - Sokolovic, Ana (Université de Montréal, 1996)

Violet Balestreri Archer: Milestones of a Career (Canadian University Music Review / Revue de musique des universités canadiennes, 1995)
Un article de la revue Canadian University Music Review / Revue de musique des universités canadiennes, diffusée par la plateforme Érudit.

Musica E Poesia Nell’ Opera di Violet Archer [Musique et poésie dans l'œuvre de Violet Archer] - Calo, Francesca (Université de Rome « La Sapienza », 1995)
Keywords: Pas de lien web

Women's Roles in Judeo-Spanish Song Traditions - Cohen, Judith R.; Sacks, Maurie (Active Voices: Women in Jewish Culture, 1995)

The Composer's Voice: "What women can do" - Dalen, Brenda (Canadian University Music Review / Revue de musique des universités canadiennes, 1995)
In this interview, conducted on 18 August 1994, Violet Balestreri Archer revisits her past, recreating the experiences of her youth from the earliest days of her childhood in Como and Montreal to her graduation from Yale University in 1949 and sharing highly personal memories of her family, teachers, and friends. She recalls her first visit to Italy, her school years, her piano lessons, her early attempts at composition, her participation in the Montreal Women's Symphony, and her compositional studies with Douglas Clarke at McGill University, Béla Bartók in New York, and Paul Hindemith at Yale University. In listening to her story, we discover "who" she is and "how" she succeeded in establishing her compositional voice and in creating a space or "room" for herself in a profession traditionally dominated by men.

Sacred songs and arias by women composers: A survey of the literature and performer's analysis of selected works by Isabella Leonarda, Luise Reichardt, Ethel Smyth, Violet Archer, Margaret Bonds and Edith Borroff - Heape, Mary Willis (Séminaire théologique baptiste du Sud-Ouest, 1995)
This document is written in support of a recital of sacred songs and arias by women composers. It is divided into two sections: a survey of sacred music, specifically sacred arts songs and sacred arias from larger works, and a performer's analysis of selected works drawn from the research of the first part. The survey begins with the commercial printing of music around 1500 and extends to 1994. Countries from around the world are represented, some more broadly than others. Biographical information, when available, is given for each composer featured in the survey as well as some discussion of her general compositional style and output. Greater attention is given to the composer's sacred music, especially compositions that involve the solo voice. Composers who wrote very little sacred music for the solo voice are mentioned only briefly. The performer's analysis includes biographical information on each composer as well as a discussion of her general style, significant compositions, honors and awards and sphere of influence. In the analysis of the pieces, attention is focused on elements in the music that affect its performance. The selected works include Volo Jesum, a solo motet by Isabella Leonarda, "An Maria," "Stille der Andacht" and "Die Blume der Blumen," three art songs by Luise Reichardt, "Benedictus" from Mass in D by Ethel Smyth, Violet Archer's Three Biblical Songs, Five Spirituals by Margaret Bonds and Missa Patrinae Rerum Domini, a setting of the mass for solo voice by Edith Borroff. The appendices include work lists of the selected composers, IPA transcriptions of the pieces, a chronological listing of composers, and a copy of the program, program notes and lecture from the recital. An extensive bibliography is included.
Keywords: Archer; Bonds; Borroff; Communication and the arts; Edith; England; Ethel; Germany; Isabella; Leonarda; Luise; Margaret; Reichardt; Smyth; Social sciences; Violet

The emergence of a new reality for Quebec Women Composers - Lefebvre, Marie-Thérèse (With a Song in Her Heart: A Celebration of Canadian Women Composers, 1995)

Creating Worlds For Music To Exist: How Women Composers of Electroacoustic Music Make Place For Their Voices - McCartney, Andra (Université York, 1995)

Inventing Images: Constructing and Contesting Gender in Thinking about Electroacoustic Music - McCartney, Andra (Leonardo Music Journal, 1995)
The author explores symbolic imagery in the world of electroacoustic music, as presented in both popular music publications and the language of 14 Canadian women composers. While mainstream discourse uses imagery that emphasizes power and control, these composers use metaphors of painting, dancing, sustenance, addiction, wilderness, meetings, circuitry, curses, locks, boxes, blessings and desire to describe their work. This imagery suggests different ways for artists to think about their interaction with technology.

Whose Playground, Which Games and What Rules?: Women Composers in the Digital Playground - McCartney, Andra (International Composer Music Association, 1995)
Keywords: Pas de lien web

Le Classement des documents musicaux des archives des Ursulines de Québec : démarche archivistique et intérêt musicologique - Vézina-Demers, Micheline (Les Cahiers de l'ARMuQ, 1995)

Violet Archer's Formative Years: A Bibliographical Catalogue of Her Compositions, 1932–43 - Whittle, James (Canadian University Music Review / Revue de musique des universités canadiennes, 1995)
This chronological catalogue of Violet Archer's earliest completed compositions, including works written from 1932 to 1943, is based on manuscripts in her possession and on deposit at the University of Calgary Library, as well as published scores and reproductions of manuscripts in the University of Alberta Library and the libraries of the Canadian Music Centre. It provides the date of composition for each work and summarizes the supporting evidence, including dates found on manuscripts, the types of paper used, entries on lists of works compiled by the composer, and dates of first and early performances. Also included are the medium of performance of each work, a list of movements, the source of any text, and the location of scores and recordings.

Fleur d'Alys - Beaunoyer, Jean (Leméac Éditeur, 1994)
« L'histoire d'Alys Robi, la première grande star du Québec des années 1940, auteur d'un destin exceptionnel qui nous amène jusqu'aux portes du paradis hollywoodien avant de nous faire vivre par la suite, une chute qui ressemble à celle d'un ange.».

When Shirley Met Florence - Bezalel, Ronit (Office national du film du Canada, 1994)
Portrait intime de deux femmes juives au milieu de la soixantaine, l'une homosexuelle et l'autre hétérosexuelle, dont l'amour l'une pour l'autre et la musique qu'elles créent ensemble transcendent les différences. L'attachement de Florence pour Shirley défie toute catégorisation.

Diane Dufresne. Cendrillon kamikaze - Ducharme, André (Éditions Mnémosyne, 1994)
Pour le premier ouvrage de la collection ##Portraits d'artistes##, l'éditeur nous convie à une belle rencontre intime, avec Diane Dufresne, notre diva nationale. En fait, l'auteur ne tarit pas d'éloges pour cette femme hors du commun, qu'il qualifie "de plus grande chanteuse francophone du monde". A vrai dire, il est difficile d'en nommer une autre dont le parcours fut si grandiose.

Chanson québécoise et urbanité : quatre portraits. La Bolduc, Jean-Pierre Ferland, Beau Dommage et Luc de Larochellière - Saint-Louis, Chantal (Université Laval, 1994)
La chanson, comme toutes les formes d'expression, s'inspire largement de la quotidiennete, elle subit donc inevitablement l'influence de la realite urbaine qui, depuis le debut du XX$\sp{e}$ siecle, occupe une place preponderante dans la societe quebecoise. La ville est tout d'abord percue de facon negative par des gens qui se sont exiles de la campagne afin de pouvoir survivre; lentement, elle devient un espace essentiel dont on subit l'influence. Le but de ce memoire est de dresser, dans un premier temps, un portrait de l'evolution de la notion d'urbanite et des valeurs qui s'y rattachent dans la chanson quebecoise, puis, dans un deuxieme temps, de decrire le processus de modification de la perception de la ville dans l'imaginaire quebecois, des annees 1930 aux annees 1990.

Sierra norteña: The influence of Latin music on the French-Canadian popular song and dance scene, especially as reflected in the career of Alys Robi and the pedagogy of Maurice Lacasse-Morenoff - Sévigny, Jean-Pierre (Productions Juke-box, 1994)

Expressive Modes in the Judeo-Spanish Wedding Song - Anahory-Librowicz, Oro (New Horizons in Sephardic Studies, 1993)

The Music of the Songs: Musical Transcriptions and Commentary of the Songs Discussed by Oro Anahory-Librowicz "Expressive Modes in the Judeo-Spanish Wedding Song" - Cohen, Judith R. (New Horizons in Sephardic Studies, 1993)

Women and Judeo-Spanish Music - Cohen, Judith R. (Bridge, 1993)

Les dessous des Folles alliées. Un livre affriolant - Godbout, Lucie (Éditions du remue-ménage, 1993)

The Women’s Art Society of Montreal: A Century of Commitment to the Arts - Holowach-Amiot, Elaine (Musée McCord d'histoire canadienne, 1993)

La communication musicale à travers les femmes que j’ai connues - Kendergi, Maryvonne (Les Bâtisseuses de la Cité, 1993)

Existe-t-il une musique dite féministe ? - Lefebvre, Marie-Thérèse (Les Bâtisseuses de la Cité, 1993)

La musique composée au féminin - Martin-Kostajnsek, Sylvaine (Les Bâtisseuses de la Cité, 1993)

Y a-t-il une musique virile ? - Panneton, Isabelle (Les Bâtisseuses de la Cité, 1993)

L'importance des femmes dans la vie musicale montréalaise entre les deux guerres: mythe ou réalité ? - Paul, Hélène (Les Bâtisseuses de la Cité, 1993)

Le couple Maubourg-Roberval : un apport décisif à l’implantation de l’art lyrique à Montréal - Paul, Hélène (L'Annuaire théâtral. Revue québécoise d’études théâtrales, 1993)
Un article de la revue L'Annuaire théâtral, diffusée par la plateforme Érudit.

Madame Bolduc. Paroles et musiques - Remon, Lina (Guérin, 1993)
Madame Bolduc, Paroles et musiques. L'intégrale. Oui, cet ouvrage est plus que nécessaire pour raconter l'histoire musicale de cette Gaspésienne qui, avec sa musique à bouche, sa guimbarde, son humour, sa vivacité et sa turlute, a su conquérir le Québec et l'espace et le temps...

Les voies parallèles de Pauline Julien suivi de trente-deux chansons - Rheault, Michel (VLB Éditeur, 1993)

Les femmes dans l'industrie du disque et du spectacle au Québec depuis 1945 - Tremblay, Danielle (En avant la chanson!, 1993)
Recueil de textes sur différentes facettes de la chanson populaire au Québec et au Canada. Comprend un large éventail de pistes de recherche : une esquisse de l'historiographie de la chanson québécoise; un aperçu des fabricants de disques au Québec; la place des femmes dans l'industrie du disque et du spectacle; le statut social des artistes; ou encore, la figure emblématique que constitue Robert Paquette chez les Ontariens.

Archives of Emma Albani - Willis, Stephen C. (National Library News, 1993)

Canada 125. Cantate profane pour chœur et orchestre, analyse musicologique - Badian, Maya (Lucian Badian Editions, 1992)

Die Komponistin Violet Archer unter Berücksichtigung ihrer nationalen und internationalen Stellung im Musikleben [La compositrice Violet Archer au regard de sa position nationale et internationale dans la vie musicale] - Glathe, Kerstin (Université de Münster, 1992)

Le phénomène musical de La Bolduc : reflet d'un itinéraire socioculturel de la collectivité canadienne-française - Kilfoil, Charles Anthony (Université de Montréal, 1992)
Keywords: Pas de lien web

Alanis Obomsawin - Kivi, K. Linda (Canadian Women Making Music, 1992)

Marie-Claire Séguin - Kivi, K. Linda (Canadian Women Making Music, 1992)

Marie-Lynn Hammond - Kivi, K. Linda (Canadian Women Making Music, 1992)

Pauline Julien - Kivi, K. Linda (Canadian Women Making Music, 1992)

La Bolduc. Soixante-douze chansons populaires - Laframbroise, Philippe (VLB Éditeur, 1992)

La Bolduc. La vie de Mary Travers - Lonergan, David (Triptyque, 1992)
La vie de la célèbre chanteuse étudiée dans le contexte social de son temps. C'est toute la première moitié du 20e siècle qui revit à travers l'histoire de cette Gaspésienne, qui s'exile à Montréal à l'âge de 13 ans. C'est aussi une partie de l'histoire de la chanson populaire québécoise qui nous est relatée à travers le vécu de la Bolduc

The Creative Piano Constructions of Violet Archer - Parker, James Edward Kimura (Juilliard School, 1992)

Une histoire de la Bolduc. Légendes et turlutes - Day, Pierre (VLB Éditeur, 1991)
Cinquante ans après son décès, le nom de madame Bolduc demeure toujours présent dans la tête et dans le cœur des amateurs de la bonne chanson québécoise. Qui peut se vanter de connaitre la vraie nature de celle qu'on appelait familièrement La Bolduc et qui anima pendant des années les salles de spectacles, les fêtes et les soirées de chez nous? Tant de rumeurs ont circulé qu'elles sont devenues légendaires. Une chose est sûre, La Bolduc a su mener de front une double carrière: celle de musicienne et de chanteuse, et celle de mère de famille, innovant ainsi pour l'époque. Et elle a su capter et traduire en chansons - comme peu d'autres ont réussi à le faire - le climat politique et social du Québec d'alors, n'hésitant pas à caricaturer les mieux nantis pour prendre le parti des petites gens. L'auteur a consacré plus de six ans de sa vie à retracer les grandes lignes de la carrière artistique et de la vie familiale de cette figure légendaire de la chanson québécoise. Ce qu'il a découvert, c'est un beau roman d'amour, qu'il nous livre ici en primeur. Pierre Day est réalisateur à Radio-Canada.

Violet Archer: A Bio-Bibliography - Hartig, Linda (Greenwood Press, 1991)

La création musicale des femmes au Québec - Lefebvre, Marie-Thérèse (De mémoire de femmes, 1991)
Keywords: History and criticism; Music by women composers; Québec (Province); Women composers

Transit de Micheline Coulombe Saint-Marcoux : l’aboutissement du cheminement du créateur - Lévesque, Carole (Les Cahiers de l’ARMuQ, 1991)

Quel plain-chant pour la Nouvelle-France ? L'exemple des Ursulines - Pinson, Jean-Pierre (Canadian University Music Review, 1991)
S'il est une musique qui fut pratiquée en Nouvelle-France depuis les origines jusqu'au XXe siècle, ce fut bien celle du plain-chant1. Or, ce répertoire se présente comme un reflet souvent exact du plain-chant gallican, de son histoire et de sa pratique. Certes, il lui a fallu s'adapter aux lieux, aux populations et aux coutumes, mais sa répartition géographique, moins complexe qu'en France, et le nombre plus restreint d'institutions et de paroisses permettent une méthode d'approche à peu près contrôlable. Au cours de notre projet de recherche2, nous avons recueilli à travers le Québec des centaines de sources qui tracent un portrait riche de cette pratique. Mieux : au-delà du plain-chant lui-même c 'est en fait le chant baroque français qui s'est conservé longtemps ici, « sous cloche », dans un milieu très conservateur : ce chant de la Nouvelle-France est un beau cas de Performing practice. Parmi toutes les institutions visitées, les Ursulines de Québec et de Trois-Rivières3 constituent une excellente illustration de ce phénomène. Les sources conservées chez elles, classées dans l'annexe bibliographique, présentent une synthèse assez fidèle des sources demeurées en Nouvelle-France, contribuant ainsi à l'élaboration de ce portrait.

La question de l'identité dans l'écriture de Pauline Julien - Rheault, Michel (Université du Québec à Montréal, 1991)

The Odyssey of Dahlia Obadia: Morocco, Israel, Canada - Sawa, Suzanne Myers (Canadian Folk Music Journal, 1991)
Dahlia Obadia interprète les danses de la tradition du moyen orient. Pendant sa carrières, elle a rémarque qu’il existe des grandes différences entre les interprétations de cette tradition vue de l’intérier et de l’extérieur. L’auteur décrit la vie de Dahlia et explore les problèmes qu’elle a affrontes pendant sa quête de sa propre identité culturelle.

Sur les traces de Dina. Dina Bélanger, 1897-1929 - Boucher, Ghislaine (Les Religieuses de Jésus-Marie, 1990)

La formation professionnelle des filles dans les écoles supérieures de musique tenues par les religieuses, 1926-1960 - Mendez, Manon (Université de Sherbrooke, 1990)

La chanson écrite au féminin: de Madeleine de Verchères à Mitsou, 1730-1990 - Tremblay-Matte, Cécile (Trois guinées, 1990)
Histoire des femmes auteures-compositeures dans la chanson du Québec et au Canada français. Des débuts de la colonie à aujourd'hui, l'auteure retrace 409 créatrices et plus de 6600 chansons.
Keywords: History and criticism; Music by women composers; Québec; Québec (Province); Songs, French

Les chansonnières au Québec, 1960-76 - Tremblay-Matte, Cécile (Les Cahiers de l'ARMuQ, 1990)

"Ya salio de la mar": Judeo-Spanish Wedding Songs among Moroccan Jews in Canada - Cohen, Judith R. (Women and Music in Cross-Cultural Perspective, 1989)

Maureen Forrester. Au-delà du personnage. Un récit autobiographique - Forrester, Maureen; McDonald, Marci (Éditions Libre Expression, 1989)
Les petits et grands moments de la vie et de la carrière de l'artiste.

Les Ursulines et la musique - Gréroire-Reid, Claire; V. -Demers, Micheline (Cap-aux-Diamants : la revue d'histoire du Québec, 1989)

Népal. L'échappée belle - Julien, Pauline; Hébert, Denise (VLB Éditeur, 1989)

Analyse de la composition musicale Coulage - Pelletier, Marie (Université de Montréal, 1989)
Keywords: Pas de lien web

Histoire des femmes auteures-compositeures dans la chanson canadienne-française, 1730-1985 - Tremblay-Matte, Cécile (Université de Montréal, 1989)

The Morphology and Phonology of Katajjait (Inuit Throat Games) - Bagemihl, Bruce (Canadian Journal of Linguistics/Revue canadienne de linguistique, 1988)
A linguistic theory can be considered to have explanatory force if it may be extended to a body of facts considerably beyond the domain for which it was originally conceived. In general, the further the new domain is from the original, the greater the support that accrues to that theory. In this paper, a number of developments within current morphological and phonological theory will be utilized in the analysis of an extraordinary form of vocal behaviour, the katajjait (sg. katajjaq) or throat games of the Canadian Inuit. The result will be a revealing account of the structures of these katajjait, as well as a remarkable confirmation of principles of linguistic theory from a domain which has been hitherto unreported in the linguistic literature.

L’Abandon et Mosaïques : deux œuvres musicales, deux parcours - Carignan, Nicole (Université de Montréal, 1988)

Diane Dufresne en spectacle : I'impact de la gestualité - Chénier, Marie-Claude (Université de Montréal, 1988)
Keywords: Pas de lien web

Hommage à Micheline Coulombe Saint-Marcoux - Gagné, Mireille (Les Cahiers de l'ARMuQ, 1988)

Place aux femmes-compositeurs du Québec - Lefebvre, Marie-Thérèse (Les Cahiers de l'ARMuQ, 1988)

Pierrette Alarie et Léopold Simoneau. Deux voix, un art - Maheu, Renée (Éditions Libre Expression, 1988)

Emma Albani (1847-1930) - Potvin, Gilles (Les Cahiers de l'ARMuQ, 1988)

Notes on Violet Archer - Proctor, George A. (Musical Canada: Words and Music Honouring Helmut Kallmann, 1988)
Notes on Violet Archer was published in Musical Canada on page 188.

La création musicale chez les religieuses enseignantes de Montréal - Rhéaume, Claire (Cahiers de l'ARMuQ, 1988)

Éva Gauthier (1885-1958) : première cantatrice canadienne-française d’avant-garde - Turbide, Nadia (Les Cahiers de l'ARMuQ, 1988)

Entretien avec Louise Portal - Bélanger, Denis (Ciné-Bulles, 1987)

« Sursis», « Play room » [analyses] - Bertrand, Ginette (Université de Montréal, 1987)
Keywords: Pas de lien web

Music consumption among English speaking teenage girls in the city of Montreal - Giles, Jennifer (Université Carleton, 1987)
Music Consumption among English Speaking Teenage Girls in the City of Montreal

Exposition au monastère des Ursulines de Québec - Grégoire-Reid, Claire; Vézina-Demers, Micheline (Les Cahiers de l'ARMuQ, 1987)

Les femmes compositeurs au Canada : données sociologiques et historiques - Kidd, Roseanne (Sonances, 1987)

L'implication sociale et créatrice de Micheline Coulombe Saint-Marcoux - Lévesque, Carole (Université McGill, 1987)

Nathalie Simard, vedette de la chanson pour enfants au Québec et Passe-Partout, l’autre vedette - Poulin, Manon (La chanson dans tous ses états, 1987)

La création musicale chez les religieuses de trois communautés montréalaises - Rhéaume, Claire (Université de Montréal, 1987)

Aimer Clémence ou se voir différent - D'Amours, Réal (La chanson en question(s), 1986)

Out of Character - Forrester, Maureen; McDonald, Marci (McClelland & Stewart Publishing, 1986)

Jeunes femmes et « contre-culture » au Québec - Lamont, Ève (Les Cahiers du Grif, 1986)

Biographical Study of Eva Gauthier (1885–1958): First French-Canadian Singer of the Avant-Garde - Turbide, Nadia (Université de Montréal, 1986)

Muséalogue : Maryvonne Kendergi - Bail Milot, Louise (Les Cahiers de l'ARMuQ, 1985)
Muséalogue : Maryvonne Kendergi

Clémence Desrochers et l'imaginaire social de l'Estrie - Gaulin, André (La chanson en question(s), 1985)

Ginette Reno. L'histoire d'une superstar - Cellier, Gérard (Éditions Québécor, 1984)

Au-delà du mur du son, l’univers consonant et dissonant d’Anne Lauber - Cloutier, Diane (La Scène musicale, 1984)

La musique de salon au Québec (1880-1915) - Geoffrion, Diane (Les Cahiers de l'ARMuQ, 1984)

Écrire un théâtre musical. Transit. Entretien avec Micheline Coulombe Saint-Marcoux et France Théoret - Jonassaint, Jean (Dérives, 1984)

Emma Albani: Victorian Diva - MacDonald, Cheryl (Dundurn Press, 1984)
Talented Emma Albani was a favourite of Queen Victoria, singing at Victoria's funeral as well as Edward VII's coronation, and for many other heads of state from Russia, Austria, France, Italy, Belgium, Denmark, United States and Canada. Sir Arthur Sullivan, Gounod, Von Flotow and Dvorak wrotemusic for her and she sang with Nellie Melba, Adelina Patti, Jean de Reszke, Francesco Tamagno among others. Emma, who married Ernest Gye, manager of Covent Garden, was celebrated as one of the leading operatic and oratorio sopranos of the century. Emma (Lajeunesse) Albani, one of Canada's first internationally known performers, began as a student singing in a Chambly, Quebec convent and an Albany, New York church. From her opera debut in April 1870 in Sicily to her farewell concert in October 1911 in London, England, she was loved for her voice as well as her kindness, which was rare in a prima donna. She was adored by fans world-wide as George Bernard Shaw recorded in 1889," ... people were standing two and three deep behind the chairs ..., consisting of prima donna worshippers who are bent on obtaining a bird's eye view of Madam Albani.

Renaissance. Un récit bouleversant de sa lutte contre l'alcoolisme - Martel, Renée; Nantel, Linda (Presses libres, 1984)

Musique inuit au Québec arctique : contribution à une méthode d'analyse en anthropologie de la musique - Montpetit, Carmen; Veillet, Céline (Les Cahiers de l'ARMuQ, 1984)

Fabienne Thibeault... Cœur voyageur - Portelli, Rose-Marie (Éditions Plasma, 1984)

Diane Dufresne. Sa vie, ses amours, sa carrière, ses spectacles - Racine, Gaëtan (Éditions Québécor, 1984)
Femme aux milles visages, aussi excentrique que Boy George, Diane Dufresne est devenue en quelques années une véritable superstar qui compte des milliers d'admirateurs. Ce livre passionnant raconte sa vie: son enfance difficile, ses débuts de chanteuse, ses voyages, ses amours et son ascension fulgurante vers la gloire.

René et Nathalie Simard. Les enfants chéris du showbiz - Bachand, Danielle; Bachand, Claudine (Éditions Québecor, 1983)

Dina Bélanger, Marie Sainte-Cécile-de-Rome, 1897-1929. Itinéraire spirituel - Boucher, Ghislaine (Éditions Paulines, 1983)

La musique de salon au Québec (1880-1915) - Geoffrion, Diane (Université de Montréal, 1983)

Mon enfance à Rosemont - Leyrac, Monique (Éditions Primeur, 1983)

The Rekkukara of the Ainu (Japan) and the Katajjaq of the Inuit (Canada): A Comparison - Nattiez, Jean-Jacques (The World of Music, 1983)

C'était la plus jolie des filles. Répertoire des chansons d'Angélina Paradis-Fraser - Deschênes, Donald (Quinze, 1982)
La parution d'un recueil consacré tout entier au répertoire d'une chanson traditionnelle constitue une première dans l'édition de la chanson populaire d'ici. Doanld Deschênes nous présente quatre-vingt-dix des plus belles chansons de la gaspésienne Angelina Paradis-Fraser, venant de la mémoire des temps. Les lecteurs dégusteront toute l'atmosphère chaude et accueillante dont ces chansons ont pu s'imprégner, avec un petit arrière-goût de golfe et de sapin et le mûrissement que trois cents ans en sol québécois et acadien ont pu leur conférer.

Une missionnaire de la musique : Sœur Marie-Stéphane, S.N.J.M. fondatrice de l'école Vincent-D'Indy - Millette, Juliette (Cahier de la Société historique de Montréal, 1982)

Éva Gauthier. De Java au Jazz - Turbide, Nadia (Aria, 1982)

Clémence Desrochers : humour et solitude - Lacoursière, Yvan (Université du Québec à Trois-Rivières, 1981)

Kate and Anna McGarrigle - Leaf, Caroline (Office national du film du Canada, 1981)

Né homme, comment je suis devenu femme - Martel, Brigitte (Québécor, 1981)
Dans « Né homme, comment je suis devenu femme », vous découvrirez une des histoires les plus surprenantes du Show-business québécois, Sans fausse honte, avec une franchise que plusieurs trouveront choquante, le jeune prodige de la chanson, Jacques Bélanger, qui créa le phénoménal succès de « Maman, la plus belle du monde », raconte comment, il est devenu une femme véritable. À travers un récit émouvant, il relate sa jeunesse difficile, les débuts de sa carrière, ses aventures homosexuelles, ses expérience avec la drogue, et, enfin, le grand drame de sa vie : celui de se sentir femme, pleinement femme, mais d'être né dans un corps d'homme. Cet « accident de la nature », il finira par le corriger, à force de courage et de persévérance, envers et contre tous, par une série d'opérations chirurgicales dont il ne nous épargne aucun détail. La métamorphose une fois accomplie, Jacques Bélanger, devenu Brigitte Martel, a réalisé son plus grand rêve en épousant l'homme de sa vie.

Angèle Arsenault - Normand, Pascal (La chanson québécoise. Miroir d’un peuple, 1981)
Keywords: Entretien

Diane Juster - Normand, Pascal (La chanson québécoise. Miroir d’un peuple, 1981)
Keywords: Entretien

Diane Tell - Normand, Pascal (La chanson québécoise. Miroir d’un peuple, 1981)
Keywords: Entretien

Fabienne Thibeault - Normand, Pascal (La chanson québécoise. Miroir d’un peuple, 1981)
Keywords: Entretien

The Motet in New France: Some 17 th and 18 th Century Manuscripts in Quebec - Schwandt, Erich (Fontes Artis Musicae, 1981)

The Choral Music of Violet Archer - Don Huiner, Harvey (Université d'Iowa, 1980)

Chanson de madame Édouard Bolduc (née Mary Travers) - Gaulin, André (Dictionnaire des œuvres littéraires du Québec, 1980)

Violet B. Archer : une élève canadienne de Bela Bartok - Lenoir, Yves (Institut supérieur d'archeologie et d'histoire de l'art, Université catholique de Louvain, 1980)

Alys Robi. Ma carrière et ma vie - Robi, Alys (Éditions Québécor, 1980)
Dans son émouvante autoblographie, Alys Robi, la première véritable STAR du Québec, raconte, avec une sincérité boulever- sante, l'histoire prodigieuse de sa carrière. Une carrière qui débuta fort précocement alors qu'elle avait a peine quatre ans et qui lui permit rapidement de se hisser au rang des vedettes internationales à une époque où le "show business" quebécois en était encore à ses balbutiements. A vingt ans, en effet, déjà adulée, Alys Robi chante dans les plus grandes capitales du monde: Paris. Londres, Buenos Aires ... Hollywood lui ouvre ses portes. Elle vit comme une princesse, touche des cachets astronomiques, habite les plus grands hotels, recoit les célebrites du monde entier. Parallelement elle decouvre l'amour: une passion très tendre la lie au célèbre Olivier Guimond. Mais son livre ne raconte pas seulement les heures glorieuses, il évoque aussi les heures sombres. Les heures où ses plus beaux rêves s'effondrerent, où elle découvrit la précarité du succès, les désillusions de l'amour et de l'amitié, et surtout, le monde halluci- nant de la folie. Son livre lève en effet le voile sur une des périodes les plus sombres de sa vie: le cauchemar de cinq ans qu'elle vécut à Saint-Michel-Archange, parmi les aliénés. Un cauchemar au cours duquel sa fortune sera "mystérieusement" dilapidée et dont elle sortira marquée à jamais pour affronter une épreuve nouvelle: celle d'un mariage dont l'échec retentissant l'ébranlera à nouveau. Dans, ma carrière et ma vie, ce n'est pas seulement le portrait émouvant d'une vie qui est tracé, c'est aussi celui de toute une époque, la 'belle époque" du "show business" québecois diront certains, celle, surtout, du fameux cabaret La Casa Loma où le Tout-Montreal se donnait rendez-vous.

Le monde de la chanson. Comment quatre femmes ont pris place dans l'industrie du disque - Lemay, Jacqueline (Canadian Woman Studies, 1979)

Fabienne Thibeault - Pedneault, Hélène (Éditions de l'Aurore, 1979)
Keywords: Pas de lien web

Une Canadienne à Moscou en 1873 - Potvin, Gilles (Bulletin du Centre de recherche en civilisation canadienne-française de l'Université d'Ottawa, 1979)

The Montreal Women's Symphony - Rooney, Frances (Atlantis, 1979)

Le katajjaq : un jeu inuit traditionnel - Beaudry, Nicole (Études Inuit Studies, 1978)
Katajjaq, a traditional Inuit game Katajjait — the traditional Inuit throat-games — display unusual musical properties and for that reason they have been submitted to extensive musicological analysis. Furthermore, they also constitute a particularly rich example of traditional Inuit game behaviour. The present article aims at backing that statement through an analysis of Inuit games from Central Arctic, based on available written information¹.This analysis enables us to define the katajjaq not only in terms of formal properties, but also in terms of social functions. This analytical definition is achieved by comparing katajjaq with some of the Inuit game mechanisms. le katajjaq, un jeu inuit traditionnel Le katajjaq ou jeu de gorge inuit à l'origine lointaine, se caractérise par des propriétés musicales exceptionnelles. Ce jeu vocal a donc fait l'objet d'analyses musicologiques approfondies. Par ailleurs, il illustre particulièrement bien le système ludique inuit traditionnel. Nous cherchons ici à confirmer cette hypothèse, à la suite d'une étude par les textes¹ sur les jeux inuit de l'Arctique central en général. A la lumière de cette étude, nous tâchons de définir le jeu de gorge, tant par ses fonctions sociales que par son comportement formel et ce, en comparaison avec quelques mécanismes des jeux inuit traditionnels.

Toward Transcription and Analysis of Inuit Throat-Games: Micro-Structure - Charron, Claude (Ethnomusicology, 1978)

Entre cri et chant. Les katajjait, un genre musical féminin - Saladin d'Anglure, Bernard (Études/Inuit/Studies, 1978)
The growing popularity in the West of various graphic or plastic expressions of contemporary (or prehistoric) Inuit art has overshadowed other aspects of Inuit art — particularly traditional music, within which throat games represent a most fascinating genre. Indeed, some of the first western travelers who attended a katajjaq performance were to pay a high price to have their curiosity satisfied — as we shall see in the following documents. The anthropologist cannot escape this fascination either, for the katajjait constitute a complex and ambiguous genre, belonging to cry and language, song and dance, game and music, ritual and performance, expressing Inuit symbolism on the relationship between man and woman, the relationship to nature and the supernatural and reflecting elements of the social structure since the performance of katajjait requires cooperation and sometimes gives rise to competition between performers. Le succès croissant en occident des différentes expressions graphiques ou plastiques de l'art inuit contemporain (ou préhistorique) a masqué d'autres aspects de l'art inuit, en particulier l'art musical traditionnel au sein duquel les jeux de gorge (notamment les katajjait) constituent un genre fascinant. Plusieurs des premiers voyageurs occidentaux qui y assistèrent en firent l'expérience à leurs dépens comme nous le verrons dans les documents qui suivent. Genre fascinant aussi pour l'anthropologue en raison de sa complexité et de son ambiguïté qui le font relever à la fois du cri et du langage, du chant et de la danse, du jeu et de la musique, du rite et de la performance; en raison également et de sa dimension symbolique lorsqu'il traite du rapport à la nature, du rapport au surnaturel et du rapport homme-femme, et de sa dimension sociologique à travers la coopération nécessitée par son exécution et la compétition parfois organisée entre les exécutants.

Recherches en ethnomusicologie: les katajjait chez les Inuit du Nouveau-Québec - Montpetit, Carmen; Veillet, Céline (Études/Inuit/Studies, 1977)

Diane Dufresne - Racicot, Hélène; Taschereau, Yves; Lessard, Jean-Guy; Lignères, Claude (Éditions de l'Aurore, 1976)

Pauline Donalda: The Life and Career of a Canadian Prima Donna - Brotman, Ruth C. (Eagle Publishing, 1975)
Pauline Donalda (1882-1970) was born Pauline Lightstone in Montreal. She adopted the name "Donalda" after her benefactor, Donald Smith, Lord Strathcona. She studied music at Montreal's Royal Victoria College and in Paris, and made her opera debut in 1904 in Nice, France. In 1922 she opened a studio in Paris and became a teacher, and in 1937 she returned to Montreal where she opened a studio. In 1942 she founded the Opera Guild of Montreal. She served as President and Artistic Director of the Guild until 1969.

La moitié du monde est une femme - Lemay, Jacqueline (Leméac Éditeur, 1975)

L'enseignement de la musique vocale et instrumentale aux Ursulines de Québec de 1830 à 1880 - Pagé, Thérèse (Université Laval, 1975)

Pauline Julien. Choix de textes. Discographie, portraits - Calvet, Louis-Jean (Éditions Seghers, 1974)

Les chansons de "La Bolduc" : manifestations de la culture populaire à Montréal (1928-1940) - Leclerc, Monique (Université McGill, 1974)
Dans cette étude, nous considérons le répertoire de madame Bolduc comme manifestation culturelle soumise à une dynamique historique, dotée d'un sens global à travers lequel on peut déceler les éléments originaux de l'identification d'un groupe social. Au premier chapitre, les chansons sont définies en tant que manifestation du folklore urbain afin d'en déterminer l'aire culturelle et le potentiel collectif. Le deuxième chapitre offre un inventaire thématique des chansons et le troisième chapitre aborde l'analyse de l'univers culturel des chansons. C'est à ce niveau que s'établit l'état de congruence entre les valeurs véhiculées dans les chansons et les conditions de vie imposées aux classes populaire dans les années '30.

Mémoires d’Emma Albani. L’éblouissante carrière de la plus grande cantatrice québécoise - Albani, Emma (Éditions du Jour,, 1972)

Juliette Béliveau - Martineau, Denise (Montréal : Éditions de l'Homme, 1970)

Madame Édouard Bolduc et ses chansons - Doyon, Marie-Blanche (Université Laval, 1969)
Keywords: Pas de lien web

L'histoire de la musique de l'Institut des Sœurs de la Charité de Québec - Roy, Marielle (Université Laval, 1968)

La Bolduc. Sa carrière fulgurante, sa vie courageuse, ses chansons canailles - Benoît, Réal (Éditions de l'Homme, 1959)
Pourquoi publier un livre consacré à Madame Bolduc? D'abord parce que tout ce qui est humain intéresse les Éditions de l'Homme. Surtout que cette femme du peuple, courageuse et dynamique, s'est enchée sur les misères des petites gens avec un tel sens de l'humain que ses chansonettes sont encore vraies, vingt ans après sa mort. Comme l'écrit Doris Lussier dans sa préface: «Il faut dire merci à Réal Benoit de s'être penché sur l'histoire de Madame Bolduc. Son livre,tout plein de détails passionnants sur une vie qui par certains aspects est une leçon, nous fait mieux comprendre l'ARTISTE en nous montrant la FEMME qu'à été Madame Bolduc.»

Musiciennes de chez nous - Gingras, Claude (École de musique Vincent-d'Indy, 1955)

L’Albani. Sa carrière artistique et triomphale - Charbonneau, Hélène (Imprimerie Jacques-Cartier, 1938)

Albani (Emma Lajeunesse) - Legendre, Napoléon (Imprimerie A. Coté et Cie, 1874)
Le Rossignol du Canada français, la connaissiez-vous ? Auriez-vous aimer l'entendre chanter ? Une soprano tout en douceur... Voyez ce que le travail acharné a fait de cette dame une célébrité internationale.

Music, mothering and Martha Wainwright - ABC Radio Australia

La route de Lhasa (1972-2010) - Andrieu, Elise; France Culture

Y a-t-il une compositrice en musique au programme ? - Carignan, Nicole; Vincent, Jean Windsow (Musique et pédagogie)